Upregulation of YAP attenuates doxorubicin-induced cardiotoxicity through inhibiting ferroptosis - Yuming Zhang; Anbo Zhao; Li Tang; Shicheng Xia; Rui Wang; Qin Gao; Hongwei Ye (Tissue and Cell, 2027)

Production of bioemulsifier by Serratia marcescens and its potential application in oily sludge washing remediation - Rui Tang; Na Liu; Yongsheng Zhao (Bioresource Technology, 2027)

CFD-based approaches for low-carbon shipping: A systematic review - Ranqi Ma; Zhiqiang Tang; Haoyang Zhao; Junhao Zhao; Rui Zhang; Zhuang Wang; Jianlin Cao; Yuhao Xie; Lianzhong Huang (Marine Pollution Bulletin, 2026)

A robust wide-pH-range hydrogen evolution catalyst via stabilizing amorphous Ru on a COF-derived carbon framework - Yujie Tang; Yunqi Song; Yumei Zhang; Xueni Ma; Fei Ye; Rui Zou; Yao Yao (Fuel, 2026)

Scenario-based zoning of vegetation water-use efficiency risk for ecological restoration prioritization under compound drought in China - Ninglei Ouyang; Xiaoping Rui; Xuepeng Zhang; Heng Tang; Yiheng Xie; Hongyue Zhang (Ecological Engineering, 2026)

Cyclic regeneration and up-concentration for nitrate recovery from wastewater via in situ NaNO3 generation under saline, fully autotrophic nitrification conditions - Molin Lian; Zihang Ma; Guang Chen; Siqi Yu; Qing Xia; Bingjie Lin; Xiangdong Xu; Rui Tang; Zhen Zhou (Bioresource Technology, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Modeling fracture behavior of rock-concrete composite using a grain-based and phase-separated mesoscale thermomechanical FDEM model - Tengfei Guo; Xu Chang; Chunan Tang; Changfu Wei; Wei Kuang; Yichao Rui (International Journal of Rock Mechanics and Mining Sciences, 2026)

Advances in selenium-containing brown rice protein: structural characteristics, functional modification, and applications - Shu Li; Xinjie Shang; Yaxin Wu; Yumeng Wang; Shiyu Lin; Zexu Li; Zhaohui Xu; Yixuan Li; Yao Tang; Rui Yang (Food Hydrocolloids, 2026)

Riverine transport dynamics and historical trends of emerging and legacy flame retardants in an urbanized coastal zone: Pollutant management effectiveness in China - Jun-Rong Liang; Hui-Ping Wen; Ting Pan; Rui Tang; Lei Mai; Chen-Chou Wu; Ze-Hua Liu; Eddy Y. Zeng (Environmental Pollution, 2026)

Dominant taxa, rather than Shannon diversity, drive zooplankton stability across scales - Zeng Lei; Zhang Rui; Chen Yuxiang; Liu Beibei; Zheng Tingting; Li Wuhui; Tang Yuqi; Li Yating; Xiang Yuqi; Nie Mengwei; Chen Guobao (Estuarine, Coastal and Shelf Science, 2026)

Ascorbic acid enhanced performance of trace Cu(II)-Peroxydisulfate in oxidation of PPCPs: Mechanism and application - Xiujuan Kong; Rui Lu; Jielian Li; Yiming Qiu; Penghui Du; Kexin Tang; Jiaxi Lu; Wangdui Bianba; Yixin Hou; Yinuo Jia (Chemical Engineering Journal, 2026)

Modeling preferential flow and deep drainage in a long-term furrow-irrigated cotton–wheat rotation on a shrink–swell clay soil in semi-arid Australia - Rui Chen; Anthony J. Ringrose-Voase; Anthony J. Nadelko; Igor Bogunović; Lana Filipović; Vinod Phogat; Hailong He; Michael J. Bell; Tong Li; Chaosheng Tang; Zhenhua Wang; Vilim Filipović (CATENA, 2026)

Machine learning-guided discovery of poly(ethylene terephthalate)-binding modules to enhance durable whole-cell degradation - Rui Long; Yaxin Tang; Chengyong Wang; Tangli Yang; Wei Liu; Ling Jiang (Bioresource Technology, 2026)

Using spherical protrusions for simultaneous pressure pulsation mitigation and efficiency enhancement in a giant Francis turbine across a wide load operation - Lei Tang; Xiao-Wen Huang; Rui Zhao; Tian-Yi Shi; Wen-Quan Wang (Ocean Engineering, 2026)

Co-inoculation of lactic acid bacteria improves silage quality and mitigates antibiotic resistance gene transmission by restructuring the microbial community in hybrid Pennisetum silage - Duoting Wu; Wan Zhong; Zhisheng Wang; Xinyan Tao; Liyuan Shi; Peng Dai; Fali Wu; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Yiping Tang; Huawei Zou; et al. (Journal of Environmental Chemical Engineering, 2026)

Electro-activated potassium ferrate pretreatment for micropollutant removal and membrane fouling mitigation: Insight into oxidation and foulant structural changes - Qibin Xu; Qinglin Zhang; Weiping Sima; Henjun Tang; Jian Tan; Yi Liao; Jianwei Dong; Rui Miao; Le Han; Chun Zhao (Journal of Environmental Chemical Engineering, 2026)

Composition-dependent interactions and thermal energy demand in lignocellulosic biomass pyrolysis for sustainable energy recovery - Mingming Liu; Yiyun Zhang; Wenhao Tang; Chenyi Duan; Minmin Gao; Chao Li; Rui Xu; Samuel Mbugua Nyambura; Xiaojun Gao; Xueru Zhu; Hua Li (Journal of Environmental Chemical Engineering, 2026)

Linkage of the stationary threshold sizes of surface roughness and shear strength for natural rock joints: A quantitative estimation framework - Rui Yong; Changshuo Wang; Shengqi Yang; Zhicheng Tang; Shigui Du; Nick Barton (International Journal of Rock Mechanics and Mining Sciences, 2026)

Decoding lipid signatures and aroma characteristics of four Chinese traditional dark teas via integrative lipidomics, volatilomics, and quantitative descriptive analysis - Shan Zhang; Ruizhi Tang; Yunxia Wang; Ying Wang; Chuang Zhou; Rui Shen; Rui Liang; Niuniu Mao; Yinzi Chen; Nan Deng; Qinghua Zhou; Jia Li; et al. (Food Research International, 2026)

Polysaccharide–metal complexes for precision nutrition: Intelligent delivery, gut microbiota modulation and gut–brain communication - Xiaoliang Zhang; Rui Tang; Zhi Wang; Hong Zhuang (Food Bioscience, 2026)

Establishment of a novel brain cell line from grass carp (Ctenopharyngodon idella) with high transfection efficiency and CRISPR/Cas9-mediated genome editing capacity - Zi-Ling Qu; Tao Liu; Tang-Kai-Yuan Qin; Hua-Mei Yue; Ling Huang; Rui Ruan; Chang-Song Wu; Huan Ye; Chuang-Ju Li (Fish & Shellfish Immunology, 2026)

Maternal exposure to particulate matter during pregnancy and offspring liver function - Ziyi Zhou; Bin Sun; Yudiyang Ma; Ning Chen; Haibo Li; Wenpu Shao; Rui Tang; Lei Zheng; Meiqi Xing; Xinru Zhao; Yibing Zhu; Yaohua Tian (Environmental Pollution, 2026)

Impacts of engineering activities on the permafrost environment in the Hola Basin in the Northern Da Xing'anling Mountains in Northeast China - Hongwei Wang; Xiaoying Li; Ruixia He; Juan Zhang; Wenhui Wang; Yuan Qi; Jinlong Zhang; Rui Yang; Yan Li; Xiaoying Jin; Shuai Huang; Jianjun Tang; et al. (Engineering Geology, 2026)

Polysiloxane-enabled dual-interphase engineering coupled with fluorescence diagnosis of Ni2+ dissolution for 4.6 V lithium metal batteries - Hankun Zhang; Jiacheng Yan; Benhua Wang; Jinqiang Gao; Chao Fu; Rui Zhang; Xiaowei Huang; Xiaowei Tang; Zhengzhao Yang; Kefei Wang; Bowei Ju; Xiangzhi Song; et al. (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Harnessing a MMP-sensitive fluorescent probe for in-situ and reversible monitoring MMP alteration in dual color based on aggregation/monomer mechanism - Mengmeng Wei; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Yi Qian; Jing Xu; Xiaoyan Tang; Jiaojiao Liu; Shenqiang Wang; Tingwang Jiang; Xifeng Yang; Xuekun Hong; et al. (Analytica Chimica Acta, 2026)

A robust method for the simultaneous quantification of 30 legacy and emerging per- and polyfluoroalkyl substances (PFAS) across multiple marine media - Nuo Chen; Jing-Chun Feng; Li Tang; Rui Hou; Si Zhang (Marine Pollution Bulletin, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Critical review on strategies for the removal of antibiotics from water and wastewater: Present situation, challenges, and perspective - Ruiwu Zhou; Wei Pan; Weichao Huang; Ping Yu; Binrui Chen; Ruizhe Zhao; Lirong Chen; Rui Tang (Process Safety and Environmental Protection, 2026)

A comparative evaluation of a depth-robust integrated rainfall noise metric for passive rainfall monitoring in shallow water - Qingming Zhang; Qi Li; Dajing Shang; Rui Tang; Zhenxing Zhao (Ocean Engineering, 2026)

Extracellular polymeric substances-mediated detoxification of roxarsone in anaerobic granular sludge: Molecular insights and the critical role of proteins - Yuxuan Wang; Guanbao Yao; Rui Tang; Lei Chen; Shoujun Yuan; Zhen-Hu Hu; Xinmin Zhan (Journal of Hazardous Materials, 2026)

Product-grade enrichment of byproduct deuterium in PEM natural water electrolysis for hydrogen production - Zezheng Zhang; Jinguang Cai; Chao Lv; Ning Zeng; Aojie Liu; Qin Li; Liuxin Yang; Rui Hou; Siyi Liu; Peilong Li; Yan Shi; Xiaopeng Wang; et al. (Journal of Cleaner Production, 2026)

Synergistic utilization of ternary solid wastes for sustainable red sandstone subgrades: A simplex-centroid design approach - Weilong Song; Yunfei Han; Huayan Yao; Rui Tang; Yulu Cao; Feng Xiong; Fan Yang; Yufan Chen (Journal of Environmental Management, 2026)

Green extraction of non-starch polysaccharides from millet using a deep eutectic solvent: structural elucidation and structure-activity relationship of their inhibition of α-glucosidase - Yuxin Li; Rui Fang; Xia Tang; Pravin Ojha; Jingke Liu; Qinghai Sheng; Liangfu Zhou (Food Chemistry, 2026)

Prenatal Heat Wave Exposure and Renal Function in Early Childhood: Findings from a Chinese Birth Cohort - Yibing Zhu; Rui Tang; Yudiyang Ma; Ning Chen; Xinru Zhao; Wenpu shao; Yaohua Tian; Chong Miao (Environmental Research, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

From vision to physics: Generative occupant modeling and 3D spatial data architecture in indoor environments - Rui Li; Lu Tang; Haibo Feng (Energy and Buildings, 2026)

Interfacial-confined metal-support interaction in rare-earth oxide enables selective high-valent iron-oxo species generation for efficient water purification - Min Tang; Baoleerhu Borjigin; Wu Liu; Qi Zhang; Yanjun Zhao; Rui Peng; Jinquan Wan (Chemical Engineering Journal, 2026)

Fracture development characteristics in carbonate reservoirs: insights from stress field simulation with a heterogeneous rock mechanics model and adaptive boundaries - Yao Wang; Wenlong Ding; Zhongliang Guo; Chenggang Li; Bochao Tang; Ziyou Zhang; Dong Fu; Rui Xia (Carbonates and Evaporites, 2026)

Study on thermal damage and pore structure evolution of granite under high temperature and different cooling methods - Yingjie Zhang; Chuanqu Zhu; Yanlin Zhao; Lianyang Zhang; Shuailong Lian; Rui Luo; Pei Tang (Bulletin of Engineering Geology and the Environment, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Inhalable HUCMSC-Lipo biomimetic formulation inhibits fibroblast activation in mouse and non-human primate pulmonary fibrosis models - Fangyu Zhao; Yige Sun; Haoran Wang; Dayong Hou; Rui Zhang; Wenjing Xia; Yongchen Zhang; Luyao Li; Xueqi Zhao; Kaiqi Wang; Wenwen Pan; Jiannan Wang; et al. (Science Bulletin, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

A new dynamic thrust prediction method for tracked deep-sea mining vehicles based on structural integrity evolution of deep-sea sediments - Zhiyong Xu; Haining Lu; Jianmin Yang; Maozhen Xia; Peng Tang; Rui Qin; Pengfei Sun (Ocean Engineering, 2026)

From acute defense to prolonged metabolic homeostasis: Insights into microalgae responses to PVC microplastic exposure - Jia Liang; Xiao Tan; Jiawei Li; J. Paul Chen; Yuanyuan Tang; Zhipeng Duan; Jiang Huang; Rui Zhu (Journal of Hazardous Materials, 2026)

Genetic discrimination of the Dongshan Pb-Zn-Cu deposit based on sphalerite chemistry - Yi-Chen Chen; Shi-Jiong Han; Cheng-Gang Cao; Jun-Wei Bo; Yu-Rui Yuan; Ming-Yu Tang; Jin-Xin Yuan (Journal of Geochemical Exploration, 2026)

Preparation of reinforced PVC composites utilizing waste PET fabrics as an alternative to wood materials and potential applications in furniture - Chuanyun Tang; Zhen Shi; Rui Dan; Pu Zheng; Shuo Nie; Xiaoli Wang; Yuanyuan Hu; Quanquan Wang (Journal of Environmental Chemical Engineering, 2026)

Size-Dependent grazing and trophic cascades shape Zooplankton–phytoplankton interactions in Eutrophic Lake - Jin Lu; Yue Wu; Jinsheng Yang; Xiaoxian Tang; Rui Gao; Santao Xie; Jianxin He; Huaizhen Gao; Kaining Chen; Xiaoli Shi (Harmful Algae, 2026)

Micritization mechanism in penecontemporaneous carbonate rocks: coupled C − Ca cycles and constraints from diagenetic environments - Yunfeng Zhang; Menghao Zhu; Wen Yan; Haizhou Qu; Kexin Guo; Weihai Xu; Xiyang Zhang; Fei Tan; Yu Tang; Rui Wang; Guanghui Wu; Shuai Huang (Geochimica et Cosmochimica Acta, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Pea protein isolate as a versatile and sustainable protein: basic characteristics, applications, and limitations - Zexu Li; Xinjie Shang; Zhaohui Xu; Jingjing Xu; Yao Tang; Rui Yang (Food Chemistry, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Autophagy dysfunction in pancreatic acinar cells in acute pancreatitis: from molecular mechinery and trypsinogen activation to heterogeneity and therapeutic implications - Yuping Feng; Wen Guo; Rui Wu; Tingting Tan; Chen Tang; Li Zhang (Journal of Molecular Histology, 2026)

Characteristics and triggering mechanism of buoyancy-driven and seepage-driven landslides: insights from physical model tests - Pengju An; Huiming Tang; Changdong Li; Qianyun Wang; Kun Fang; Rui Yong (Bulletin of Engineering Geology and the Environment, 2026)

Compartmental pH regulation in cancer and antitumor immunity: therapeutic opportunities and challenges - Fangquan Chen; Xiutao Cai; Qile Zhou; Zhen Huang; Jie Wang; Rui Kang; Daolin Tang; Jiao Liu (Apoptosis, 2026)

An ecological security framework for land use conflict assessment and spatiotemporal dynamics: a case study of the Chengdu-Chongqing Urban Agglomeration - Lei Zhu; Yi He; Dejing Chen; Yanhong Tang; Rui Yan (Environment, Development and Sustainability, 2026)

Synergistic pathways and microbial mechanisms of iron-mediated nitrogen transformation in wastewater treatment systems: a critical review - Xiaoyi Sun; Shenbin Cao; Meihui Tang; Yongzhen Peng; Rui Du (Water Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Unveiling spatiotemporal mechanisms of urban traffic: Multi-scale determinants and explainable street-level dynamics of a graph neural network in Berlin - Shiyu Tang; Jin Rui; Sven Lautenbach; Christina Ludwig; Sukanya Randhawa; Steffen Knoblauch; Alexander Zipf (Journal of Transport Geography, 2026)

Novel non-thermal plasma based strategy to synthesize high-performance multistage mesoporous cobalt-ceria oxides for plasma-catalytic decomposition of environmentally hazardous acetone - Lu Liu; Jian-hua Liu; Zhen-yun Wang; Guang-cai Shao; Yan-gang Hu; Karen Leus; Jian-li Mi; Chuan-long Ma; Rui-tang Guo; Qing-shan Wang; Anton Nikiforov; Pascal Van Der Voort; et al. (Journal of Hazardous Materials, 2026)

Invasive giant African snails as potential reservoirs of antimicrobial resistance and bacterial pathogens in urban park - Yiyue Zhang; Zhonghui Tang; Huayuan Shangguan; Rui Zhu; An Xie; Qiansheng Huang; Jianqiang Su; Patrick O'Connor; Yong Jiang; Xin Sun (Journal of Environmental Management, 2026)

Molten salt − assisted graded carbonization tailors hard carbon pores toward enhanced sodium ions storage - Zuqin Duan; Rui Tang; Ying Mo; Peng Gao; Yan Duan; Hui Liu; Aiping Hu; Jilei Liu (Fuel, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Less is more: Retaining uncyclized o-quinone group in quinone/pyrazine hybrid molecules for high-energy zinc–organic batteries - Han Yan; Rui Wang; Jinyin Yu; Xiaotang Gan; Housheng Gong; Qian Wang; Zewen Zhu; Xiang Tang; Zhiping Song (Chemical Engineering Journal, 2026)

Well-defined edge structured graphene as a gas sensor - Chuan Tang; Rui Wang; Zhili Huang; Kakarla Raghava Reddy; Bai Cheolho; Ch. Venkata Reddy; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Multi-level design of a chitosan-based membrane: from sisal fiber reinforcement to surface micropatterning and hybrid hap for enhanced bone regeneration - Shuo Tang; Rui Lin; Yuqing Wang; Xinyuan Feng; Fang Shi; Yupeng Guo; Shu Huang; Xiang Hu; Liuyun Jiang (Carbohydrate Polymers, 2026)

De novo synthesis of p-coumaric acid from fructose and carbon dioxide in chemoautotrophic Cupriavidus necator H16 - Ruohao Tang; Cunxi Dai; Caiyun Liu; Shuqi Tan; Yuanxin Ma; Yaru Fan; Rui Zeng; Xiaochun Qin (Systems Microbiology and Biomanufacturing, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Machine learning-driven error correction and feature analysis for near-surface wind fields in complex terrain - Shunxian Tang; Shiqian Li; Yusheng Chen; Rui Li (Advances in Space Research, 2026)

Correction to: Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Ecosystem service dominance of natural forest vegetation in karst landscapes: evidence from Southwest China - Zhixin Li; Rui Li; Bin Yan; Shitian Tang; Jie An (Environment, Development and Sustainability, 2026)

Osteopontin as an emerging multifunctional food ingredient: recent advancements, production, applications, and challenges - Shiyu Lin; Xiuxiu Teng; Xinjie Shang; Shu Li; Jingjing Xu; Yao Tang; Rui Yang (Critical Reviews in Food Science and Nutrition, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Glucose stabilizes the KLF5 transcription factor to promote glycolysis and malignancy of basal-like breast cancer - Rui Liu; Yu Tang; Wenjing Liu; Chunli Zhou; Zhongmei Zhou; Wen Liu; Qiang Yu; Longlong Zhang; Jian Sun; Jing Peng; Yongchun Zhou; Dewei Jiang; et al. (Science Bulletin, 2026)

Prediction of ship motions based on hybrid ACO–PSO and CNN-BiLSTM-SAT algorithm - Haoyang Yu; Haoyun Tang; Xianku Zhang; Rui Zhu (Ocean Engineering, 2026)

Enhancing runoff simulation in data-scarce mountainous regions: a coupled SWAT and transferable transformer approach - Yi He; Rui Yan; Yanhong Tang; Jinyu Zhang; Hui Qian; Dejing Chen; Lei Zhu; Xin Cao (Journal of Hydrology, 2026)

Lignin-based sunscreen materials: A review of mechanisms of action, precision modification strategies, multifunctional application advances, challenges and prospects - Yuan Chen; Zibo Yu; Rui Tang; Jiayi Sun; Xigao Jian; Jinyan Wang; Xiaozhou Zhang; Xing Wang; Jingyu Xu (Journal of Environmental Chemical Engineering, 2026)

Relationship of catalytic performance and catalyst structure evolution based on pressurized CH4-CO2 reforming reaction over carbon-supported Co-Ir alloy catalysts - Wen Tang; Jing-Pei Cao; Xiao-Yan Zhao; Dan Xie; Kai-Rui Luan; Chang-Jiang Li; Qi-Ming She; Tungalagtamir Bold (Fuel, 2026)

Operation-resolved VOC emissions from electronics manufacturing: Implications for ozone formation, toxicity, and risk-oriented management - Jun Tao; Rui Xu; Zhisheng Zhang; Zijun Tang; Ping Fang; Leilei Fei; Zhihui Li; Zhihang Chen (Environmental Research, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Synergistic parameter optimization Unlocks High-Efficiency H2/CO2 Bio-methanation: Decoupling mass transfer enhancement from microbial Trade-offs - Qingqing Ye; Hualiang Fang; Rui Tang; MingDa Li; Xin Li (Bioresource Technology, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Drought Duration Alters the Soil Water Threshold Corresponding to the Leaf Photosynthetic Efficiency of Potato in Semi-arid Regions - Yang Yang; Hong Zhao; Shi-qiong Yang; Di-hua Cai; Kai Zhang; Yu-rui Tang; Yue Qi; Peng-cheng Huang (Potato Research, 2026)

Rhizosphere microbial carbon utilization stimulates soil phosphorus fraction transformation in response to maize (Zea mays L.) and soybean (Glycine max.) interspecific interactions - Ruixue Wang; Lizhen Su; Dingjin Li; Zikun Yang; Rui Feng; Yi Zheng; Li Tang (Plant and Soil, 2026)

Optimizing drug delivery in smart pharmacies: a novel framework of multi-stage grasping network combined with adaptive robotics mechanism - Rui Tang; Shirong Guo; Yuhang Qiu; Honghui Chen; Lujin Huang; Ming Yong; Linfu Zhou; Liquan Guo (Medical & Biological Engineering & Computing, 2026)

Linking soil nematode communities to plant- and microbial-derived carbon in a 15-year field experiment - Jigao Wang; Yanli Jing; Tao Wang; Kai Wei; Rui Yang; Jinlong Yan; Jialiang Tang; Bo Zhu (Soil Ecology Letters, 2026)

Coral-based reconstruction of interannual and decadal SST variability in the northern South China Sea during the mid-Holocene - Zhiheng Wu; Tingli Yan; Rui Tang; Ben Wang; Yanjun Mei; Ning Zhao (Geo-Marine Letters, 2026)

Extracellular Vesicle-Associated MicroRNA-25-3p Derived from Pancreatic Cancer Cells Promotes Hepatic Stellate Cell Activation and Enhances Cancer Progression - Xuejiao Wu; Rui Shen; Zilin Yang; Yuming Tang; Jia Huang; Weiyan Yao (Biochemical Genetics, 2026)

Laboratory Observation of Grain Size Controls on Granite Pulverization Under Dynamic Compression - Jiazhi Zhang; Yingchun Li; Zhiyi Liao; Fuxin Rui; Chun’an Tang (Rock Mechanics and Rock Engineering, 2026)

Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Distribution and transport of trace organic contaminants from land to the coastal sea - Shi-Jie Lv; Ting Pan; Rui Tang; Jun-Rong Liang; Hui He; Lei Mai (Marine Pollution Bulletin, 2026)

Machine learning assisted-hyperspectral imaging for in-situ evaluation of compost maturity - Jianmei Zou; Shengui Tang; Chao Chen; Junyu Tao; Rui Liang; Xianjia Jiang; Yihao Hua; Fanrui Chen; Shenglin Yang; Fei Shen (Waste Management, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Spatially explicit process-resolved fluxes and microbial drivers: Linking community succession to greenhouse gas emissions from full-scale industrial wastewater treatment - Weiwei Kong; Rui Dai; Zhaohui Yang; Qinyang Li; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Water Process Engineering, 2026)

Extreme rainfall intensifies nitrogen responses through baseflow in arid and semi-arid river basins - Jinghui Dou; Rui Xia; Zixuan Tang; Zhen Huang; Xiaohui Jiang; Kai Zhang; Lina Li; Chao Yan (Journal of Hydrology, 2026)

Sustained grain cadmium reduction in rice-wheat rotation: A cost-effective CaCO3-based amendment strategy from three-year trials - Zhi-Xian Tang; Ge Dong; Zhong-Rui Xu; Zhong Tang; Fang-Jie Zhao; Peng Wang (Journal of Environmental Management, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Application of layered double hydroxides (LDHs) derived catalysts for selective catalytic reduction of NOx with NH3 - Tian-yu Lv; Zuo-lin Cui; Rui-tang Guo (Fuel, 2026)

Fish oil emulsion stabilized by multi-modified β-Lg improves lipid metabolism, inflammation, and hepatic–gut homeostasis in high-fat diet mice - Qingchun Zhang; Hao Zhu; Rui Wang; Weilin Liu; Jianfei He; Wei Tang; Jianhua Liu (Food Bioscience, 2026)

Peak shear strength of rock discontinuities in the near-surface: Criteria, influencing factors, challenges, and perspectives - Shigui Du; Man Huang; Rui Yong; Nick Barton; Zhicheng Tang (Engineering Geology, 2026)

Fluoride-ion mediated radical scavenging in a hydrophobic microenvironment for durable PEM fuel cells - Xuelin Wei; Gang Zhu; Donghao Ye; Aojie Zhang; Hao Zhang; Wangkai Zhu; Tian Tian; Shengqiu Zhao; Jiangping Song; Rui Chen; Haolin Tang (Chemical Engineering Journal, 2026)

Constructing a Z-scheme heterojunction on leather waste-derived biochar supporting graphitic carbon nitride for highly-efficient photocatalysis toward water decontamination - Liming Zhao; Rui Dai; Yuling Tang; Xin Cheng; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Engineering Escherichia coli cell Factories for continuous 5′-cytidine monophosphate production via biofilm-anchored dual-enzyme cascade catalysis - Wenjun Sun; Shiya Zhu; Qiwei Dong; Shuyan Tang; Qingguo Liu; Yu Sha; Tianpeng Chen; Rui Wang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Analysis of the species distribution and drug resistance of pathogenic microorganisms causing diabetic foot infections in Southwest China from 2020 to 2024: a retrospective cross-sectional analysis - Shangyu Zhang; Junchi Chen; Rui Sun; Yu Pan; Yusen Zhuo; Li Tang; Jianhua Zhu; Shuyang Li; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Common respiratory virus spectrum and epidemiological trends among children in Northwest China during the post-COVID-19 era - You Wu; Weina Yang; Congcong Chen; Jianfei Shi; Peiwen Ning; Jiahua Liu; Rui Wu; Zengguo Wang; Jianyong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Trajectories of vegetation dynamics and their driving factors across China Ecosystem Research Network: A long-term assessment (2000–2024) - Shuyi Zhang; Ziwen Jin; Mengyao Ci; Ke Zeng; Yue Wang; Hanxin Tang; Rui Zhang; Chaolin Cai; Xianzhong Cao; Min Liu (Journal of Geographical Sciences, 2026)

Prediction and application of water inrush in water-rich area of TBM construction deep buried tunnel - Fa-yong Gao; Kun Yang; Yan-qiang Cheng; Yong-tao Ma; Kang Fu; Ming-yang Tang; Jin-rui Duan (Applied Geophysics, 2026)

Comprehensive insights into the occurrence, spatiotemporal distribution, source apportionment, and risk assessment of antibiotics in Chaohu Lake - Qian Tang; Yongmei Zhang; Fali Liu; Yancan Wu; Jifei Hou; Jie Tang; Rui Liang; Dapeng Deng; Xuede Li (Environmental Monitoring and Assessment, 2026)

Vibrio sinaloensis NH-7 induces yellow-spot and rough-shell syndrome in Porphyra sensu lato (Bangiales, Rhodophyta) - Jiaxia Lv; Qiqin Liu; Xinwei Wang; Caihua Lin; Yangyin Mao; Xianming Tang; Juanjuan Chen; Haimin Chen; Rui Yang (Aquaculture, 2026)

Study on mechanical response and meso-scale behaviour of pile-soil interface under traffic loading - Qingyao Zhang; Jukun Guo; Rui Guo; Wan Zhang; Shengxiang Tang; Yajuan Huang; Jiahao Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Boundary-based random forest leveling of multi-map geochemical data: A case study of the Baiyinchagan-Maodeng Area, Inner Mongolia - Rui Tang; Cheng Li; Keyan Xiao (Journal of Geochemical Exploration, 2026)

Fabrication of novel FO membrane supported on PU-PAN electrospun nanofiber membrane for high-permeability and selectivity - Dibakar Pandaya; Yu-Qian Yue; Zhen-Liang Xu; Ming-Xiao Zhang; Rui Jia; Mateen Hedar; Muhammad Irfan; Liang Cheng; Yong-Jian Tang; Mahesh Kumar Joshi (Journal of Environmental Chemical Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Revisit the improvement of coagulation pretreatment on ozonation performance: The critical roles of HO• and O3 for effluent organic matter transformation and micropollutant degradation - Rui Hu; Hao-Tong Zheng; Boxi Tang; Jialing Tu; Yu-Hong Cui; Xuedong Zhai; Gang Wen; Zheng-Qian Liu (Journal of Cleaner Production, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

Estimating road speed classes: Integrating OpenStreetMap and Street View imagery for missing data imputation - Shiyu Tang; Sukanya Randhawa; Jin Rui; Christina Ludwig; Steffen Knoblauch; Charles Hatfield; Alexander Zipf (Computers, Environment and Urban Systems, 2026)

Enhanced performance of direct contact membrane distillation for aquaculture wastewater treatment via far-ultraviolet/sulfite-based pretreatment - Bing Zhang; Rui Guo; Heli Tang; Bing Zhang; Haiqing Chang; Wenxin Shi (Chemical Engineering Journal, 2026)

P2X7 receptor mediates the anti-tumor effect of running on cervical cancer in mice - Hai-Yun Xiong; Rui Li; Xiu-Min Hu; Yi Zhang; Patrizia Rubini; Peter Illes; Yong Tang (Purinergic Signalling, 2026)
Previous studies have suggested that running exerts anti-tumor effects on various cancers through multiple pathways. It has been reported that the P2X7 receptor (P2X7R) may display anti-tumor activity in cervical cancer cells, and running can regulate P2X7R expression and function in mice. However, the specific impact of running on cervical cancer and whether its underlying mechanism is associated with the regulation of P2X7R levels remains to be elucidated. In this study, mice bearing U14 cervical cancer tumors were used as a model to explore the association between running and P2X7R in cervical cancer. The results showed that running significantly inhibited tumor progression in mice, accompanied by an increase in P2X7R protein expression in tumor tissues. Additionally, treatment with the P2X7R antagonist JNJ-47965567 alone or in combination with running intervention promoted tumor growth and attenuated the anti-tumor effect of running. In contrast, the P2X7R agonist BzATP alone or combined with running intervention exerted anti-tumor effects and enhanced the anti-tumor effect of running. In conclusion, the present findings suggest only a pharmacological association between P2X7R and the anti-tumor effect of running against cervical cancer progression, given that genetic validation was not performed in this study. The potential involvement of immune mechanisms remains an inference and requires further experimental validation. As a possible therapeutic target, P2X7R provides supportive data for the treatment of cervical cancer and the clinical exploration of running as an adjuvant intervention.

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Flexible Ultrasound Patch for Noninvasive, Targeted Anti-Angiogenic Therapy of Unstable Carotid Plaques - Jie Hu; Mingke Jiao; Chenchen Tang; Ping Liang; Jingwei Tang; Li Wan; Jimei Chen; Rui Li (Annals of Biomedical Engineering, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Construction and Simulation of Global Land Surface Microwave Emissivity Atlas Using FY-3D Satellite Data - Yonghong Liu; Fuzhong Weng; Fei Tang; Yang Han; Qingyang Liu; Rui Li; Yongming Xu; Jun Yang (Advances in Atmospheric Sciences, 2026)

Elucidating the pharmacological mechanism of Yangming-Kaixin-Yizhi formula in inhibiting neuronal ferroptosis via Nrf2 in Alzheimer’s disease: a study combining network pharmacology, transcriptomics, and experimental validation - Rui Xiong; Pan Liu; Lu Wang; Shipeng Zhang; Hengxu Liu; Cuiping Rong; Nurmuhammat Kehriman; Jianjun Wang; Jing Wang; Xiaodan Lai; Yong Tang (Metabolic Brain Disease, 2026)

In situ biofilm development on microplastics and its impact on PFAS adsorption in aquatic environment - Guoqing Hou; Rui Zhang; Tianhui Zhao; Mengyuan Fang; Lin Niu; Qitao Lei; Qiang Li; Nuo Chen; Zhi Tang; Xiaoli Zhao; Fengchang Wu (Water Research, 2026)

Overcoming temperature and substrate limitations of anammox via partial denitrification: Stable performance, microbial structure, and N2O mitigation - Rui Du; Meihui Tang; Shenbin Cao; Yongzhen Peng (Water Research, 2026)

Thermal resilience in the built environment: A critical review - Yingyue Li; Eirini Tsouknida; Tom Collins; Ashley Bateson; Rui Tang; Esfandiar Burman (Sustainable Cities and Society, 2026)

Heavy metal removal and concurrent stabilization of pig manure via constructed wetland-microbial fuel cell driven by sponge iron: Microbial response and mechanistic insight - Qingyun Zhang; Wanqing Jin; Xiaolu Tang; Xiang Mao; Rui Zuo; Yajun Hong; Dayong Xu (Process Safety and Environmental Protection, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Sustainable electronics manufacturing using environmentally safe short chain fluorinated Gemini surfactants for high efficiency printed circuit board cleaning - Yunye Huang; Lewen Huang; Chen Zhou; Danni Tang; Xiangyu Yin; Longqiang Xiao; Rui Zhao; Linxi Hou (Journal of Cleaner Production, 2026)

Dual-group functionalized self-floating adsorbent based on hollow glass microspheres for removal of diclofenac sodium and Moxifloxacin: Synthesis, performance and mechanism - Erming Ouyang; Jianxing Que; Wenqing Xia; Hongwei Yang; Jiachang Tang; Rui Zhao (Journal of Environmental Management, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Self-enhancing climatic resilience of surface soil through bio-carbonation constructed barrier - Rui Wang; Chao-Sheng Tang; Guang-Hui Lei; Xiao-Hua Pan; Zhi-Hao Dong; Shao-Dan Wang; Xiancai Lu (Engineering Geology, 2026)

Predicting pedestrian-level melanopic illuminance from multi-source urban data with explainable machine learning - Wenjin Hong; Zhe Kong; Peng Tang; Ziqi Fan; Rui Duan; Zixuan He; Xintong Li; Xinyi Wu (Building and Environment, 2026)

Selenium-Enriched Akkermansia muciniphila: A Novel Probiotic Bacterium for Se Supplementation - Wen Rui; Yuhang Sun; Xiaoqian Li; Jingpeng Yang; Xuna Tang (Probiotics and Antimicrobial Proteins, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Mechanism of baicalein from Wudang Mountain Scutellaria baicalensis Georgi. against atopic dermatitis based on network pharmacology, transcriptomics and in vitro experimental validation - Liu Tang; Gang Liu; Dan Li; Tianshuai Wang; Chun Wang; Guangwen Luo; Rui Peng; Xu Cai (Natural Product Research, 2026)

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

WTAP-mediated m6A modification of PRMT1 regulates cuproptosis to promote anaplastic thyroid carcinoma progression - Guoli Feng; Changju Chen; Yi Luo; Rui Chen; Xinghong Tang; Taolang Li (Tissue and Cell, 2026)

Multilayer hydrogel thermal management for high-efficiency solar cells - Rui Guo; Haotian Ding; Haoyu Pan; Yu Chen; Jiajun He; Huan Xing; Fei Xu; Jun Chen; Shaochun Tang (Science Bulletin, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Study on the irradiation control of urease activity and its solidification of red clay to enhance radon reduction - Yuanyuan Tang; Rui Liang; Jia Wei; Yiqing Sun; Weihang Peng; Fubing Li; Chengyu Zhang; Changshou Hong (Journal of Environmental Radioactivity, 2026)

Miocene carbonate crash in the eastern Pacific: A catalyst for early rare earth element enrichment - Yayue Tang; Dengfeng Li; Fei Huang; Rui Wang; Jiewei Hu; Jinzhou Peng; Yu Fu; Xiaoming Sun (Global and Planetary Change, 2026)

Study on flame retarding mechanism of 1,1,2,3,3,3-hexafluoro-1-propene - Rui Zhai; Jinkun Chen; Yongjie Shi; Yuan Zhuang; Xiang Li; Bin Ye; Lei Tang; Shancai Tang (Fuel, 2026)

Modification of β-lactoglobulin by glycation, high-pressure microfluidization and EGCG binding: Enhanced emulsifying and antioxidant properties - Rui Wang; Qingchun Zhang; Juan Qu; Jianfei He; Christos Ritzoulis; Weilin Liu; Wei Tang; Jianhua Liu (Food Research International, 2026)

Infrared spectroscopy combined with deep learning to describe the textural properties of cooked rice from raw materials: revealing spectral variations and internal correlations during processing - Rui Tang; Ting Yu; Zi Li; Junru Wu; Xiaoming Zheng; Leiqing Pan; Yang Chen; Kun Duan; Hui Dong; Weijie Lan (Food Control, 2026)

Enhanced seawater desalination dual-driven by synergistic photothermal and joule-heating effects in an engineered bilayer evaporator - Juan Jia; Ying Tang; Yang Song; Wenjing Zeng; Jinlong Shen; Hui Zeng; Zebao Rui (Chemical Engineering Journal, 2026)

Linking runoff and sediment characteristics to karst development degree in small watershed - Zhengyi Tang; Rui Li; Li Qin; Tao Song; Benjin Yu; Pingping Yang; Jun Jing; Linlv Xiao (CATENA, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Mitochondria to nucleus/nucleolus migration probe for in-situ and dual-color visualization of MMP alteration and monitoring apoptosis - Mengmeng Wei; Derong Xiang; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Jing Xu; Xiaoyan Tang; Qijian Zhang; Zhida Han; Xifeng Yang; Rui Yang (Analytica Chimica Acta, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

Bacterial transport enhancement by colloidal gas aphrons in heterogeneous aquifers: Performance evaluation and mechanistic insights - Yufeng Fu; Chuanyu Qin; Tingdi Zhang; Chengwu Zhang; Jintao Ru; Rui Tang (Water Research, 2026)

Estrogen inhibits granulosa cell apoptosis via nuclear receptors by suppressing death receptor and mitochondrial pathways in goat small antral follicles - Sihai Lu; Baijuan Yue; Yaju Tang; Haoyu Xu; Rui Xu; Xiaoe Zhao; Qiang Wei; Jia Xue; Meng-Hao Pan; Sha Peng; Baohua Ma (Theriogenology, 2026)

Effective domain adaptive shipwreck detection method in side-scan sonar images for unmanned underwater vehicles - Rui Tang; Yimin Chen; Dawei Gao; Jian Gao; Shaowen Hao (Ocean Engineering, 2026)

Preparation of iron oxide/montmorillonite catalyst and its green remediation performance of pyrene-contaminated soil - Yun-rui Zhao; Kang Zhou; Xiao-xiao Qi; Hui Shi; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Water Process Engineering, 2026)

Development of a new surface sediment connectivity model based on network analysis and application to the Yeji River watershed in the karst region of southern China - Feiyang Cai; Rui Li; Benjin Yu; Linlv Xiao; Ling Xiong; Zhengyi Tang (Journal of Hydrology, 2026)

Efficient oxygen evolution in acidic electrolysis of water using copper loaded with iridium nanoclusters - Yanan Song; Bingxin Zhang; Tai Xiang; Huabin Wang; Yong Zhang; Xiaoning Tang; Lin Tian; Rui Xu (Journal of Environmental Sciences, 2026)

Study on the flame inhibition characteristics and mechanism of R1233zd(E) - Rui Zhai; Zhijun Li; Yuan Zhuang; Bin Ye; Hongling Zhao; Lei Tang; Ke Wang (International Journal of Refrigeration, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Revealing the operando ORR mechanism of single-atom catalysts anchored in nanobowl structures for advanced hydroxide exchange membrane fuel cells - Sun-Tang Chang; Hui-Xin Liu; Yi-Ching Chu; Ying-Rui Lu; Chen-Hao Wang (Chemical Engineering Journal, 2026)

Sb(Ⅲ) oxidation by UV-based advance oxidation processes: Kinetics, radical contributions, influencing factors, and energy demand - Jinrong Lv; Min Liu; Lirong Zhu; Rui Tang; Zhongyue Liang; Ting Xie; Xuecai Tan; Bernard A. Goodman; Mengkai Li; Shaogang Liu (Chemical Engineering Journal, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Field measurements of the typhoon near-surface wind characteristics under different precipitation intensities - Yun Guo; Shengming Tang; Huan Li; Jie Tang; Shuai Zhang; Rui Peng; Xuhui He (Atmospheric Research, 2026)

The Role of Toll-like Receptor 3 Signaling in Cognitive Impairment Induced by Propofol Addiction - Jiahui Wu; Liyun Deng; Rui Gao; Ying Cui; Yidan Tang; Changliang Liu; Tao Zhu; Chan Chen (Molecular Neurobiology, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Study on pore characteristics of sandstone with different preloading ratios under high temperature - Chaolin Wang; Rui Wu; Can Du; Wei Tang; Jing Bi (Bulletin of Engineering Geology and the Environment, 2026)

A sustainable biochar system to significantly reduce global greenhouse gas emissions - Meng Tan; Jianwei Zhou; Peng Liu; Ziyi Zhou; Jinping Tang; Yingxiang Fei; Jing Shang; Xingjie Wang; Rui Qi (Mitigation and Adaptation Strategies for Global Change, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

From plant-based food waste to biochar: A green strategy for agri-food supply chain waste valorization–a comprehensive review - Xuejiao Chen; Yanbo Hao; Wei Lin; Liya Xie; Rui Yang; Wenliang Xiang; Zhilian Gong; Feng Gu; Hongyan Liu; Jie Tang (Trends in Food Science & Technology, 2025)

Spatiotemporal evolution of urban–rural ozone disparities and the “pollution transfer” effect in rapidly urbanizing regions - Rui Zhang; Shuyi Zhang; Hanxin Tang; Ke Zeng; Yue Wang; Jiarui Zhang; Mengyao Ci; Ziwen Jin; Min Liu (Urban Climate, 2025)

Additive effects of Lp(a) and inflammation on cardiovascular risk beyond LDL-C lowering: circulating and genetic evidence from 401,548 adults - Rui Li; Wenyue Dong; Wenxiu Wang; Youling Duan; Miao Zhang; Tao Huang; Xinwei Hua; Yi-Da Tang (Science Bulletin, 2025)

Arrangement optimization of wingsails subject to complex mutual aerodynamic interference: A numerical study - Ranqi Ma; Daize Li; Rui Zhang; Feng Tian; Zhiqiang Tang; Jianlin Cao; Yuhao Xie; Zihan Jing; Jijun Chen; Xiaowu Li; Lianzhong Huang (Ocean Engineering, 2025)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

Effects of a diet containing glutamine on the slaughter performance, meat quality, and skeletal muscle fiber types of feed-restricted yaks - Ziqi Yue; Shanpeng Ke; Liyuan Shi; Rui Hu; Zhisheng Wang; Quanhui Peng; Huawei Zou; Jianxin Xiao; Yahui Jiang; Fali Wu; Yiping Tang (Meat Science, 2025)

Editorial: Crust formation from subduction to collision - Rui Wang; Ming Tang; Qing Wang; Kang Chen; Peter A. Cawood (Lithos, 2025)

The detection method of ammonia nitrogen concentration in water bodies based on hyperspectrum - Yahe Di; Tao Li; Hui Ran; Rui Yang; Fei He; Aixuan Li; Chenzhan Tang; Wenjing Tian (Journal of Water Process Engineering, 2025)

Poly(ionic liquid)s-loaded metal-organic framework gel for CO2 capture and cycloaddition catalytic conversion - Rui Li; Yangyang Lei; Meilin Yin; Lipeng Wang; Shaokun Tang (Journal of Environmental Chemical Engineering, 2025)

Effect of pyrite on the bio-oxidation and arsenic migration of realgar mediated by Acidithiobacillus ferrooxidans - Rui Liao; Xin Sun; Shitong Liu; Anni Tang; Chenxu Wang; Guanzhou Qiu; Jun Wang; Baojun Yang (Journal of Environmental Chemical Engineering, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Multi-modified β-Lg-stabilized fish oil emulsions: physicochemical stability, antioxidant capacity, and bioavailability in Caco-2 cells - Qingchun Zhang; Hao Zhu; Rui Wang; Jianfei He; Christos Ritzoulis; Owen Griffith Jones; Weilin Liu; Wei Tang; Jianhua Liu (Food Chemistry, 2025)

Effect of modified β-lactoglobulin on the stability of algae oil emulsion: Storage, environmental and oxidative stability - Rui Wang; Jianfei He; Weilin Liu; Wei Tang; Jianhua Liu (Food Hydrocolloids, 2025)

Carbon dots-melatonin-chitosan coating to alleviate chilling injury, enhance storage quality and antioxidant capacity of yellow peaches - Kai Fan; Rui Tang; Lijing Li (Food Packaging and Shelf Life, 2025)

NepTrain and NepTrainKit: Automated active learning and visualization toolkit for neuroevolution potentials - Chengbing Chen; Yutong Li; Rui Zhao; Zhoulin Liu; Zheyong Fan; Gang Tang; Zhiyong Wang (Computer Physics Communications, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

Start-up and operational strategies for side-stream nitrification reactors in a cyclic up-concentration nitrogen recovery process: Enhancing targeted nitrate conversion and deciphering nitrogen metabolism - Molin Lian; Zihang Ma; Guang Chen; Xiangdong Xu; Rui Tang; Shikun Yan; Yu Wang; Yuyue Zhang; Zhen Zhou (Chemical Engineering Journal, 2025)

One-step hydrothermal upcycling of PET waste into carbon quantum dots for fabricating flame-retardant and toughened PET - Yuhang Wu; Jianfei Wei; Chaohui Ma; Linhan Bing; Chuanjiang Tang; Puzhen He; Zhenfeng Dong; Zhiguo Zhu; Xiaopeng Hu; Yanying Wei; Rui Wang (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Transcriptome Analysis Revealed the Copper Ion Uptake by Oocystis borgei from Offshore Polluted Water - Junyu Tang; Qizhao Liang; Rui Zhang; Xiaoping Huang (Marine Biotechnology, 2025)

Metformin suppresses gammadelta T17 cell differentiation alleviating DSS-induced colitis - Mingzhong Sun; Hongli Liu; Huixiang Ju; Hongmei Chen; Rui Yang; Dongmei Yan; Langping Shen; Aiting Cai; Yaru Zhi; Lihua Xiao; Qinfang Tang; Yungang Wang (Immunologic Research, 2025)

Fuel relocation dynamics in sodium-cooled reactor transients: numerical modeling and experimental benchmarking with CABRI-LTX data - Shaowei Tang; Rui Hou; Siqi Feng; Bin Zhang; Jianqiang Shan (Annals of Nuclear Energy, 2025)

Two undescribed constituents from Salvia castanea Diels and evaluation of their cytotoxic activity - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Tashi Tsering; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2025)

Evaluation of efficacy of intensity measures for fast and reliable seismic fragility analysis of bridge columns - Jian-Cheng Dai; Dong-Sheng Wang; Xiao-Yu Chen; Wei-Jian Tang; Rui Zhang; Ying-Xin Hui (Soil Dynamics and Earthquake Engineering, 2025)

Combined effect of organic matter and antiscalants on gypsum scaling during nanofiltration - Xin He; Yulin Tang; Min Rui; Yuzhu Fan (Journal of Water Process Engineering, 2025)

Resorcinol-formaldehyde resin as co-catalyst in Fenton-like reaction: Synergistic enhancement of Fe3+/Fe2+ cycling via phenolic hydroxyl redox and conjugated-structure mediated electron transfer - Qingnan Meng; Rui Fu; Linzhi Huang; Zhangwen Xie; Yufei Tang; Kang Zhao (Journal of Cleaner Production, 2025)

Morphological, productivity and grain quality characteristics and evolutionary trends of wheat cultivars in different ecological regions of China in the past decades - Rui Nan; Jiawei Zhang; Shuaijie Han; Shaoqi Wu; Gaijuan Tang; Xiaofeng Zhao; Baolin Wu; Xiaohong Chen; Fengli Sun; Yajun Xi; Chao Zhang (Journal of Cereal Science, 2025)

Efficient synthesis of FePO4 from the incinerated sewage sludge ash by modification–selective leaching–precipitation - Zhong-hua Yang; Chuan-ming Du; Pei-yuan Ni; Lei Yuan; Yu-tang Zhang; Rui-yuan Yuan (Chemical Engineering Journal, 2025)

Self-reactive, in-situ generated PUA aerogels: Synergistic low-frequency noise attenuation via metamaterial-like structures and dynamically variation of acoustic impedance - Wanxing Zheng; Yufei Tang; Rui Yang; Zhangwen Xie; Yani Sun; Kang Zhao (Chemical Engineering Journal, 2025)

Thermodynamic and kinetic improvement of MgH2 via the synergism of Al species and Nb-TiO2 - Mengran Li; Jialing Gu; Qinke Tang; Jiabao Bai; Bin Cui; Ruoyu Ma; Yunfeng Zhu; Rui Shi; Yao Zhang; Jiguang Zhang; Yana Liu; Jun Wang; et al. (Chemical Engineering Journal, 2025)

FeCl3-integrated PD/A process for municipal wastewater treatment: Enabling synergistic N and P removal under carbon-limited and short-HRT conditions - Meihui Tang; Shenbin Cao; Rui Du; Yongzhen Peng (Chemical Engineering Journal, 2025)

Integrating categorical and standard triple collocation to improve precipitation fusion over the five largest freshwater lakes in China - Lingjie Li; Guoqiang Tang; Yintang Wang; Rui Gao; Yong Liu; Wenpeng Zhao; Cheng Chen (Journal of Geographical Sciences, 2025)

Stream sediment geochemical anomaly identification and mapping in the Xinbo area, northern China: Using a catchment basin approach and the Apriori algorithm - Ming Liang; Panfeng Liu; Rui Tang; Xiaodong Wang; Chao Li; Feng Zhu (Applied Geochemistry, 2025)

Protective effects of melatonin pretreatment on oxidative damage and immune system impairment in Eriocheir sinensis exposed to ammonia-N stress: insights from the intestine-hepatopancreas axis - Rui Wang; Hui Peng; Dapeng Li; Rong Tang (Aquaculture International, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Modal frequency analysis for Camellia oleifera with sympodial branching growth mode using allometric scaling law - Lewei Tang; Huiyu Zhang; Shiyi Zhang; Rui Pan; Mingliang Wu (Biosystems Engineering, 2025)

Suspended solids dominated tailing effect in UV disinfection of livestock wastewater: Mechanistic deciphering and modelling prediction for epidemic control - Wenjing Bai; Jiaojiao Xu; Zhen-Hu Hu; Rui Tang; Xinmin Zhan (Water Research, 2025)

Hybrid artificial bee colony algorithm with Q-learning for distributed heterogeneous flexible job shop scheduling problem considering machine preventive maintenance - Rui Wu; Enzhuang Luo; Xixing Li; Hongtao Tang; Yibing Li (Swarm and Evolutionary Computation, 2025)

Interaction effects of organic mulch application rates and rainfall intensities on soil and water loss in karst sloping farmlands: Insights from a laboratory simulation experiment - Panpan Wu; Rui Li; Feiyang Cai; Ling Xiong; Zhengyi Tang; Linlv Xiao (Soil and Tillage Research, 2025)

Feasibility of reducing the capacity of plain reservoirs through the joint optimal scheduling of mountain and plain reservoirs - Dingrong Zhai; Aijun Guo; Yimin Wang; Jianxia Chang; Yibin Liang; Zhehao Li; Jingyao Sun; Zhentao Tang; Rui Zheng (Journal of Hydrology, 2025)

The ternary synergy of Fe, N and P enhances the membrane capacitive deionization performance of porous biochar - Houqi Zhou; Ting Xu; Chi Fei; Yilong Fan; Keying Tang; Chunyu Chen; Dianchun Ju; Han Ma; Zuoqiao Zhu; Rui Mao (Journal of Environmental Chemical Engineering, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

A comprehensive review on algae oil: Resources, production, encapsulation and application in food - Wei Tang; Rui Wang; Weilin Liu; Jianfei He; Jianhua Liu (Food Research International, 2025)

Utilizing a three-zone control model of adaptive concentrating photovoltaic facade to enhance visual comfort and energy benefits - Bo Wang; Yifan Xu; Hao Wang; Xinshuo Zhang; Yuan Chen; Rui Tang; Ayin Yan; Mengli Zhang; Ying He (Energy and Buildings, 2025)

Calcium and molybdenum isotopes trace eclogitic crust recycling in formation of unique carbonatite-hosted Mo-REE-U-Nb deposits in orogenic belt - Li Tang; Tao Zeng; Thomas Wagner; Tobias Fusswinkel; Long-Long Chen; Jie Li; Rui Wang (Earth and Planetary Science Letters, 2025)

Laser-free 'smart bomb': self-adaptive nanozyme for the treatment of multidrug-resistant Helicobacter pylori - Chao Sun; Yaya Bai; Rui Shen; Ping Yue; Jia Huang; Ziyun Yang; Jiani Song; Yixun Jin; Yunlong Yang; Yuming Tang; Weiyan Yao (Chemical Engineering Journal, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Evaluating the Role of Postbiotics in the Modulation of Human Oral Microbiota: A Randomized Controlled Clinical Trial - Wen Rui; Saiwei Zhong; Xiaoqian Li; Xuna Tang; Lijun Wang; Jingpeng Yang (Probiotics and Antimicrobial Proteins, 2025)

Response of soil viruses to multiple crop types and environmental changes - Guirong Xie; Hui Zhou; Rui Zhou; Zhimin Tang; Kang Zhou (Plant and Soil, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Apigenin inhibits endothelial-to-mesenchymal transition of coronary artery endothelial cells and myocardial fibrosis by regulating ribosome biogenesis through GTPBP4 modulation - Xiaoyong Hu; Zhaoying Yang; Rui Tang; Zhongying Lv; Ting Zou; Yuanyuan Dou; Hongjian Li (Human Cell, 2025)

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

Dynamic and pseudo-static analysis of shield tunnels in liquefiable ground with nearby aboveground structures - Tong Zhu; Meng-Xiong Tang; Junguang Huang; Jian-Min Zhang; Rui Wang (Soil Dynamics and Earthquake Engineering, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

The chemosensory protein CSP4 increased dinotefuran tolerance in Diaphorina citri adults - Cuiting Liu; Yaoyao Chen; Xinyi Xie; Huiyin Hu; Junxian Wu; Cuiling Ye; Rui Tang; Zhongzhen Wu; Benshui Shu (Pesticide Biochemistry and Physiology, 2025)

Dithiothreitol oxidative potential (OP) of PM2.5 in Beijing: Quantitative contribution of metals to OP and its prediction based on machine learning models - Yusheng Ma; Mengshuang Sheng; Jing Shang; Rui Tang; Jiong Cao; Yuhan Liu; Chenyu Liang; Yu Kuang; Yan Zheng; Zhen Cheng; Rico K.Y. Cheung; Robin L. Modini; et al. (Journal of Hazardous Materials, 2025)

Mechanistic insights into electric field-driven specific ion effects on nanoplastics aggregation in heavy metal co-contaminated aquatic systems - Yan Peng; Rui Li; Ying Tang; Xinmin Liu; Yaowu Zhang; Xinping Gao; Kai Wang; Rui Tian; Hang Li (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Ecological security patterns for coordinating development in frozen soil regions - construction framework by coupling climate change and development objectives - Xiangdong Xu; Xu Yang; Lin Lin; Jingxiao Zhang; Jinggan Shao; Rui Zhi; Tao Feng; Zedong Wang; Yuwen Tang; Junyao Li (Journal of Environmental Management, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Enhancing volatile fatty acid yield via organic loading rate regulation in anaerobic co-digestion: Linking microbial community adaptation and enzyme activities to propionate-dominated metabolic pathways - Xilong Xia; Dongmin Yin; Lili Zhang; Honggang Mao; Lixia Zhu; Rui Tang; Chunyu Li; Dongze Niu; Jianjun Ren (Chemical Engineering Journal, 2025)

“Zombie” cell drug delivery system: A novel strategy for the treatment of cancer and inflammation-related diseases - Zhouru Wang; Wenjing Yang; Danhua Liu; Peihong Lin; Rui Gao; Zhen Ma; Qiao Wang; Zhan Tang; Jie Fang; Wenying Yu (Chemical Engineering Journal, 2025)

Performance-differentiated phase change sandwich composite with gradient thermal conductivity for transient thermal shock protection and multi-source thermal management - Zihan Wang; Xinze Li; Chenbo He; Rui Yang; Mingyang Yang; Guihua Tang; Hu Zhang; Qi Xie; Jingjing Sun; Chencheng Sun; Junning Li (Chemical Engineering Journal, 2025)

Customized microbial inoculants enhance rhizosheath functionality and drive ecosystem restoration in desertified grasslands - Qiqi Han; Weimeng Liu; Yingjie Jiang; Pengyuan Yang; Zixuan Wang; Ziyuan Yan; Zhuo Zhang; Rui Xu; Hui Tang; Guixia Liu (Plant and Soil, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Transcriptomic analysis of inhibitory effects of isothiazolone antimicrobial agents on Aspergillus amstelodami ZR - Junyu Tang; Qizhao Liang; Rui Zhang; Xiaoping Huang (Journal of Applied Genetics, 2025)

Impacts of Landscape Lighting on Karst Ecosystems and Sustainable Lighting Strategies: A Case Study of Zhangguan Cave, Southwestern China - Ran Duan; Yixue Zhao; Rui Tang; Zhigang Wang (Geoheritage, 2025)

MOF-on-MOF nanomaterial (Fe-MOF@UiO-66)-based ratiometric fluorescence/colorimetric dual-mode sensor for ultrasensitive detection of uric acid - Tao Lian; Rui Peng; Zhengyue Xiao; Xiaomin Tang; Peng Xu; Yu Hu; Ping Qiu (Analytica Chimica Acta, 2025)

Neuroprotective effects of Yangming-Kaixin-Yizhi formula in Alzheimer’s disease: dual regulation of PI3K/Akt and p38 MAPK signaling via network pharmacology and experimental approaches - Jing Lei; Jiaming Li; Wei Wu; Rui Xiong; Yao Liu; Yong Tang (Metabolic Brain Disease, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

One-billion-year-old eukaryotic algal fossil Arctacellularia from North China and its implications for the evolution of pre-Cryogenian filamentous multicellularity - Rui Huang; Guangjin Li; Jiayue Wang; Qing Tang; Mingyang Qiu; Qian Chen; Hanzhi Qu; Chengxi Wu; Wenfei Cui; Xianqin Yan; Chuanming Zhou; Xunlai Yuan; et al. (Precambrian Research, 2025)

Dynamic compensation operating rule of parallel reservoirs to enhance sufficient hydrological and reservoir capacity compensation - Zhentao Tang; Xiaoya Deng; Aijun Guo; Yimin Wang; Jianxia Chang; Yibin Liang; Zhehao Li; Dingrong Zhai; Rui Zheng (Journal of Hydrology, 2025)

Hydrodynamic and geomorphological responses of tidal flats to extreme climate events - Renzhi Li; Ya Ping Wang; Rui Yuan; Ning Zhao; Bixuan Tang; Zhixuan Feng; Bruno Castelle (Journal of Hydrology, 2025)

Global impact of fire emission on ambient nitrate (NO3-) and health effects during 2005–2019 - Wenwen Sun; Dongmei Tang; Rui Li (Journal of Hazardous Materials, 2025)

Graphitic nitride decorated with silver oxide nanoparticles as p–n heterostructured catalyst for photoelectrochemical properties and visible-light photodegradation of tetracycline from wastewater - Rui Wang; Mule Vijayalakshmi; Aijia Dai; Kakarla Raghava Reddy; Hui Tang; Bai Cheolho; Jaesool Shim; Ch Venkata Reddy; Tejraj M. Aminabhavi (Journal of Environmental Management, 2025)

Upcycling of cathode materials from spent lithium-ion batteries cathode materials enabled by deep eutectic solvent - Yanshun Liao; Xianglei Meng; Hongwei Wu; Guang Yang; Xinyao Zhang; Rui Tang; Yali Li; Ni Yang; Yibiao Guan; Yuefeng Su; Feng Wu; Qing Huang (Journal of Environmental Chemical Engineering, 2025)

Design optimization and performance analysis of a self-lubricating linear compressor using vapor injection in a dual-temperature zone refrigerator - Shuo Zhang; Mingsheng Tang; Huiming Zou; Rui Kong; Fanchen Kong; Xuan Li (International Journal of Refrigeration, 2025)

l-theanine alleviates ulcerative colitis by repairing the intestinal barrier through regulating the gut microbiota and associated short-chain fatty acids - Aoxiang Liu; Bin Wang; Minming Wang; Rui Tang; Wei Xu; Wenjun Xiao (Food and Chemical Toxicology, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

2D nonlayered titanium oxynitrides intercalated with nitrogen-doped graphene for pseudocapacitive energy storage - Xiuli Li; Rui Huo; Zihuan Tang; Yulei Ren; Hao Song; Paul K. Chu; Kaifu Huo (Chemical Engineering Journal, 2025)

Hydrogen-bonded organic framework-based signal amplification strategy combined with high-specificity sandwich immune response system for dual-mode ultrasensitive detection of gliadin allergen - Jie Han; Youfa Wang; Geoffrey I.N. Waterhouse; Yuxin Wang; Shuang Wu; Rui Wang; Xinxue Zhang; Yajie Tang; Vijaya Raghavan; Jin Wang (Chemical Engineering Journal, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Microbial mediation of soil organic carbon fractions and its feedback to long-term climate change - Xinqi SiMa; Rui Fang; Zhenhua Yu; Yansheng Li; Xiaojing Hu; Haidong Gu; Caixian Tang; Judong Liu; Junjie Liu; Xiaobing Liu; Guanghua Wang; Ashley Franks; et al. (Plant and Soil, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Geochemical Characteristics of Natural Gas in the Upper Permian Reservoir of the Eastern Sichuan Basin, China: Implication of Multiple Sources Mixing - Lu Xu; Rui Liu; Yufeng Tang; Kangbin Zhang; Liang Feng; Xiucheng Tan; Fei Liu; Dingchuan Jiang (Journal of Earth Science, 2025)

Complete genome analysis of a novel mitovirus in the phytopathogenic fungus Penicillium digitatum - Zhimin Tang; Yunhui He; Ya Yang; Xiaoping Zhang; Rui Zhou; Kang Zhou (Archives of Virology, 2025)

Nitrogen and phosphorus dynamics during medium and small flood regulation in the Xiangxi River Bay of the Three Gorges Reservoir: implications for tributary eutrophication - Rui Li; Xianqiang Tang; Danyang Wang; Wenzhong Chen; Xinbo Liu; Wenjun Yang (Environmental Monitoring and Assessment, 2025)

Streptococcus suis AdcA interacts with factor H and inhibits C3b deposition on the bacteria to participate in complement evasion - Siqi Pang; Zhulin Qiao; Jiajia Xu; Hao Tang; Qiuhong Zhang; Weiyao Han; Lu Peng; Jiaojiao Yang; Jiao Zhang; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Addressing challenges and advancing solutions: Enhancing semi-coking wastewater treatment for a sustainable prospect - Tingting Cui; Chunhui Zhang; Bingxu Quan; Liwei Wang; Zhao Zhang; Peidong Su; Yuanhui Tang; Guifeng Zhao; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Management, 2025)

Flash elimination of nano-/microplastics from complex matrices with record efficiency and sustainability - Nuan Liu; Yingxin Ji; Feng Tang; Jianxin Fu; Chuntian Qiu; Rui Wang; Zhiyang Zhang; Lingxin Chen; Guoqing Wang (Chemical Engineering Journal, 2025)

Urban Park Waterfront Microclimate Optimization Using the Orthogonal Experimental Method - Junyou Liu; Haifang Tang; Bohong Zheng; Rui Guo (Theoretical and Applied Climatology, 2025)

The effect of soil microbial functional groups, abiotic and biotic factors on plant functional groups: insights from a tropical rainforest in Southwest China - Yanxuan Chen; Xiaobo Huang; Rong Tang; Rui Zhang; Cong Li; Tongli Wang; Jianrong Su; Shuaifeng Li (Plant and Soil, 2025)

The effects of high intensity exercise on pregnancy outcomes and complications during pregnancy: a meta-analysis of randomized controlled trials - Xinyuan Liu; Xian Guo; Rui Jie; Yuting Tang (European Journal of Applied Physiology, 2025)

Arboviruses: the hidden danger of the tropics - Zhen Yun Siew; Isaac Seow; Xin Rui Lim; Chen Zhe Tang; Fadhilah Moh Djamil; Ghee Khang Ong; Pooi Pooi Leong; Siew Tung Wong; Kenny Voon (Archives of Virology, 2025)

Unlocking the future potential of SWATH-MS: Advancing non-target screening workflow for the qualitative and quantitative analysis of emerging contaminants - Di Xia; Guofang Pan; Yaxiong Liu; He Liu; Bo Zhao; Jiahui Wu; Ting Tang; Guining Lu; Rui Wang (Water Research, 2025)

Enzyme- and nanozyme-based food allergen detections: from natural biocatalysts to rational engineering approaches - Shuang Wu; Jinlong Zhao; Youfa Wang; Vijaya Raghavan; Pengfei Dong; Xinxue Zhang; Jie Han; Rui Wang; Yajie Tang; Geoffrey I.N. Waterhouse; Jin Wang (Trends in Food Science & Technology, 2025)

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

Zircon and apatite constraints on the key factors controlling porphyry Mo mineralization in the Shijiawan deposit: Implication for Mo metallogeny in the Qinling Orogenic Belt - Long-Long Chen; Li Tang; Peng-Rui Lv; Ya-Peng Chen; Tao Zeng (Lithos, 2025)

The combination of microplastics and glyphosate affects the microbiome of soil inhabitant Enchytraeus crypticus - Huihui Yang; Guogang Zheng; Guoyan Qin; Qi Zhang; Ziyao Zhang; Bingfeng Chen; Chaotang Lei; Meng Liu; Rui Cui; Liwei Sun; Shengjie Xia; W.J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2025)

Microbial characteristics accompanied with electricity generation in response to the polyaniline derived covalent organic framework-carbon nanotube composite modified sludge microbial fuel cell - Fengfei Sun; Ziren Sun; Rui Li; Yuewei Yang; Meizhen Tang; Junfeng Chen (Journal of Environmental Chemical Engineering, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Enhanced Cr(VI) adsorption by DOM-coated iron-manganese binary oxides: Process and mechanisms - Zeyu Zhang; Xiaole Ti; Rui Yang; Yuxi Tang; Beidou Xi; Xiaojie Sun; Wenjie Zhang; Ningjie Li (Journal of Environmental Chemical Engineering, 2025)

Study on the flame retarding mechanism of HFC-134a on hydrocarbon refrigerants - Rui Zhai; Xiang Li; Yuan Zhuang; Bin Ye; Xiangnong Liu; Qingqing Li; Lei Tang; Ke Wang (International Journal of Refrigeration, 2025)

Glabridin pharmacodynamic activity toward Gram-positive bacterial infections - Chan Chen; Rui Sun; Tianle Pan; Lian Liu; Wenqiang Tang; Mi Wang; Lifang Zhang; Chenzhong Fei; Yingchun Liu (Food Bioscience, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

Terpene-conjugated curcumin analogs alleviated alcoholic liver injury in rats through mitigation of intestinal barrier abnormalities - Shuaihu Tao; Ruanping Song; Ziyu Wang; Wenjing Xie; Siyuan Xiao; Yangyang Liao; Xinjie Zhang; Qiongdan Hu; Xinxing Tang; Jingyuan Huang; Wan Liao; Hongtao Xiao; et al. (Food Bioscience, 2025)

The novel MAT1-1-2 gene of golden-flower fungus from fuzhuan brick tea is required for normal colony morphology and sexual development, and affects metabolism - Jie Wang; Rui Zhang; Zhenglin Fei; Changfa Yang; Yilong Li; Yaya Yuan; Qilan Hu; Caiyan Tang; Zhonghua Liu; Mingzhi Zhu; Yongyi Ge (Food Bioscience, 2025)

Global landscape fire-sourced ambient benzene and health risks in different future scenarios - Wenwen Sun; Dongmei Tang; Yuanzhi Yao; Rui Li (Environmental Pollution, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Superficial Mycoses: A Mapping Through Bibliometric Research - Jintong Wu; Zijie Tang; Su Wang; Yuxin Qiu; Xinyu Nie; Chengxin Li; Rui Wang (Mycopathologia, 2025)

The performance of an embankment over soft clay under rainfall with tension cracks at soil-pile interface caused by lateral deformation - Xing Wei; Shitao Cheng; Yanjun Li; Rui Chen; Zijian Wang; Fan Tang; Bingkun Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Exposure to glyphosate causes hypoxia in crustaceans by targeting hemocyanin - Rui-Geng Niu; Cheng-Ming Yin; Jia-Yu Si; Meng-Di Tang; Jiang-Feng Lan (Aquaculture, 2025)

The antioxidant protein PntA coordinates with OmpW to resist oxidant stress in Actinobacillus pleuropneumoniae - Weiyao Han; Qiuhong Zhang; Zhen Luo; Hao Tang; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Algicidal activity and mechanism of novel Bacillamide a derivative against red tide algae Skeletonema costatum and Prorocentrum minimum - Huili Li; Xiaoxue Li; Yi Liu; Ronglian Xing; Hongxia Zhang; Wenguang Jia; Lihong Chen; Rui Li; Zhen Yu; Zhihong Tang (Pesticide Biochemistry and Physiology, 2025)

Suppressing sediment nutrient release via electrokinetic drainage of porewater: apparent paradox and underlying mechanisms - Danyang Wang; Xianqiang Tang; Rui Li; Yanping Hu; Junjun Gu; Zhenhua Wang (Journal of Environmental Management, 2025)

Experimental and numerical investigation on the superheated and subcooled ammonia spray characteristics under high injection pressure - Rui Yang; Heng Liu; Bing Li; Qinglong Tang; Mingfa Yao (Fuel, 2025)

Prediction of chlorination degradation rate of emerging contaminants based on machine learning models - Yufan Du; Ting Tang; Dehao Song; Rui Wang; He Liu; Xiaodong Du; Zhi Dang; Guining Lu (Environmental Pollution, 2025)

Radiochromic perovskite La2MgZrO6:Pr for X-ray imaging and ionizing radiation detection - Zi-Hao Chen; Qiang Tang; Jian-An Zeng; Haijiao Xie; Rui Zou; Jing Wang; Bo-Mei Liu (Chemical Engineering Journal, 2025)

Plasmon-assisting surface reaction on gas–vapor-solid photothermal catalytic system for efficient ammonia photosynthesis - Ying Tang; Zhipeng Liu; Juan Jia; Xin Zhong; Hui Zeng; Haijiao Xie; Zebao Rui (Chemical Engineering Journal, 2025)

Stimuli-responsive hydrogels composed of modified cellulose nanocrystal and gelatin with oriented channels for guiding axonal myelination - Shuqin Xu; Xiaoli Tang; Maosen Wang; Zhuqun Wang; Rui Zhan; Jinghua Chen (Carbohydrate Polymers, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Metabolomics provide novel insights into the settlement and metamorphosis of the scyphozoan jellyfish Aurelia coerulea - Shuai Liu; Xiaoyu Tang; Xuerui Liu; Rui Zhang; Xiangrui Guo; Zhen Yu; Ye Zhao; Jiehui Yin; Hao Sun; Yanying Zhang (Journal of Oceanology and Limnology, 2025)

Time-varying compressive mechanical characteristics and empirical model construction of loquat (Eriobotrya japonica Lindl.) based on FEM-RSM - Changsu Xu; Puzan Zhang; Rui Song; Han Tang; Yunwu Li (Computers and Electronics in Agriculture, 2025)

Dissemination mechanisms of unique antibiotic resistance genes from flowback water to soil revealed by combined Illumina and Nanopore sequencing - Rui Yang; Jialin Tang; Junfeng Niu; Bowen Hou; Lilan Zhang (Water Research, 2025)

A comprehensive review on selenium and blood pressure: Recent advances and research perspectives - Pusong Tang; Rui Huang; Xing Zhong; Xin Chen; Yuhua Lei (Journal of Trace Elements in Medicine and Biology, 2025)

Efficient and precise outdoor lifetime prediction method for biodegradable poly (butylene adipate/ terephthalate) under various climate conditions - Yan Ye; Guoshuo Tang; Xiangze Meng; Rui Yang; Baohua Guo; Xuming Xie (Journal of Cleaner Production, 2025)

Direct interspecies transfer modulated chromium(VI) reduction by coculture inorganic SOB-SRB - Rui Qi; Minglu Tang; Yuancai Chen (Journal of Environmental Chemical Engineering, 2025)

Enhanced effects and mechanisms of Tween80 on aniline biodegradation by newly isolated Pseudomonas veronii T1 - Yufeng Fu; Tingdi Zhang; Chuanyu Qin; Chengwu Zhang; Jintao Ru; Rui Tang; Guoxin Huang; Jian Chen (Journal of Environmental Chemical Engineering, 2025)

Synthesis, characterization, and catalytic performance of a novel and efficient iron-based catalyst NaFeS2 for direct coal liquefaction - Rui Zhang; Bowen Tang; Haiyun Liu; Xin Zheng; Zhixian Bao; Lijun Jin; Jianli Wang; Haoquan Hu (Fuel, 2025)

Multifunctional layer-by-layer smart film with betalains and selenium nanoparticles for intelligent meat freshness monitoring and preservation - Hafiz Nabeel Ahmad; Yueyuan Yong; Zhinuo Tang; Rui Li; Noshaba Munawar; Jie Zhu (Food Chemistry, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Iron-carbon amendment enhanced pollutant removal and greenhouse gas reduction in constructed wetlands under PFBA stress - Jiaqing Tao; Xiaoying Zheng; Chao Zhou; Zhilin Zhao; Tianxing Hu; Yi Fan; Yu Tang; Rui Wang; Tao Lin (Chemical Engineering Journal, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Novel nonmetallic acidic molten salt anode with high lithium storage capacity and Proper voltage platform for lithium-ion batteries - Yiting Wang; Jiali Chai; Longzhen Wang; Zhiyuan Chen; Ning Han; Bohejin Tang; Yichuan Rui; Lei Jiang (Chemical Engineering Journal, 2025)

Swertiamarin relieves radiation-induced intestinal injury by limiting DNA damage - Zhe Zhao; Dan He; Jinyu Wang; Yu Xiao; Lixin Gong; Can Tang; Haibo Peng; Xuemei Qiu; Rui Liu; Tao Zhang; Jingyi Li (Molecular and Cellular Biochemistry, 2025)

Fatty acid binding protein 4 knockdown improves fetal development in rats with gestational diabetes mellitus through modulating autophagy mediated by the PTEN/Akt/mTOR signaling pathway - Fanglei Yang; Yifan Mao; Bin Tang; Rui Xu; Feiyun Jiang (Journal of Molecular Histology, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Development of a Mitochondrial Marker for Distinguishing Between Ulva linza and Ulva prolifera - Rui Zhai; Chengnuo Tang; Shuying Wang; Jing Ma; Xinshu Li; Guoqiang Chen; Juntian Xu (Journal of Marine Science and Engineering, 2025)
The green tide is the biggest ecological disaster in Yellow Sea in recent decades, and the species composition has varied from year to year. The ITS (internal transcribed spacer) sequence combined with 5S rDNA spacer are the mainstream molecular markers for green macroalgae. The former can perfectly distinguish the majority of Ulva spp. except the LPP (Ulva linza–procera–prolifera) complex, and the latter is used to distinguish U. linza and U. prolifera exactly based on the former. However, in practice, 5S rDNA spacer is difficult to amplify perfectly with universal primers, and this ultimately affects the experimental process. For this reason, we developed a stable mitochondrial marker for the distinction between U. linza and U. prolifera. The phylogenetic tree based on the mitochondrial rps2 (ribosomal protein S2) gene fragment can distinguish the LPP complex into two clades: U. linza and U. prolifera. Therefore, we concluded that the mitochondrial marker can be a great substitute for 5S primers to distinguish U. linza and U. prolifera.

Effects of karst vegetation-soil-rock composite structure on soil and water flow/leakage processes and driving factors at the micro-plot scale - Rui Li; Jun Jing; Zhengyi Tang; Ling Xiong (Soil and Tillage Research, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

An amino-functionalized magnetic mesoporous silica nano-adsorbent for removing antibiotics from aqueous environments - Sihai Hu; Liuyan Tang; Rui Zhang; Ran Sun; Yuchen Zhang; Zhengcang Song; Yasong Li; Yaoguo Wu; Xujiang Chao; Yuezhou Zhang (Journal of Water Process Engineering, 2025)

Biochar chemical-looping gasification for hydrogen-rich syngas production in solid-solid reaction: O, H and CaO of carbide slag effect NiFe2O4 oxygen carrier - Chenlong Liu; Wenqiang Tang; Xuechen zhang; Siddig Abuelgasim; Chenghua Xu; Rui Liu; Hengyi Xie; Fan Jiang (Journal of Environmental Management, 2025)

Structural evolution of Ni-Ce bimetallic alloy on Al2O3 support in methane dry reforming: Achieving sustainability and high-efficiency reaction through cerium modulation strategy - Xu Ma; Wei-Wei Yang; Jia-Rui Zhang; Xin-Yuan Tang (Fuel, 2025)

Effectively enhanced hydrogen storage properties of Mg90Al10 catalyzed by CeF3 - Mengran Li; Qinke Tang; Lili Yang; Rui Shi; Shihao Chen; Yingzhen Zhu; Yunfeng Zhu; Yao Zhang; Jiguang Zhang; Yana Liu; Jun Wang; Zhixin Ba (Fuel, 2025)

Fish oil emulsions stabilized by enzymatic hydrolysis, glycation, and fibrillation of β-Lg: Stability and EPA/DHA bioaccessibility - Qingchun Zhang; Hao Zhu; Rui Wang; Jianfei He; Christos Ritzoulis; Weilin Liu; Wei Tang; Jianhua Liu (Food Chemistry, 2025)

Spectral analysis of the impact of various polysaccharides on the entrapment of curcumin by whey protein isolate - Yuhan Yan; Rui Tang; Feng Li; Liurong Huang; Yu Chen; Ronghai He (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Unexplored role of nanoconfinement in regulating contaminant oxidation pathways for water decontamination: Confined energy driving low-carbon route - Min Tang; Wu Liu; Zhiyong Wang; Zhaoduan Hu; Jinquan Wan; Rui Peng (Chemical Engineering Journal, 2025)

Screening heat-resistant energetic molecules via deep learning and high-throughput computation - Jian Liu; Jie Tian; Rui Liu; Yuechuan Tang; Chunming Yang; Junhong Zhou; Chaoyang Zhang (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

An eco-friendly catalytic pretreatment using recyclable CuFeO2 catalyst for enhancing the production of bio-based ethanol and jet fuel - Rui Zhang; Can Zhu; Yu Jiang; Yuming Ni; Nan Huang; Wanyun Tang; Minghui Fan; Quanxin Li (Biomass and Bioenergy, 2025)

PKS1 involved in anthocyanin accumulation in red-skinned pear fruit - Lei Guo; Yuting Hao; Ying Tang; Mengjia Wu; Rui Zhai; Chengquan Yang; Lingfei Xu; Zhigang Wang (Plant Cell Reports, 2025)

Effects of aging and temperature on the desorption of polychlorinated biphenyls from microplastics in simulated digestive fluids - Rui Tang; Huiping Wen; Junrong Liang; Xiaoyu Zhang; Xiangfei Sun; Lei Mai (Journal of Oceanology and Limnology, 2025)

Selenium Treatment Alleviates the Inhibition Caused by Nep-L Gene Knockdown in Silkworm (Bombyx mori) - Ting-Ting Hong; Fei Hu; Wen-Jie Ge; Rui Zhang; Juan Du; Kiran Thakur; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

CircTBCK protects against osteoarthritis by regulating extracellular matrix and autophagy - Wei Wang; Yuzhe Sun; Peng Tang; Rui Zhang; Yufeng Jiang; Hongwei Min; Chen Gao (Human Cell, 2025)
Osteoarthritis (OA) is a widespread chronic bone and joint disease for which there is currently no effective preventive or therapeutic treatment. Accumulating evidence indicates that circular RNAs (circRNAs), a class of noncoding RNAs, play critical roles in OA. Therefore, in this study, we aimed to reveal an unexplored circTBCK and elucidate its mechanism of action in the pathological process of OA. The different expression of circTBCK was obtained both in vitro and in vivo. In the in vivo model, mice were induced via destabilization of the medial meniscus (DMM) surgery, while in vitro model, mouse cells like primary chondrocytes of newborn mice and ATDC5 cell line were treated with IL-1β treatment (10 ng/mL for 24 h). The level of circTBCK was examined by quantitative real-time polymerase chain reaction (qRT-PCR). After circTBCK was overexpressed or knocked down, IL-1β treatment was performed, and then, chondrocyte viability was detected via a Cell Counting Kit-8 (CCK-8) assay at 0, 24, 48, or 72 h. To assess type II collagen (Collagen II) expression, immunofluorescence (IF) analysis was used. The levels of mRNAs and proteins related to proliferation, the extracellular matrix (ECM) and autophagy were determined by qRT-PCR and Western blotting. Compared with OA treatment, primary chondrocytes with treatment of both circTBCK overexpression and IL-1βincreased the expression of anabolic factors—Collagen II and SRY-box transcription factor 9 (SOX9), proliferation-related molecules—Ki-67 and proliferating cell nuclear antigen (PCNA), and autophagy-related molecules—Microtubule-associated protein 1 light chain 3 (LC3), B-cell lymphoma 1 (Bcl1), and autophagy-related 5 (Atg5) and decreased Sequestosome 1 (SQSTM1 or P62). In contrast, knockdown of circTBCK aggravated the chondrocyte degeneration induced by IL-1β. Overall, our findings suggest that circTBCK, an unexplored circRNA, could regulate autophagy, proliferation, and the extracellular matrix (ECM) to mitigate the development of OA, suggesting a possible target for OA prevention and therapy.

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Computational Design and Optimization of Multi-Compound Multivesicular Liposomes for Co-Delivery of Traditional Chinese Medicine Compounds - Mengjie Rui; Yali Su; Haidan Tang; Yinfeng Li; Naying Fang; Yingying Ge; Qiuqi Feng; Chunlai Feng (AAPS PharmSciTech, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Long-term warming offsets the beneficial effect of elevated CO2 on mineral associated organic carbon in Mollisols - Xinqi SiMa; Yansheng Li; Zhenhua Yu; Haidong Gu; Junjie Liu; Judong Liu; Rui Fang; Xiaojing Hu; Xiaobing Liu; Guanghua Wang; Caixian Tang; Ashley Franks; et al. (Science of The Total Environment, 2025)

Niche and interspecific association of dominant zooplankton species near the Taishan coastal area in the South China Sea - Rui He; Bingqing Xiao; Ren Hu; Hongliang Tang; Jingxin Wei; Peng Wu (Marine Environmental Research, 2025)

Binary response of runoff generation and erosion processes to karst vegetation-soil-rock structure and its hydrodynamic mechanisms - Jun Jing; Rui Li; Ling Xiong; Zhengyi Tang (Journal of Hydrology, 2025)

Relative contributions of climate and grazing to forage supply in the Yellow River source area - Suizi Wang; Jiangwen Fan; Miaomiao Wang; Rui Tang; Nan-Ji Jiang (Journal of Environmental Management, 2025)

A TiO2/ZnO (nanoparticle/quantum dot) heterojunction with strong interfacial coupling for ultrasensitive SERS sensing of antibiotic residues in environment (water and soil) and their efficient degradation - Yimin Tang; Xuewei Zhang; Rui Wang; Huizhu Zhang; Libin Yang; Xin Jiang; Bing Zhao (Journal of Environmental Chemical Engineering, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

Light limitation during a compound drought and heat event inhibited algal blooms in a nutrient-rich shallow lake - Tianhao Wu; Rui Gao; Xiaoxian Tang; Zhaosheng Chu; Bibi Ye; Zhen Yuan (Harmful Algae, 2025)

A novel g-C3N4/TiO2 heterojunction for ultrasensitive detection of bisphenol A residues - Xin Jiang; Han Jiang; Yimin Tang; Rui Wang; Wenxue Wang; Libin Yang; Bing Zhao (Food Chemistry, 2025)

Investigating building stock energy and occupancy modelling approaches for district-level heating and cooling energy demands estimation in a university campus - Salam Al-Saegh; Vasiliki Kourgiozou; Ivan Korolija; Rui Tang; Farhang Tahmasebi; Dejan Mumovic (Energy and Buildings, 2025)

Multifunctional composites made from waste polyester cotton fabric and waste rigid polyurethane foam for potential building wall material applications - Feng Liang; Qinxian Chen; Zhen Shi; Rui Dan; Huan Liang; Xu Feng; Chuanyun Tang; Xijing Yu; Xianqin Shang; Denglu Zhang; Yuanyuan Hu (Energy and Buildings, 2025)

Up-concentration of organic matter from municipal wastewater by coagulation coupled with active coke adsorption to improve carbon capture and anaerobic methanogenesis efficiency - Ying An; Yanhua Xu; Chen Tang; Xingzhi Du; Zihang Ma; Rui Tang; Bin Zhou; Zhan Qiu; Zhen Zhou (Chemical Engineering Journal, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Scale effects on suspended sediment and their response to extreme precipitation in karst basins - Jiang Yuan; Rui Li; Jie An; Shitian Tang; Qianying Mei; Jun Jing (Science of The Total Environment, 2025)

Evidence of sewage discharge on the coalescence mechanism of aquatic microbial communities during high amplitude hydrological periods - Xin Kou; Shier Huang; Rui Bian; Qingwen Tang; Hui Wang; Song Liu; Li Wang; Weixiao Qi; Xiaofeng Cao; Huachun Lan; Huijuan Liu; Jiuhui Qu (Science of The Total Environment, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

An in situ reactive zone approach using calcium peroxide for the remediation of benzene and chlorobenzene in groundwater: A field study - Rui Li; Changlong Wei; Zhiwen Tang; Mukhtiar Ali; Zhipan Ma; Bing Li; Ailiang Gu; Xin Song (Journal of Environmental Management, 2025)

High-fidelity model development of CO2 booster refrigeration systems in supermarkets using field measurements - Wenzhuo Li; Ivan Korolija; Rui Tang; Dejan Mumovic (International Journal of Refrigeration, 2025)

Inactivation and sublethal injury of Salmonella Typhimurium on beef and in aqueous solution treated with lactic acid - Yunshuang Man; Mengjiao Zhang; Hui Tang; Rui Wen; Rongrong Yang; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Research International, 2025)

An investigation of the mechanism of emulsion stabilization in octenyl succinic anhydride-modified tamarind seed polysaccharide - Yuxing Kou; Rui Guo; Xianbao Sun; Xuan Ma; Yinan Chen; Lihua Song; Zibo Song; Chunmei Yuan; Siyan Huang; Jian Tang; Yan Wu (Food Hydrocolloids, 2025)

A prediction model of the optimal defrosting initiating time for the air source heat pumps with different configurations and operations - Shiquan Wang; Wenzhe Wei; Jianfei Luo; Wei Wang; Yuying Sun; Zhaoyang Li; Chengyang Huang; Rui Tang; Shiming Deng (Energy and Buildings, 2025)

In-situ experiments of dynamic microscopic reaction for CO2-brine-carbonate system - Yulong Zhao; Yongchao Wang; Shaomu Wen; Liehui Zhang; Zhenglin Cao; Zihan Zhao; Wei Xiong; Cheng Cao; Rui Tang; Yunting Fan; Zehao Xie; Ruihan Zhang; et al. (Chemical Engineering Journal, 2025)

Production of α-amylase from gluconate and carbon dioxide by protein synthesis and secretion optimization in Cupriavidus necator H16 - Ruohao Tang; Rui Xu; Xuemin Gao; Cunxi Dai; Xiaochun Qin; Jianming Yang (Bioresource Technology, 2025)

Towards resilient communities: Evaluating the nonlinear impact of the built environment on COVID-19 transmission risk in residential areas - Weiqi Guo; Jingwei Wang; Xiaoyu Liu; Zhenyu Pan; Rui Zhuang; Chunying Li; Haida Tang (Building and Environment, 2025)

Effect of supply water temperature on frosting performance of air source heat pump and indoor thermal environment in space heating - Wei Wang; Haoran Di; Rui Tang; Wenzhe Wei; Yuying Sun; Chuanmin Dai (Building and Environment, 2025)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: Improving Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Dian-Long Wang; Rui Wang; Bin Shi (Rock Mechanics and Rock Engineering, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Dual-CRISPR/Cas12a-assisted RT-RAA visualization system for rapid on-site detection of nervous necrosis virus (NNV) - Jie Gao; Siyou Huang; Jing Jiang; Qijin Miao; Rui Zheng; Yiling Kang; Wanting Tang; Hongliang Zuo; Jianguo He; Junfeng Xie (Analytica Chimica Acta, 2025)

Tracing contaminants of emerging concern and their transformations in the whole treatment process of a municipal wastewater treatment plant using nontarget screening and molecular networking strategies - Zhenguo Chen; Di Xia; Huangrui Liu; Rui Wang; Mingzhi Huang; Ting Tang; Guining Lu (Water Research, 2024)

Are air travelers willing to pay for mandatory carbon emission policies? Evidence from China - Bao-Jun Tang; Rui Yan; Jun-Yu Chen; Chang-Jing Ji (Sustainable Production and Consumption, 2024)

Unraveling drivers of per- and polyfluoroalkyl substances (PFASs) occurrence and removal in leachate: Insights from disposal methods, geo-climate, and biodegradation - Leilei Lu; Xiaofei Yan; Guodong Kang; Dan Qi; Na Tang; Rui Zhu; Changwei Lv; Yuanqing Bu; Houhu Zhang; Shenghu Zhang (Science of The Total Environment, 2024)

Neolithization of Dawenkou culture in the lower Yellow River involved the demic diffusion from the Central Plain - Fen Wang; Rui Wang; Hao Ma; Wen Zeng; Yongsheng Zhao; Hao Wu; Zhongming Tang; Haifeng He; Hui Fang; Chuan-Chao Wang (Science Bulletin, 2024)

Nonfragile memory-based sampled-data control for Unmanned Surface Vehicles with time-varying coupling delay - Xinyuan Long; Hua Chen; Jinhai Zheng; Jisheng Zhang; Mi-An Xue; Yao Tang; Rui Xu; Yang Zhao (Ocean Engineering, 2024)

Application of metallic minerals in wastewater treatment: A review - Xuchao Sun; Yinghao Tang; Rui Li; Kaizhen Wu; Fang Shen; Shiping Zhang; Lutao Xue; Yu Jiang; Xiaoyong Wu (Journal of Water Process Engineering, 2024)

Controllable fabrication of high-quantum-yield bimetallic gold/silver nanoclusters as multivariate sensing probe for Hg2+, H2O2, and glutathione based on AIE and peroxidase mimicking activity - Wei Tang; Siqi Chen; Ying Song; Miaomiao Tian; Rui Yan; Baodong Mao; Fang Chai (Journal of Hazardous Materials, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

In situ generation of cuprous oxide in metal-organic framework for significantly enhanced room-temperature ammonia sensing: Synergy enabling excellent sensitivity and selectivity - Honglei Zhang; Zhuang Yan; Yue Ying; Fengbin Zheng; Rui Song; Zhiyong Tang; Yaling Liu (Journal of Environmental Chemical Engineering, 2024)

Carvacrol acts on the larval midgut of Spodoptera frugiperda by destroying the tissue structure and altering the bacterial community - Jingjing Zhang; Cuiting Liu; Xinyi Xie; Xuanyue Yu; Yuting Huang; Rui Tang; Jian Zeng; Benshui Shu (Journal of Asia-Pacific Entomology, 2024)

Carboxymethyl chitosan coating infused with linalool-loaded molten globular β-Lactoglobulin nanoparticles for extended preservation of fresh-cut apples - Xiaotong Wang; Junxiang Zhu; Tianjin Tang; Lei Yang; Xingyu Chen; Si Meng; Rui Zheng; Hao Wu (Food Chemistry, 2024)

Bacterial community and antibiotic resistance genes assembly processes were shaped by different mechanisms in the deep-sea basins of the Western Pacific Ocean - Qianyi Jin; Jialin Tang; Lilan Zhang; Rui Yang; Bowen Hou; Qijun Gong; Dong Sun (Environmental Pollution, 2024)

An efficient bio-stabilization technology with bio‑carbonation of reactive magnesia for soil improvement in cold regions - Rui Wang; Chao-Sheng Tang; Xiao-Hua Pan; Dian-Long Wang; Zhi-Hao Dong; Xiancai Lu (Engineering Geology, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

High-performance COFs composite nanofiltration membrane fabricated by organobase catalyst - Lin Yu; Jia-Yue Dai; Zhen-Liang Xu; Yin-Xin Fang; Rui Jia; Yong-Jian Tang (Desalination, 2024)

Optimization of Preparation Technology for PET-Based Carbon Dots by Response Surface Method and Its Application - Chaohui Ma; Gaoling Jin; Puzhen He; Chuanjiang Tang; Linhan Bing; Botong Liu; Hanjiang Huang; Yu Fan; Rui Wang; Jianfei Wei (Journal of Fluorescence, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Small watersheds are the best control and management unit for improving soil conservation services in karst areas - Zhengyi Tang; Rui Li (Science of The Total Environment, 2024)

Soil microbiome regulates community functions when using biochar-based fertilizers made from biodegradable wastes - Jiajia Xing; Caixian Tang; Rui Xu; Junhui Chen; Liyuan Peng; Hua Qin (European Journal of Agronomy, 2024)

Manipulating surface reconstruction and lattice oxygen mechanism of nickel (oxy)hydroxide by defect engineering for industrial electrocatalytic water oxidation - Xiangling Wang; Zhimin Li; Yu Tang; Zhengfu Zhang; Chengping Li; Rui Bao; Guo Chen; Jinsong Wang (Chemical Engineering Journal, 2024)

Structurally programmed bioderived polyimide for foldable humidity sensors with ultrafast response and recovery times - Caihong Gong; Huilong Liu; Shaoji Wu; Zhao Liu; Sutong Zheng; Yanhuang Tang; Zhiming Qiu; Rui Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Molecular insights and functional analysis of isocitrate dehydrogenase in two gram-negative pathogenic bacteria - Wei Xiong; Rui Su; Xueyang Han; Mengxiao Zhu; Hongyiru Tang; Shiping Huang; Peng Wang; Guoping Zhu (World Journal of Microbiology and Biotechnology, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Experimental Study on the Classification and Evolution of the Tip Cavitation Morphology in Axial Waterjet Pumps with Two Different Blade Numbers - Xi Shen; Haoran Wu; Gang Yang; Rui Tang; Chenxin Chang; Bin Xu; Suben Lin; Desheng Zhang (Journal of Marine Science and Engineering, 2024)
Tip leakage flow and induced unstable cavitation can significantly damage the performance of axial waterjet pumps. This study investigated the impact of blade numbers on cavitating conditions in an axial waterjet pump by conducting tests of performance characteristics and high-speed photography experiments on three-blade and four-blade impellers. The results showed that the critical cavitation number σc of the three-blade impeller was larger, while the four-blade impeller flow pattern deteriorated more rapidly after σc. Various cavitation structures in the tip region were observed under different conditions, including clearance cavitation, shear layer cavitation, tip leakage vortex cavitation, and suction-side-perpendicular cavitating vortices (SSPCVs). Tip cavitation maps of the test impellers were drawn based on the flow rate coefficient and cavitation number variation. The three-blade impeller exhibited a wider range of severe cavitation, particularly with an increased occurrence of SSPCVs. With the cavitation number and flow rate coefficient decreased, the SSPCV generated from triangular cavitation cloud shedding presented an increased trend in scale and quantity. Conversely, in the case of the four-blade impeller, SSPCVs were often disrupted by the adjacent blade during migration and interfered with the tip cavitation in the neighboring flow passage.

Long-term escape behavior and release mechanism of organic emissions from asphalt materials - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Rui Li; Gengren Hao (Science of The Total Environment, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Functionally-designed metal salt and ball milling co-modified sludge biochar for adsorptive removal of trace level sulfamethoxazole: Behavior, characterization, mechanism and DFT study - Rui Mu; Shufang Qian; Yongfei Ma; Zhikang Deng; Jiayi Tang; Zulin Zhang (Journal of Environmental Chemical Engineering, 2024)

Shrinking and upward shifting of siberian Jerboa's suitable habitat in China under climate change impacts - Ruixun Gan; Limin Hua; Tao Yu; Zhuangsheng Tang; Xincheng Cai; Rui Dong; Longming Dong; Daerhan Bao; Bin Chu; Yuanyuan Hao (Journal of Arid Environments, 2024)

Reaction mechanism for NH3-SCR of NOx over CrMn1.5O4 catalyst - Zheng-nan Yuan; Rui-tang Guo; Xiao-jing Liu; Yi-feng Xu; Lu Liu; Wei-guo Pan (Fuel, 2024)

Fabrication and characterization of oxidized starch-xanthan gum composite nanoparticles with efficient emulsifying properties - Zheng Cai; Wei Zhou; Rui Zhang; Yuqi Tang; Kun Hu; Fangfang Wu; Chao Huang; Yong Hu; Tao Yang; Yun Chen (Food Chemistry, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Spatial distribution and enrichment characteristics of selenium in paddy soil and rice around the Dongting Lake - Rui Liu; Weijun Zhou; De Yu; Guiduo Shang; Yuzhou Zhou; Zhangqian Xu; Dou Tang; Haojie Cui; Chaolin Liao (Environmental Pollution, 2024)

Use of modified poly-epoxysuccinic acid as an efficient scale inhibitor to control CaSO4 scaling in NF processes: Performance and mechanisms - Xinyuan Yi; Shumin Yang; Xin He; Zhiwei Wang; Min Rui; Yulin Tang (Desalination, 2024)

Multifunctional molecular bridge enabled interface passivation and strain release for stable and efficient all-inorganic perovskite solar cells - Zhiwei Ma; Benlin He; Rui Tui; Xinyi Zhang; Qihang Cheng; Changqing Liu; Haiyan Chen; Jialong Duan; Qunwei Tang (Chemical Engineering Journal, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Deciphering pathogens inactivation mechanism during anaerobic co-digestion of food waste and waste activated sludge: The role of pH - Rui Tang; Qi Zhang; Yong-Dong Chen; Wen-Jing Bai; Jiao-Jiao Xu; Yilin Pang; Ying An; Zhen Zhou; Zhen-Hu Hu (Chemical Engineering Journal, 2024)

Anion vacancy engineering in carbon coating VS4 microspheres assembled by nanorod arrays for high-performance rechargeable Mg-Li hybrid batteries - Xu Zhang; Qinke Tang; Yana Liu; Yunfeng Zhu; Jiguang Zhang; Jun Wang; Rui Shi (Chemical Engineering Journal, 2024)

Dynamic covalent adhesives and their applications: Current progress and future perspectives - Zhipeng Liu; Ying Tang; Yuxuan Chen; Zhiyan Lu; Zebao Rui (Chemical Engineering Journal, 2024)

Cyclodextrin-based host-guest hierarchical fire retardants: Synthesis and novel strategy to endow polylactic acid fire retardancy and UV resistance - Jing Zhang; Xiuqin Zhang; Rui Wang; Wenqing Wang; Hui Zhao; Shuo Yang; Zhenfeng Dong; De-Yi Wang; Ye-Tang Pan (Carbohydrate Polymers, 2024)

Sesquiterpenes from Tinospora sinensis and their chemotaxonomic significance - Rui Ao; Ming-Hui Li; Zi-Nan Xiao; Xue-Lian Tang; Jun-Sheng Zhang; Hua Zhang (Biochemical Systematics and Ecology, 2024)

Advances in the Differentiation of hiPSCs into Cerebellar Neuronal Cells - Yingxin Wang; Wenzhu Liu; Yichang Jiao; Yitong Yang; Didi Shan; Xinbo Ji; Rui Zhang; Zexin Zhan; Yao Tang; Dandan Guo; Chuanzhu Yan; Fuchen Liu (Stem Cell Reviews and Reports, 2024)

Potential Applications of Blautia wexlerae in the Regulation of Host Metabolism - Wen Rui; Xiaoqian Li; Lijun Wang; Xuna Tang; Jingpeng Yang (Probiotics and Antimicrobial Proteins, 2024)

New insights into the mechanisms and therapeutic strategies of chondrocyte autophagy in osteoarthritis - Lujia Tang; Jiatong Ding; Kangping Yang; Zhen Zong; Rui Wu; Hui Li (Journal of Molecular Medicine, 2024)

WNT2B high‑expressed fibroblasts induce the fibrosis of IBD by promoting NK cells secreting IL-33 - Yanling Cheng; Shuzhe Xiao; Lin Lan; Danqiong Liu; Rui Tang; Jianbiao Gu; Li Ma; Zhihua He; Xirong Chen; Lanlan Geng; Peiyu Chen; Huiwen Li; et al. (Journal of Molecular Medicine, 2024)

Bentonite/Sesbania Gum Hydrogel for Effective Removal of Cationic Dyes: Network Structure Construction and the Role of Multiple Hydroxyl and Carboxyl Adsorption Sites - Luying Jiang; Sishan Yu; Jingwei Zhang; Zisong Xu; Rui Tang; Yinlong Wang; Ke Liang; Chen Zhai; Zhangfa Tong; Hanbing Zhang (International Journal of Environmental Research, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Enhancing collaboration of anammox with heterotrophic microbes mediated selectively by iron of different valences: Activities balance, metabolic mechanism, and functional genes regulation - Meihui Tang; Rui Du; Xiaoyu Han; Yongzhen Peng (Chemosphere, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

RpedOBP1 plays key roles in aggregation pheromones reception of the Riptortus pedestris - Yongzhi Zhong; Rui Tang; Lulu Lin; Wei Zhao; Shuang Wei; Feng Zhang; Md Kafil Uddin; Minghui Xie; Haoliang Chen (Pesticide Biochemistry and Physiology, 2024)

Antiviral C-geranylated flavonoids from Artocarpus communis - Rui-Li Huang; Wei Tang; Chaoqun Wang; Cong Yan; Yun Hu; Hai-Xia Yang; Hai-Yang Xiang; Xiao-Jun Huang; Li-Jun Hu; Wen-Cai Ye; Jian-Guo Song; Ying Wang (Phytochemistry, 2024)

Construction of an S-scheme electron transfer channel in Cu0/CuFe2O4 magnetic plate column reactor for the LEV degradation: New strategy of visible Photo-Fenton system application - Rui Wang; Aiwen Wang; Yunhao Pan; Jiaxin Ni; Yingjie Deng; Zhe Tao; Xiongying Liang; Jingrui Tang; Xunming Tian; Tiancheng Zha; Dongmei Liu; Jun Ma (Journal of Hazardous Materials, 2024)

How does the issuance of green bonds impact stock price crash risk: An analysis utilizing the NCSKEW and DUVOL - Pengfei Ge; Wen Yue; Chuxiong Tang; Rui Zhu (Journal of Environmental Management, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

Metal–organic frameworks and their composites: Design, synthesis, properties, and energy storage applications - Rui Wang; Jinlong Gao; Mule Vijayalakshmi; Hui Tang; Kai Chen; Ch. Venkata Reddy; Raghava Reddy Kakarla; P.M. Anjana; Mashallah Rezakazemi; Bai Cheolho; Jaesool Shim; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2024)

Alginate/multi-wall carbon nanotube fiber-based moist-electric generator with enhanced performance by constructing radial heterogenous structure - Rui Zhang; Xinye Li; Wenshuo Du; Taofu Zhao; Ping Tang; Xiaozhu Ju; Hai Wang; Yuezhen Bin (Chemical Engineering Journal, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

External electron donor and transporter of iron triggers the paths to enhancing collaboration of anammox and denitrification in granular sludge: Bacterial resilience and synergetic promotion mechanism - Meihui Tang; Rui Du; Xiangchen Li; Jacek Makinia; Shenbin Cao; Yongzhen Peng (Chemical Engineering Journal, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Mangrove monitoring and extraction based on multi-source remote sensing data: a deep learning method based on SAR and optical image fusion - Yiheng Xie; Xiaoping Rui; Yarong Zou; Heng Tang; Ninglei Ouyang (Acta Oceanologica Sinica, 2024)

Characterization and source apportionment of pharmaceuticals in surface water of the Yangtze Estuary and adjacent sea - Chunzhao Chen; Jian Tang; Fei Li; Rui Xue; Yihua Xiao; Ling Chen; Gang Yu (Environmental Science and Pollution Research, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Compositional analysis and quantitative evaluation of organic emissions from asphalt materials: Improvements and refinements - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Huailei Cheng; Jia Liu; Rui Li (Journal of Cleaner Production, 2024)

Two cytokine receptor family B (CRFB) members in orange-spotted grouper Epinephelus coioides, EcCRFB3 and EcCRFB4, negatively regulate interferon immune responses to assist nervous necrosis virus replication - Siyou Huang; Yiling Kang; Rui Zheng; Linwei Yang; Jie Gao; Wanting Tang; Jing Jiang; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Silica's silent threat: Contributing to skin fibrosis in systemic sclerosis by targeting the HDAC4/Smad2/3 pathway - Bingsi Tang; Yaqian Shi; Zhuotong Zeng; Xinglan He; Jiangfan Yu; Ke Chai; Jiani Liu; Licong Liu; Yi Zhan; Xiangning Qiu; Rui Tang; Yangfan Xiao; et al. (Environmental Pollution, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Promotion and monitor wound healing by anthocyanin enhanced light curing ε-poly-l-lysine hydrogel encapsulated Cu-MOF - Xiawei Zhao; Rui Liu; Tiantian Tang; Zihao Liu; Xiaozhi Liu; Kai Yu; Ye Zhang; Hao Wang (Chemical Engineering Journal, 2024)

Removal of artificial sweeteners in wastewater treatment plants and their degradation during sewage sludge composting with micro- and nano-sized kaolin - Jishao Jiang; Rui Hou; Huilin Cui; Zhuyu Tang; Yousif Abdelrahman Yousif Abdellah; Caspar C.C. Chater; Ke Cheng; Fuqiang Yu; Dong Liu (Bioresource Technology, 2024)

Release Experiment Reveals Eutrophication Risk of using Polders to Impound Flood Water in the Yangtze River - Danyang Wang; Xianqiang Tang; Rui Li; Huijun Ding; Yanhong Li (Water, Air, & Soil Pollution, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Multi-objective fuzzy green scheduling optimization method of special vehicle body-in-white prototype shop considering equipment preventive maintenance - Xixing Li; Chenchen Wu; Rui Wu; Hongtao Tang (Journal of Cleaner Production, 2024)

Hydrogen-donating behavior and hydrogen-shuttling mechanism of liquefaction solvents under Fe- and Ni-based catalysts - Haiyun Liu; Rui Zhang; Xin Zheng; Jing Xie; Bowen Tang; Zhi Li; Erguang Guo; Haoquan Hu; Lijun Jin (Fuel, 2024)

Effect of annealing treatment on physicochemical properties, rheology and in vitro digestion of potato starch-galactomannan complexes - Rui Zhang; Rui Huang; Zheng Cai; Yuqi Tang; Yong Hu; Chao Huang; Nanjing Zhong; Yun Chen (Food Hydrocolloids, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Meticulously designed red emission carbon dots as efficient and stable luminescent species for rapid latent fingerprint recognition and light emitting diodes - Jianbo Cao; Rui Chen; Linfan Wang; Haoming Xing; Houwen Hu; Xiangdong Yang; Chenjie Gu; Siyuan Tang; Da Chen (Chemical Engineering Journal, 2024)

Deciphering the stability mechanism of Pt-Ni/Al2O3 catalysts in syngas production via DRM - Rui Zhao; Kun Cao; Rongli Ye; Yuanting Tang; Chun Du; Fudong Liu; Yunkun Zhao; Rong Chen; Bin Shan (Chemical Engineering Journal, 2024)

Roundup® induces premature senescence of mouse granulosa cells via mitochondrial ROS-triggered NLRP3 inflammasome activation - Heliang Ni; Xiangdong Hu; Nannan Yang; Xiaoyang Liu; Wenyang Cai; Rui Zhong; Tiancheng Wang; Mingxi Yu; Shuang Tang (Toxicological Research, 2024)

An application of hierarchical MgAl hydrotalcite in the highly efficient treatment of oilfield macromolecular contaminants - Chenye Yang; Qi Liu; Tao Li; Rui Zhou; Chengtun Qu; Ying Tang (Environmental Science and Pollution Research, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Bioactivities of essential oil extracted from Elsholtzia densa Benth. And its main components against Tribolium castaneum eggs and pupae - Xiaohan Zhang; Rui Feng; Yufei Tang; Weibao Kong; Ji Zhang; Junyu Liang (Pesticide Biochemistry and Physiology, 2024)

Various functions of detoxification enzymes against insecticides in Nilaparvata lugens selected by toxicity assays and RNAi methods - Jun Yang; Li-Yuan Sun; Ruiyan Ma; Rui Tang; Juan-Ying Zhao; Qing-Nian Cai (Pesticide Biochemistry and Physiology, 2024)

A biotechnological approach for suspended solids removal in biogas slurry via microbially induced calcite precipitation (MICP) - Rui Wang; Chao-Sheng Tang; Xiaohua Pan; Zhengtao Shen; Yujia Liu; Xiancai Lu (Journal of Cleaner Production, 2024)

Effect of nano zero-valent iron on the anaerobic digestion of food waste: Performance and mechanism - Ruonan Wang; Naif Abdullah Al-Dhabi; Yufeng Jiang; Xiaofeng Dai; Rui Li; Wangwang Tang; Rongbo Guo; Shanfei Fu (Fuel, 2024)

Synergistic multifactor influence and management of commercial vanadium-based catalyst lifetimes - Yi-feng Xu; Xiao-jing Liu; Rui-tang Guo; Tong Wu; Hong-lei Ding; Dong Ye; Wei-guo Pan (Fuel, 2024)

High-pressure microfluidization enhanced the stability of sodium caseinate-EGCG complex-stabilized fish oil emulsion - Wei Tang; Rui Wang; Minghui Li; Qingchun Zhang; Jianfei He; Dan Liu; Yuqi Feng; Weilin Liu; Jianhua Liu (Food Chemistry, 2024)

Exploiting excavation-induced displacement for slope heterogeneity characterization and stability analysis - Jing-Sen Cai; Tian-Chyi Jim Yeh; E-Chuan Yan; Rui-Xuan Tang (Computers and Geotechnics, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Curcumol: a review of its pharmacology, pharmacokinetics, drug delivery systems, structure–activity relationships, and potential applications - Sicheng Zhai; Rui Wang; Jingyuan Wang; Xiangdong Xu; Le Niu; Min Guo; Yongling Zhang; Yajun Shi; Xuexue Tang (Inflammopharmacology, 2024)

Evaluating the fracture resistance and drainage difficulty of coal reservoirs using log data - Zhi-di Liu; Bin-rui Yang; Xiao-yan Tang; Wei Wang; Liang Ji; Zhi-hao Jiang (Applied Geophysics, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Effects of cations on biofilms in gravity-driven membrane system: Filtration performance and mechanism investigation - Rui Chen; Daliang Xu; Jing Zhao; Xiaobin Tang; Haiyang Yang; Heng Liang (Water Research, 2024)

Stable continuous flow CANDAN process transitioning from anammox UASB reactor by facilitating indigenous nitrite-producing denitrification community - Rui Du; Meihui Tang; Qingtao Liu; Shenbin Cao; Yongzhen Peng (Science of The Total Environment, 2024)

Non-targeted screening and photolysis transformation of tire-related compounds in roadway runoff - Jinfan Chen; Ting Tang; Yanxi Li; Rui Wang; Xingcai Chen; Dehao Song; Xiaodong Du; Xueqin Tao; Jiangmin Zhou; Zhi Dang; Guining Lu (Science of The Total Environment, 2024)

Regional scale terrace mapping in fragmented mountainous areas using multi-source remote sensing data and sample purification strategy - Zicheng Liu; GuoKun Chen; Bohui Tang; Qingke Wen; Rui Tan; Yan Huang (Science of The Total Environment, 2024)

Non-fragile control associated with exponential stability for unmanned surface vessels with the rudder failure and dynamic event-trigger - Xinyuan Long; Hua Chen; Jinhai Zheng; Mi-An Xue; Rui Xu; Yao Tang; Yang Zhao (Ocean Engineering, 2024)

Association between air pollution and male sexual function: A nationwide observational study in China - Ziyuan Shen; Feng Zhang; Zihan Guo; Rui Qu; Yiqiu Wei; Jingxuan Wang; Weiqian Zhang; Xing Xing; Yan Zhang; Jue Liu; Dongdong Tang (Journal of Hazardous Materials, 2024)

A novel MnCoOx@TiO2 double–wall nanocages derived from Prussian blue analogue for NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Fuel, 2024)

Phosphorus recovery from phosphate tailings through a two-stage leaching-precipitation process: Toward the harmless and reduction treatment of P-bearing wastes - Yao-hui Yu; Chuan-ming Du; Yu-tang Zhang; Rui-yuan Yuan (Environmental Research, 2024)

Mechanistic insights into the stepwise lithium-mediated electrochemical nitrogen reduction for enhanced ammonia synthesis - Peng Yang; Feng Gong; Chaozhen Liu; Shenglin Liu; Enkang Fu; Yuhang Jing; Junjie Feng; Wenbo Tang; Rui Xiao (Chemical Engineering Journal, 2024)

In-situ synthesis of MEMS compatible Al/Cu2HIO6/PVDF Metastable composites film with high combustion performance - De-Yun Tang; Chuanhao Xu; Heng Ding; Haifeng Yang; Xiaodong Li; Weimiao Wang; Rui Li; Zhiqiang Qiao; Guangcheng Yang (Chemical Engineering Journal, 2024)

Fabrication of Al@AIH@PVDF metastable composite film with enhanced laser ignition ability and combustion performance - De-Yun Tang; Heng Ding; Weimiao Wang; Xiaodong Li; Haifeng Yang; Rui Li; Zhiqiang Qiao; Guangcheng Yang (Chemical Engineering Journal, 2024)

Pseudomonas aeruginosa regulator PvrA binds simultaneously to multiple pseudo-palindromic sites for efficient transcription activation - Yibo Zhu; Bingnan Luo; Xingyu Mou; Yingjie Song; Yonghong Zhou; Yongbo Luo; Bo Sun; Youfu Luo; Hong Tang; Zhaoming Su; Rui Bao (Science China Life Sciences, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Origin, Structural Characteristics, and Health Effects of Atmospheric Soot Particles: A Review - Rui Tang; Jing Shang; Xinghua Qiu; Jicheng Gong; Tao Xue; Tong Zhu (Current Pollution Reports, 2024)

A mechanistic study of Anwei decoction intervention in a rat model of gastric intestinal metaplasia through the endoplasmic reticulum stress – Autophagy pathway - De-Kun Wu; Rui-Cheng Huang; You-Ming Tang; Xian Jiang (Tissue and Cell, 2024)

Growth differentiation factor 9 regulates the expression of estrogen receptors via Smad2/3 signaling in goat cumulus cells - Yaju Tang; Sihai Lu; Juncai Wei; Rui Xu; Hui Zhang; Qiang Wei; Bin Han; Yan Gao; Xiaoe Zhao; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2024)

Isolation of Prunus persica kernel protein and its physicochemical properties and aggregating performance modulated by heating and ultrasonication - Chunxiao Tao; Taiwei Ye; Dongyun Tang; Rui Tian; Yan Xie (Sustainable Chemistry and Pharmacy, 2024)

New mechanistic insight into catalytic decomposition of dioxins over MnOx-CeO2/TiO2 catalysts: A combined experimental and density functional theory study - Qiulin Wang; Zhihao Wu; Rui Wang; Minghui Tang; Shengyong Lu; Tianyi Cai; Juan Qiu; Jing Jin; Yaqi Peng (Science of The Total Environment, 2024)

Integrated metabolomic and transcriptomic analyses provide comprehensive new insights into the mechanism of chitosan delay of kiwifruit postharvest ripening - Haiying Yang; Xueli Zhang; Rui Wu; Xiaoli Tang; Yanqing Yang; Xinguang Fan; Hansheng Gong; Donald Grierson; Xueren Yin; Jianzhao Li; Aidi Zhang (Postharvest Biology and Technology, 2024)

Improving prediction of soil heavy metal(loid) concentration by developing a combined Co-kriging and geographically and temporally weighted regression (GTWR) model - Huijuan Wang; Menglu Zhao; Xinmiao Huang; Xiaoyong Song; Boya Cai; Rui Tang; Jiaxun Sun; Zilin Han; Jing Yang; Yafeng Liu; Zhengqiu Fan (Journal of Hazardous Materials, 2024)

Asymmetric response of transition metal cationic orbitals to applied electric field - Xinmin Liu; Wanglin Chen; Ying Tang; Shuang Xiao; Qinyi Li; Wuquan Ding; Laosheng Wu; Rui Tian; Rui Li; Hang Li (Journal of Hazardous Materials, 2024)

Mineral exploration model for Lhasa Area, eastern Gangdese metallogenic belt: Based on knowledge-driven compositional data analysis and catchment basin division - Bingli Liu; Wenbao Zheng; Lu Wang; Cheng Li; Yunhui Kong; Rui Tang; Dejiang Luo; Miao Xie (Journal of Geochemical Exploration, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

A colorimetric and NIR fluorescent probe for ultrafast detecting bisulfite and organic amines and its applications in food, imaging, and monitoring fish freshness - Keli Zhong; Yang Li; Xiaoling Hu; Yangyang Li; Lijun Tang; Xiaofei Sun; Xuepeng Li; Jinglin Zhang; Yuqiong Meng; Rui Ma; Shulin Wang; Jianrong Li (Food Chemistry, 2024)

Enhancing compound confidence in suspect and non-target screening through machine learning-based retention time prediction - Dehao Song; Ting Tang; Rui Wang; He Liu; Danping Xie; Bo Zhao; Zhi Dang; Guining Lu (Environmental Pollution, 2024)

Mechanisms of benzene and benzo[a]pyrene biodegradation in the individually and mixed contaminated soils - Mukhtiar Ali; Qing Wang; Zhuanxia Zhang; Xing Chen; Min Ma; Zhiwen Tang; Rui Li; Biao Tang; Zhongyuan Li; Xiangfeng Huang; Xin Song (Environmental Pollution, 2024)

KCA/Na2SiO3/PNIPAm hydrogel with highly robust and strong solar modulation capability for thermochromic smart window - Rui Guo; Yuchun Shen; Yu Chen; Cheng Cheng; Chengwei Ye; Shaochun Tang (Chemical Engineering Journal, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Chameleon inspired high-temperature thermochromic traffic light type photonic crystal sensors toward early fire detection and visual sensing - Qingwen Shi; Jinxing Liang; Xuyi Wang; Kaixiang Yao; Yidan Tang; Chen Pan; Jiuxiao Sun; Rui Liu; Haiying Tan; Tao Tang (Chemical Engineering Journal, 2024)

Integrative transcriptome and metabolome analysis reveals the discrepancy in the accumulation of active ingredients between Lycium barbarum cultivars - Xuexia Liu; Han Gao; Yasmina Radani; Sijun Yue; Ziping Zhang; Jianning Tang; Jinzhong Zhu; Rui Zheng (Planta, 2024)

Pharmacological inhibition of EZH2 using a covalent inhibitor suppresses human ovarian cancer cell migration and invasion - Lihong Shi; Qiangsheng Zhang; Shirui Zhu; Qing Tang; Xin Chen; Rui Lan; Ningyu Wang; Yongxia Zhu (Molecular and Cellular Biochemistry, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

Preparation of novel Fe-containing zeolite-A for KN-R decolorization by Fenton-like reaction - Rui Qiu; Aiyin Chen; Peng Zhang; Xuejiao Tang; Cuiping Wang; Hongwen Sun (Environmental Science and Pollution Research, 2024)

ATF4 in cellular stress, ferroptosis, and cancer - Hu Tang; Rui Kang; Jiao Liu; Daolin Tang (Archives of Toxicology, 2024)

GRMPose: GCN-based real-time dairy goat pose estimation - Ling Chen; Lianyue Zhang; Jinglei Tang; Chao Tang; Rui An; Ruizi Han; Yiyang Zhang (Computers and Electronics in Agriculture, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Innovative multistep modifications of β-Lactoglobulin for enhanced emulsifying and antioxidant activities - Qingchun Zhang; Rui Wang; Jianfei He; Wei Tang; Jianhua Liu (Food Hydrocolloids, 2024)

Dynamic surface-enhanced Raman spectroscopy and positively charged probes for rapid detection and accurate identification of fungal spores in infected apples via deep learning methods - Jinghong Wang; Rui Zhu; Yehang Wu; Le Tang; Cong Wang; Mengqing Qiu; Ling Zheng; Pan Li; Shizhuang Weng (Food Control, 2024)

Impact of economic development on soil trace metal(loid)s pollution: A case study of China - Boya Cai; Rui Tang; Huijuan Wang; Jiaxun Sun; Menglu Zhao; Xinmiao Huang; Xiaoyong Song; Zilin Han; Zhengqiu Fan (Environmental Pollution, 2024)

Exploration of natural processes and anthropogenic inputs by Zn isotopes in suspended particulate matter: A case study from the Lancang River in Southwest China - Yang Tang; Guilin Han; Rui Qu; Jinke Liu; Man Liu (Environmental Pollution, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

Quantitative Proteomics Reveals Manganese Alleviates Heat Stress of Broiler Myocardial Cells via Regulating Nucleic Acid Metabolism - Shizhen Qin; Rui Wang; Jinlu Li; Defu Tang; Zhaoguo Shi (Biological Trace Element Research, 2024)

Purification and Characterization of a Novel Anticoagulant Peptide from Protein Hydrolysate of Eupolyphaga sinensis Walker - Xidong Li; Xuefei Zhuang; Huifen Li; Linmei Pan; Rui Liu; Huaxu Zhu; Zhishu Tang (International Journal of Peptide Research and Therapeutics, 2024)

Vertical variation of source-apportioned PM2.5 and selected volatile organic compounds near an elevated expressway in an urban area - Ho-Tang Liao; Chien-Mei Yen; Yu-Rui Chen; Jyun-De Wu; Shih-Wei Tsai; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

Over 1/4 of China's terrestrial area significantly contributed both to biodiversity conservation and carbon neutrality, requiring protection - Fangyi Wang; Zhicong Zhao; Pei Wang; Le Zhong; Shenglan Yang; Jiale Tang; Shuyu Hou; Tz-Hsuan Tseng; Yue Cao; Rui Yang (Science of The Total Environment, 2024)

Effects of short and long-term thermal exposure on microbial compositions in soils contaminated with mixed benzene and benzo[a]pyrene: A short communication - Mukhtiar Ali; Xin Song; Qing Wang; Zhuanxia Zhang; Meng Zhang; Min Ma; Jilu Che; Rui Li; Xing Chen; Zhiwen Tang; Biao Tang; Xiangfeng Huang (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Chuaria and Tawuia fossils from ∼1.0 Ga rocks in North China: Implications for a polyphyletic origin of Chuaria and a potential biological link between these two widespread Proterozoic taxa - Changtai Niu; Guangjin Li; Qing Tang; Xiaopeng Wang; Rui Huang; Hanzhi Qu; Mingyang Qiu; Bin Wan; Zhe Chen; Chuanming Zhou; Ke Pang; Xunlai Yuan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Suspended sediment dynamics and linking with watershed surface characteristics in a karst region - Linlv Xiao; Rui Li; Jun Jing; Jiang Yuan; Zhengyi Tang (Journal of Hydrology, 2024)

CO2 storage capacity estimation by considering CO2 Dissolution: A case study in a depleted gas Reservoir, China - Youwei He; Mengyun Liu; Yong Tang; Cunqi Jia; Yong Wang; Zhenhua Rui (Journal of Hydrology, 2024)

Insight into the transformation of 4-hydroxy-3-aminophenylarsonic acid (HAPA) and its mechanisms under simulated sunlight irradiation - Yixin Zhang; Yingjie Yan; Wenjing Bai; Rui Tang; Kuizu Su; Zhen-Hu Hu (Journal of Hazardous Materials, 2024)

Preparation of homogeneous LiF-BeF2-ZrF4 molten salt with low oxygen content - Yulong Song; Miao Shen; Jing Yang; Ling Han; Rui Tang; Sufang Zhao; Yuan Qian (Journal of Fluorine Chemistry, 2024)

Structurally regulated hydrogel evaporator with excellent salt-resistance for efficient solar interfacial water evaporation - Bingxue Huang; Rui Tang; Xinmei Zheng; Gang Chen; Qingye Li; Wei Zhang; Biyou Peng (Journal of Environmental Chemical Engineering, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

The promotion effect of Pr doping on the catalytic performance of MnCeOx catalysts for low-temperature NH3-SCR - Tong Wu; Shan Ren; Rui-tang Guo; Chu-fan Li; Yi-hao You; Shi-yi Guo; Wei-guo Pan (Fuel, 2024)

Constructing novel deep eutectic composites based on hydrogen bond network as anode material for lithium-ion batteries - Yiting Wang; Yifei Li; Jiali Chai; Qingmeng Li; Jiakai Du; Yichuan Rui; Bohejin Tang; Lei Jiang (Chemical Engineering Journal, 2024)

Boosting ion diffusion kinetics of Fe2O3/MoC@NG via heterointerface engineering and pseudocapacitance behavior: An alternative high-rate anode for high‐capacity lithium dual-ion batteries - Juan Ding; Yudai Huang; Wenhua Cheng; Rui Sheng; Zhenjie Liu; Xingchao Wang; Yong Guo; Jiulin Wang; Dianzeng Jia; Xincun Tang; Lei Wang (Chemical Engineering Journal, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Nitrogen removal characteristics of novel bacterium Klebsiella sp. TSH15 by assimilatory/dissimilatory nitrate reduction and ammonia assimilation - Jilong Ren; Jiajun Tang; Hongping Min; Dingding Tang; Rui Jiang; Yanchen Liu; Xia Huang (Bioresource Technology, 2024)

Blood Pressure Estimation Based on PPG and ECG Signals Using Knowledge Distillation - Hui Tang; Gang Ma; Lishen Qiu; Lesong Zheng; Rui Bao; Jing Liu; Lirong Wang (Cardiovascular Engineering and Technology, 2024)

Pathways for regions to achieve carbon emission peak: New insights from the four economic growth poles in China - Yu-Jie Hu; Fali Duan; Honglei Wang; Chengjiang Li; Rui Zhang; Bao-Jun Tang (Science of The Total Environment, 2024)

Emission characteristics of intermediate volatility organic compounds from a Chinese gasoline engine under varied operating conditions: Influence of fuel, velocity, torque, rotational speed, and after-treatment device - Rongzhi Tang; Song Guo; Kai Song; Ying Yu; Rui Tan; Hui Wang; Kefan Liu; Ruizhe Shen; Shiyi Chen; Limin Zeng; Zhou Zhang; Wenbin Zhang; et al. (Science of The Total Environment, 2024)

Metabolome analysis to investigate the effect of heavy metal exposure and chemoprevention agents on toxic injury caused by a multi-heavy metal mixture in rats - Jinyue Zhou; Hang Hong; Jinshun Zhao; Rui Fang; Shushu Chen; Chunlan Tang (Science of The Total Environment, 2024)

Synergizing policies for carbon reduction, energy transition and pollution control: Evidence from Chinese power generation industry - Yu-Jie Hu; Rui Zhang; Honglei Wang; Chengjiang Li; Bao-Jun Tang (Journal of Cleaner Production, 2024)

Tracing and utilizing nitrogen loss in wastewater treatment: The trade-off between performance improvement, energy saving, and carbon footprint reduction - Meihui Tang; Rui Du; Shenbin Cao; Maxence Berry; Yongzhen Peng (Journal of Environmental Management, 2024)

Harnessing synergy: Integrating agricultural waste and nanomaterials for enhanced sustainability - Yuying Tang; Weichen Zhao; Li Gao; Guikai Zhu; Yaqi Jiang; Yukui Rui; Peng Zhang (Environmental Pollution, 2024)

Comparison of lateral resistance between I-shaped and X-shaped sleepers using finite element and discrete element coupling method - Cheng Chen; Zi-an Tang; Lei Zhang; Rui Rui (Computers and Geotechnics, 2024)

Inverse kinetic isotope effect of proton and deuteron permeation through pyridinic N-doped graphene - Jingwen Ba; Jinfan Chen; Renjin Xiong; Jingsong Xu; Haibo Li; Xiayan Yan; Cheng Qin; Rui Li; Qifa Pan; Xinxin Tan; Tao Tang; Xin Xiang; et al. (Chemical Engineering Journal, 2024)

Tannic acid-coated cellulose nanocrystal-reinforced transparent multifunctional hydrogels with UV-filtering for wearable flexible sensors - Shuyuan Cui; Sufeng Zhang; Fengjiao Zhang; Rui Lin; Chengfang Tang; Xiaokai Jing (Carbohydrate Polymers, 2024)

Correction to: Protective Efect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2024)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Plant colorants for natural hair coloration: Dyeing optimization and photostability assessment - Hongyan Cui; Rui Cai; Zhongjie Hua; Ying Tang (Sustainable Chemistry and Pharmacy, 2023)

Human activities contributing to the accumulation of high-risk trace metal(loid)s in soils of China's five major urban agglomerations - Rui Tang; Boya Cai; Huijuan Wang; Xinmiao Huang; Xiaoyong Song; Zilin Han; Menglu Zhao; Jiaxun Sun; Honghui Huang; Jian Huang; Zhengqiu Fan (Science of The Total Environment, 2023)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

Auto encoder generative adversarial networks - based mineral prospectivity mapping in Lhasa area, Tibet - Miao Xie; Bingli Liu; Lu Wang; Cheng Li; Yunhui Kong; Rui Tang (Journal of Geochemical Exploration, 2023)

Synergistic effect triggered by Fe2O3 and oxygen-induced hydroxyl radical enhances formation of amino-phenolic humic-like substance - Yingchao Zhang; Zhitao Bi; Wenxin Tian; Zhenyu Ge; Yang Xu; Rui Xu; Hongqiong Zhang; Shoufeng Tang (Journal of Environmental Management, 2023)

Fabrication of N, O dual-doped ultra-microporous carbon from microalgae for efficient CO2 capture via deep eutectic solvent-assisted hydrothermal carbonization - Rui Huang; Anding Zhong; Kexia Huang; Yujie Yu; Yumu Tang; Peng Xia (Journal of Environmental Chemical Engineering, 2023)

Recent advances in stability improvement of anthocyanins by efficient methods and its application in food intelligent packaging: A review - Rui Tang; Yong He; Kai Fan (Food Bioscience, 2023)

A new method for estimating the smart readiness of building stock data using display energy Certificate data - Vasiliki Kourgiozou; Daniel Godoy Shimizu; Mark Dowson; Andrew Commin; Rui Tang; Dimitrios Rovas; Dejan Mumovic (Energy and Buildings, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Assessing the Connectivity of a Regional Fractured Aquifer Based on a Hydraulic Conductivity Field Reversed by Multi-Well Pumping Tests and Numerical Groundwater Flow Modeling - Jingjing Lin; Rui Ma; Ziyong Sun; Liansong Tang (Journal of Earth Science, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Coupling coordination evaluation of economic development, ecological environment, and the tourism industry in ski resorts - Chengcai Tang; Rui Zeng; Ying Han (Journal of Cleaner Production, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

Novel Fe trihalides solid molten salt-FeX3 (X = F, Cl, Br) via one-step method with low temperature as anodes of lithium-ion batteries - Yifei Li; Yiting Wang; Zhiyuan Chen; Qingmeng Li; Jiakai Du; Jiali Chai; Longzhen Wang; Yichuan Rui; Lei Jiang; Bohejin Tang (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Confined tuning of the charge distribution of Pt electrocatalyst for reinforcing anti-poisoning ability: Toward efficient separation of hydrogen from gases containing ammonia - Changqing Jin; Fanglin Wu; Haibo Tang; Hongfei Pan; Zhida Chen; Rui Wang; Zihan Meng; Junsheng Li; Haolin Tang (Chemical Engineering Journal, 2023)

A machine learning-based method for identifying the meteorological field potentially inducing ozone pollution - Jia-Hui Tang; Si-Rui Pan; Lei Li; Pak-Wai Chan (Atmospheric Environment, 2023)

Unexpected moderate contribution of intermediate volatility organic compounds from gasoline vehicle emission to secondary organic aerosol formation in summer of Beijing - Rongzhi Tang; Song Guo; Quanyang Lu; Kai Song; Yuanzheng Gong; Rui Tan; Kefan Liu; Hui Wang; Ying Yu; Ruizhe Shen; Shiyi Chen; Limin Zeng; et al. (Atmospheric Research, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Association between urinary phthalate metabolites and chronic obstructive pulmonary disease incidence in US adults: results from NHANES 2007–2018 - Jiran Shen; Yue Wang; Sijing Zhou; Min Tang; Min Li; Rui Han; Guanghe Fei; Ran Wang (Environmental Science and Pollution Research, 2023)

Rapid, stable, and highly-efficient development of salt-tolerant aerobic granular sludge by inoculating magnetite-assisted mycelial pellets - Xushen Han; Rui Tang; Changshen Liu; Jingxue Yue; Yan Jin; Jianguo Yu (Chemosphere, 2023)

Gravity-driven membrane system treating heavy metals-containing secondary effluent: Improved removal of heavy metals and mechanism - Xiaobin Ma; Yanrui Wang; Le Tong; Jiaoying Luo; Rui Chen; Yuanxin Wang; Xishou Guo; Jinlong Wang; Zhiwei Zhou; Jingyao Qi; Guibai Li; Heng Liang; et al. (Chemosphere, 2023)

Illustration on phenotypic and genotypic characteristics of typical multi-antibiotic resistant bacteria in aquatic environments through complete genomes and comparative genomics - Chunli Wan; Rui Tang; Liyan Deng; Liya Fu; Panxin Wang; Xiang Liu; Changyong Wu (Chemosphere, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Numerical study on unsteady cavitation flow and vortex dynamics characteristics around the Delft Twist 11 hydrofoil - Gang Yang; Xi Shen; Bin Xu; Qinghui Meng; Chengxin Chang; Rui Tang; Desheng Zhang (Ocean Engineering, 2023)

Tonian discoidal fossils from North China: Relating discs to worm-like annulated tubes and their paleoecological and evolutionary implications - Guangjin Li; Ke Pang; Qing Tang; Lei Chen; Chengxi Wu; Rui Huang; Bin Wan; Xunlai Yuan; Chuanming Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Role of suspended solids on the co-precipitation of pathogenic indicators and antibiotic resistance genes with struvite from digested swine wastewater - Wenjing Bai; Rui Tang; Guangxue Wu; Wei Wang; Shoujun Yuan; Liwen Xiao; Xinmin Zhan; Zhen-Hu Hu (Journal of Hazardous Materials, 2023)

The severity of foreign direct investment components on China's carbon productivity - Xin Sheng; Rui Yi; Decai Tang; David D. Lansana; Bright Obuobi (Journal of Cleaner Production, 2023)

Sustainable production of eco-friendly rubberized asphalt binders through chemically crosslinking with polymer modifier - Naipeng Tang; Chenyang Xue; Gengren Hao; Weidong Huang; Hongzhou Zhu; Rui Li (Journal of Cleaner Production, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

A spectral-temporal constrained deep learning method for tree species mapping of plantation forests using time series Sentinel-2 imagery - Zehua Huang; Liheng Zhong; Feng Zhao; Jin Wu; Hao Tang; Zhengang Lv; Binyuan Xu; Longfei Zhou; Rui Sun; Ran Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Investigation of the potential ameliorative effects of DHA-enriched phosphatidylserine on bisphenol A-induced murine nephrotoxicity - Qiuyan Pu; Fei Yang; Rui Zhao; Su Jiang; Yunping Tang; Tao Han (Food and Chemical Toxicology, 2023)

QSPR models for sublimation enthalpy of energetic compounds - Rui Liu; Yuechuan Tang; Jie Tian; Jing Huang; Chaoyang Zhang; Linyuan Wang; Jian Liu (Chemical Engineering Journal, 2023)

Space charge region induced self-evolution dehydrogenation of polymorphic magnesium-based hydrides - Qinke Tang; Jiangchuan Liu; Mengran Li; Rui Shi; Yunfeng Zhu; Yao Zhang; Jiguang Zhang; Yana Liu; Yijin Wu; Ling Li; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

Multifunctional carboxylated cellulose nanofibers/exfoliated bentonite/Ti3C2 aerogel for efficient oil adsorption and recovery: The dual effect of exfoliated bentonite and MXene - Rui Tang; Ya Hu; Jingyuan Yan; Shiqi Xu; Yinlong Wang; Jinsheng Yan; Dankui Liao; Hanbing Zhang; Zhangfa Tong (Chemical Engineering Journal, 2023)

Sodium alginate based energy harvesting fibers: Multiscale structure and moist-electrical properties - Rui Zhang; Hai Wang; Meijie Qu; Shuhui Li; Yue Ma; Xinye Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Targeted Energy Metabolomics Combined with Spatial Metabolomics Study on the Efficacy of Guhong Injection Against Cerebral Ischemia Reperfusion - Huanhuan Wang; Zhenkun Li; Guangzhao Cao; Liying Tang; Rui Zhou; Caifeng Li; Jingjing Zhang; Hongwei Wu; Xianyu Li; Hongjun Yang (Molecular Neurobiology, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Investigation of nephrotoxicity on mice exposed to polystyrene nanoplastics and the potential amelioration effects of DHA-enriched phosphatidylserine - Yunping Tang; Rui Zhao; Qiuyan Pu; Su Jiang; Fangmiao Yu; Zuisu Yang; Tao Han (Science of The Total Environment, 2023)

New insights into health risk assessment on soil trace metal(loid)s: Model improvement and parameter optimization - Jiaxun Sun; Xinmiao Huang; Xiaoyong Song; Rui Tang; Menglu Zhao; Boya Cai; Huijuan Wang; Zilin Han; Yafeng Liu; Zhengqiu Fan (Journal of Hazardous Materials, 2023)

Oxidation of 1,3-diphenylguanidine (DPG) by goethite activated persulfate: Mechanisms, products identification and reaction sites prediction - Jinbin Lai; Ting Tang; Xiaodong Du; Rui Wang; Jiahao Liang; Dehao Song; Zhi Dang; Guining Lu (Environmental Research, 2023)

Distinct urban-rural gradients of air NO2 and SO2 concentrations in response to emission reductions during 2015–2022 in Beijing, China - Tao He; Yang Tang; Rui Cao; Nan Xia; Binghe Li; Enzai Du (Environmental Pollution, 2023)

Ultimate bearing capacity of strip footings above rectangular voids in Hoek-Brown rock masses - Yao Xiao; Manyouye Zhang; Zheng Zhou; Zhenkun Hou; Jianbing Lv; Mengxiong Tang; Rui Zhang (Computers and Geotechnics, 2023)

Polyphenol synergistic cerium oxide surface engineering constructed core-shell nanostructures as antioxidants for durable and high-performance proton exchange membrane fuel cells - Shengqiu Zhao; Yucong Liao; Rui Wang; Guoliang Liu; Haining Zhang; Haolin Tang (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

The extraordinarily large vortex structure of Typhoon In-fa (2021), observed by spaceborne microwave radiometer and synthetic aperture radar - Ziyao Sun; Lina Bai; Xuesong Zhu; Xin Huang; Rui Jin; Hui Yu; Jie Tang (Atmospheric Research, 2023)

Gut microbiota bridges the iron homeostasis and host health - Lanling Xiao; Rui Tang; Jie Wang; Dan Wan; Yulong Yin; Liwei Xie (Science China Life Sciences, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Nafamostat mesilate prevented caerulein-induced pancreatic injury by targeting HDAC6-mediated NLRP3 inflammasome activation - Peng Chen; Li-Jun Zhao; Ling Huang; Wen-Qi He; Ying-Rui Tang; Yi Liu; Jian-Dong Ren (Inflammation Research, 2023)

Resolved CFD-DEM Simulation of Free Settling of Polyhedral Particles with Various Orientations: Insights Provided by Oscillation Behavior in Quiescent Liquid - Zhimin Zhang; Yuanyi Qiu; Hao Xiong; Rui Tang (Journal of Marine Science and Engineering, 2023)
Particle settling is the process by which particulates move toward the bottom of a liquid, which can affect the sediment transport and energy balance of marine systems. However, the deficiency in understanding the resolved fluid–particle interactions with complex boundaries in the settling process awaits resolution. This study employs a hybrid approach that combines computational fluid dynamics (CFD) with the discrete element method (DEM) to fully simulate the free-settling behavior of polyhedral particles in water. The accuracy of the method is verified by comparing numerical results with experimental data of ellipsoidal particle settling. Two series of tests with horizontal and vertical particle release directions are established to investigate the effects of particle shape features, such as the aspect ratio (AR) and corner (C), on the particles’ mechanical behavior and hydrodynamic characteristics. The results demonstrate that particle shape exerts a substantial influence on fluid resistance, rotational motion, and fluid disturbance throughout the settling process. The maximum velocities in vertically released cases are roughly 1.2–1.3 times greater than those in horizontally released cases. The study highlights the potency of the resolved CFD-DEM method as a robust technique for comprehending fluid–particle phenomena within the marine geotechnical engineering, including sedimentation and erosion of seabed sediments.

Recent advances in core-shell structured catalysts for low-temperature NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Chemosphere, 2023)

Co-precipitation of heavy metals with struvite from digested swine wastewater: Role of suspended solids - Wenjing Bai; Rui Tang; Guangxue Wu; Wei Wang; Shoujun Yuan; Liwen Xiao; Xinmin Zhan; Zhen-Hu Hu (Journal of Hazardous Materials, 2023)

Experimental and theorical study on the pyrolysis behaviors of 2,3,3,3-tetrafluroropropene - Rui Zhai; Yuan Zhuang; Siwei Tan; Jingchun Tang (Journal of Fluorine Chemistry, 2023)

Decorative ZIF-8 covered facet-dependent Cu2O toward highly efficient adsorption by reduction U(VI) to U(IV) - Xiaomei Zhang; Nina Yan; Min Wang; Xizhi Jiang; Rui Xu; Min Feng; Lei Xu; Shaochun Tang (Journal of Environmental Chemical Engineering, 2023)

Estimation of rough fracture network permeability using fractal and topology theories - Di Shi; Liping Li; Yintong Guo; Jianjun Liu; Jupeng Tang; Xin Chang; Rui Song; Mingyang Wu (Gas Science and Engineering, 2023)

Physicochemical properties and in vitro digestion behavior of emulsion gels stabilized by rice bran protein aggregates: Effects of heating time and induction methods - Yongxue Luo; Kexin Wang; Rui Pan; Ting Li; Qingjie Sun; Chuanfen Pu; Wenting Tang (Food Research International, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The first homosporous lycophyte genome revealed the association between the recent dynamic accumulation of LTR-RTs and genome size variation - Ji-Gao Yu; Jun-Yong Tang; Ran Wei; Mei-Fang Lan; Rui-Chen Xiang; Xian-Chun Zhang; Qiao-Ping Xiang (Plant Molecular Biology, 2023)

Synthesis and pharmacological evaluation of new disulfides linked to 1,2,4-triazole bearing urea moiety - Rui Tang; Haichuan Zhao; Shuai Zhang; Xiaojia Liu; Jinbiao Liu; Wei Li; Hongying Wang; Caiwen Li; Baoquan Chen (Medicinal Chemistry Research, 2023)

Centimeter-level clock synchronization and space-borne timescale generation for BDS-3 using inter-satellite link measurements - Jianhua Yang; Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Yezhi Song; Yufei Yang; Rui Guo; Shuai Liu; Junyang Pan (Journal of Geodesy, 2023)

Evaluation of carbon emission efficiency and spatial relevance in the thermal power industry: evidence from China - Yu Liu; Rui-tang Guo; Wei-guo Pan (Environment, Development and Sustainability, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Government–business relations, environmental information transparency, and Hu-line-related factors in China - Rui Yang; Yingwen Chen; Yiqun Liu; Yuchen Feng; Jianwan Ji; Christina W. Y. Wong; Xin Miao; Yanhong Tang (Environment, Development and Sustainability, 2023)

Optimizing Energy Management and Case Study of Multi-Energy Coupled Supply for Green Ships - Zhe Wang; Yue Ma; Yinyu Sun; Haobo Tang; Menglong Cao; Rui Xia; Fenghui Han (Journal of Marine Science and Engineering, 2023)
The ship industry is currently facing numerous challenges, including rising fuel prices, limited fuel resources, and increasingly strict regulations related to energy efficiency and pollutant emissions. In this context, the adoption of green-ship wind–photovoltaic–electricity–fuel multi-energy supply systems has emerged as an efficient and clean technology that harnesses multiple energy sources. These systems have the potential to increase the utilization of renewable energy in ship operations while optimizing management practices in order to enhance overall energy efficiency. To address these challenges, this article presents a comprehensive energy supply system for ships that integrates multi-energy sources for cold–heat–electricity supply. The primary components of this system include fuel cells, photovoltaic equipment, wind turbines, electric heating pumps, electric refrigerators, thermal refrigerators, batteries, and heat storage tanks. By ensuring the safety of the system, our approach aims to minimize daily operating costs and optimize the performance of the multi-energy flow system by running scheduling models. To achieve this, our proposed system utilizes dynamic planning techniques combined with ship navigation conditions to establish an optimized management model. This model facilitates the coordinated distribution of green ship electricity, thermal energy, and cooling loads. The results of our study demonstrate that optimized management models significantly reduce economic costs and improve the stability of energy storage equipment. Specifically, through an analysis of the economic benefits of power storage and heat storage tanks, we highlight the potential for reducing fuel consumption by 6.0%, 1.5%, 1.4%, and 2.9% through the use of electric–thermal hybrid energy storage conditions.

Eco-friendly phenol formaldehyde resin wood adhesive from bagasse lignin liquefaction - Jinming Liu; Enjun Xie; Yanrong Tang; Rui Feng; Weixing Gan (Sustainable Chemistry and Pharmacy, 2023)

Fe contents and isotopes in suspended particulate matter of Lancang River in Southwest China - Yang Tang; Guilin Han; Liu Man; Jie Zeng; Rui Qu (Science of The Total Environment, 2023)

Rainstorm sediment events in heterogeneous karst small watersheds: Process characteristics, prediction modeling and management enlightenment - Jun Jing; Jiang Yuan; Rui Li; Zaike Gu; Li Qin; Jiayong Gao; Linlv Xiao; Zhenyi Tang; Ling Xiong (Science of The Total Environment, 2023)

Geochemical controls on the distribution and bioavailability of heavy metals in sediments from Yangtze River to the East China Sea: Assessed by sequential extraction versus diffusive gradients in thin-films (DGT) technique - Yuhao Liang; Rui Wang; G. Daniel Sheng; Linhong Pan; Ergang Lian; Ni Su; Xiliang Tang; Shouye Yang; Daqiang Yin (Journal of Hazardous Materials, 2023)

Long-term effect of PBDE-99 prenatal exposure on spermatogenic injuries via the dysregulation of autophagy - Jun Wu; Fuming Deng; Xiangliang Tang; Wenbin Chen; Rui Zhou; Tianxin Zhao; Xiangming Mao; Fangpeng Shu (Journal of Hazardous Materials, 2023)

CO2 storage potential assessment of offshore saline aquifers in China - Jiazheng Qin; Qianhu Zhong; Yong Tang; Zhenhua Rui; Shuai Qiu; Haoyu Chen (Fuel, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

Physicochemical Characterization of Three Active Pharmaceutical Ingredients for Compound Glycyrrhizin Solid Formulation and Compatibility Analysis via Thermal and Non-thermal Techniques - Xiang-yun Xie; Zhan-ying Chang; Chun-li Chen; Liang Zhang; Mei Wang; Cheng Tang; Hong-rui Xue; Xiao-li Gao (Journal of Pharmaceutical Innovation, 2023)

Causal associations of circulating Helicobacter pylori antibodies with stroke and the mediating role of inflammation - Xingzhi Guo; Peng Tang; Xin Zhang; Rui Li (Inflammation Research, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Surface-enhanced Raman spectroscopy charged probes under inverted superhydrophobic platform for detection of agricultural chemicals residues in rice combined with lightweight deep learning network - Shizhuang Weng; Le Tang; Mengqing Qiu; Jinghong Wang; Yehang Wu; Rui Zhu; Cong Wang; Pan Li; Wen Sha; Dong Liang (Analytica Chimica Acta, 2023)

Rhizospheric soil organic carbon accumulated but its molecular groups redistributed via rhizospheric soil microorganisms along multi-root Cerasus humilis plantation chronosequence at the karst rocky desertification control area - Qin Tang; Qiang Li; Lingchen Tong; Rui Wu; Jiao Xu (Environmental Science and Pollution Research, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

Effects of polystyrene nanoplastic gestational exposure on mice - Xiaoke Wang; Zixuan Zhao; Xin Wang; Wenxuan Hu; Chao luo; Xiuyu Chu; Muzhou Qian; Rui Wang; Shali Yu; Qiyun Wu; Juan Tang; Xinyuan Zhao (Chemosphere, 2023)

Examining moisture contribution for precipitation in response to climate change and anthropogenic factors in Hengduan Mountain Region, China - Xingxing Zhang; Zhaofei Liu; Yubo Liu; Liguang Jiang; Rui wang; Hou Jiang; Jing Li; Qiuhong Tang; Zhijun Yao (Journal of Hydrology, 2023)

A practical application of front-face synchronous fluorescence spectroscopy to rapid, simultaneous and non-destructive determination of piperine and multiple adulterants in ground black and white pepper (Piper nigrum L.) - Zhao-Xi Liu; Shu-Rui Xiong; Shu-Hua Tang; Ying Wang; Jin Tan (Food Research International, 2023)

Comparison of Pivot Profile, CATA, and Pivot-CATA for the sensory profiling of instant black coffee - Shiqin Wang; Keng Hong Ng; Kwan Hiu Yee; Yihang Tang; Rui Meng; Wenmeng He (Food Quality and Preference, 2023)

A sulfonate-functionalized covalent organic framework for record-high adsorption and effective separation of organic dyes - Rui Li; Xihao Tang; Jialin Wu; Kai Zhang; Qianni Zhang; Jiaqi Wang; Jiayue Zheng; Shengrun Zheng; Jun Fan; Weiguang Zhang; Xinle Li; Songliang Cai (Chemical Engineering Journal, 2023)

Soil microbial and macroinvertebrate functional diversity in response to Zokor disturbance in Tibetan alpine meadow - Guohui Ye; Bin Chu; Zhuangsheng Tang; Guixin Hu; Daerhan Bao; Rui Hua; Martin Pfeiffer; Limin Hua; Yujie Niu (CATENA, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

In situ degradation of fluoroquinolone antibiotics in groundwater by CoFe2O4 nanoparticle-activated peroxymonosulfate: Performance, activation mechanism, degradation pathway - Rui Xu; Kun Qian; Xianjun Xie; Jiangjun Chen; Weiguo Tang; Feng Tao; Yanxin Wang (Applied Geochemistry, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Reservoir flood regulation affects nutrient transport through altering water and sediment conditions - Xianqiang Tang; Rui Li; Danyang Wang; Zheng Jing; Wei Zhang (Water Research, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Boosted degradation of tetracycline over a novel hierarchical 2D/1D S-scheme heterojunction Bi2O4 @SnS under visible light irradiation - Shenggeng Zhao; Fangyan Chen; Yanhua Song; Ji Hua; Rui Wu; Jietong Yang; Yubin Tang (Journal of Environmental Chemical Engineering, 2023)

The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules - Haili Sun; Yifei Sun; Xin Tang; Yuanmeng Cui; Demei Meng; Yuyu Zhang; Ku Li; Hui Guo; Hai Chen; Rui Yang (Food Bioscience, 2023)

Environmental fate of microplastics in an urban river: Spatial distribution and seasonal variation - Ting Li; Kai Liu; Rui Tang; Jun-Rong Liang; Lei Mai; Eddy Y. Zeng (Environmental Pollution, 2023)

Construction of porous chitosan macrospheres via dual pore-forming strategy as host for alkaline protease immobilization with high activity and stability - Ying Tang; Penghui Wang; Hui Zeng; Zebao Rui (Carbohydrate Polymers, 2023)

In-situ sensor calibration for building HVAC systems with limited information using general regression improved Bayesian inference - Guannan Li; Jiahao Xiong; Rui Tang; Shaobo Sun; Chongchong Wang (Building and Environment, 2023)

Sandstorms damage the photosynthetic activities of Haloxylon ammodendron seedlings - Shengbo Shi; Dangwei Zhou; Rui Shi; Tao Sun; Fanglin Wang; Xiuzhen Gao; Yunian Zhang; Peng Zhao; Gaoxing Xu; Jinnian Tang (Acta Physiologiae Plantarum, 2023)
Haloxylon ammodendron is a preferred shrub species for buffering against wind and fixing sand in arid sandy areas of northwest China. To determine whether sandstorms cause damage to H. ammodendron seedlings, we investigated the effects of wind-blown sands on the photosynthetic function of H. ammodendron by simulating sand-carrying wind in the wind tunnel. The results showed that photosystem II (PSII) non-photochemical quenching ( NPQ ) was sensitive to wind erosion, and sustained blowing of sand-carrying winds enhanced NPQ reduction. The rapidly relaxing quenching NPQ f made up the majority component of NPQ ; the NPQ f / NPQ ratio was approximately 64.4% in the sand-free wind group and nearly 56.2% in the sand-carrying wind group. The distribution of the quantum efficiency of the excitation energy indicated that the relative proportions of the quantum yield of PSII photochemistry Φ PSII , the quantum yield of quenching due to light-induced Φ NPQ , and non-light-induced Φ NO were influenced by both wind erosion and light intensity; the sand-carrying wind resulted in a relative decrease in Φ NPQ and a corresponding increase in Φ NO . The maximum quantum efficiency of PSII photochemistry F v / F m was relatively stable in the sand-free wind group, with an average value of approximately 0.81. Compared to sand-free wind, sand-carrying winds caused remarkable decreases in F v / F m . Light intensity was the main factor affecting Φ PSII , Φ NPQ , and relative electron transport rate ( rETR ); there was no interaction effect between the duration of sand-carrying wind and light intensity. Taken together, wind-blown sands cause irreversible damage to the photosynthesis of H. ammodendron seedlings, which is the main factor restricting population regeneration in shelterbelts.

Modification of fluorescence staining method for small-sized microplastic quantification: Focus on the interference exclusion and exposure time optimization - Wentao Hu; Rui Tang; Shoujun Yuan; Miao Gong; Penghui Shi; Wei Wang; Zhen-Hu Hu (Environmental Science and Pollution Research, 2023)

Study on the mechanical properties of coral sands with different particle gradations - Yuan-yi Chen; Yi Tang; Yun-fei Guan; Rui-ming Liu; Xun Han; Xian-qiang Zhao (Marine Georesources & Geotechnology, 2023)

Pyrolysis temperature affects the physiochemical characteristics of lanthanum-modified biochar derived from orange peels: Insights into the mechanisms of tetracycline adsorption by spectroscopic analysis and theoretical calculations - Zhihao Chen; Bingfeng Lin; Yingping Huang; Yanbiao Liu; Yonghong Wu; Rui Qu; Cilai Tang (Science of The Total Environment, 2023)

Potential negative effects of illumination on gravity-driven membrane system in treating sulfamethoxazole-containing water - Rui Chen; Han Zhang; Dachao Lin; Jinlong Wang; Yuanqing Guo; Xiaobin Tang; Weijia Gong; Heng Liang (Resources, Conservation and Recycling, 2023)

Simulating urban expansion using cellular automata model with spatiotemporally explicit representation of urban demand - Jianxin Yang; Wenwu Tang; Jian Gong; Rui Shi; Minrui Zheng; Yunzhe Dai (Landscape and Urban Planning, 2023)

Spatio-temporal characteristics of soil Cd pollution and its influencing factors: A Geographically and temporally weighted regression (GTWR) method - Menglu Zhao; Huijuan Wang; Jiaxun Sun; Rui Tang; Boya Cai; Xiaoyong Song; Xinmiao Huang; Jian Huang; Zhengqiu Fan (Journal of Hazardous Materials, 2023)

Influence of different thermal treatment methods on the processing qualities of sesame seeds and cold-pressed oil - Ying Huang; Changsheng Liu; Zhengfa Ge; Fenghong Huang; Hu Tang; Qi Zhou; Rui Liu; Jiazhang Huang; Chang Zheng (Food Chemistry, 2023)

Differences in the patterns and mechanisms of leaf and ecosystem-scale water use efficiencies on the Qinghai-Tibet Plateau - Xiang Wang; Guo Chen; Mingquan Wu; Xiaozhen Li; Qi Wu; Peng Wang; Hui Zeng; Rui Yang; Xiaolu Tang (CATENA, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

Identification of three Streptomyces strains and their antifungal activity against the rubber anthracnose fungus Colletotrichum siamense - Jinhong Wang; Rui Wang; Jing Gao; Huanqing Liu; Wen Tang; Zhiqiang Liu; Xiaoyu Li (Journal of General Plant Pathology, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

How seasonality affects the environmental performance of fresh appetite: Insights from cherry consumption in China - Xin Xiong; Junyi Shen; Yan Hao; Lixiao Zhang; Rui Zhao; Shoujuan Tang; Xinqing Li; Zhimin Shi (Journal of Environmental Management, 2023)

Recent progress of CeO2-based catalysts with special morphologies applied in air pollutants abatement: A review - Tong Wu; Rui-tang Guo; Chu-fan Li; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2023)

Hydrogen bond network reconstruction of lignite for efficient moisture removal via deep-eutectic-solvent-assisted hydrothermal treatment - Yujie Yu; Jianfeng Li; Rui Huang; Xianrui Yao; Yumu Tang; Yu He (Fuel, 2023)

Experimental and kinetic study on JP-10/air autoignition and the effect of NO2 at high temperatures - Lei Shi; Ping Xu; Rui Wang; Weixin Tang; Tao Ding; Rongpei Jiang; Changhua Zhang (Fuel, 2023)

Fabricated noble-metal free Co2B/g-C3N4 photocatalyst with 2D/2D structure achieved remarkable water splitting performance from visible to near-infrared wavelengths - Jun-ying Tang; Rui-tang Guo; Wei-guo Pan; Wei-guo Zhou (Fuel, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Novel supported low-temperature solid molten salt (SMS) anode materials for Li-ion batteries - Lei Jiang; Ning Han; Tingting Luo; Zhe Zhang; Fenghao Liang; Daoning Wu; Xiaochun Li; Fengjiao Liu; Yichuan Rui; Wei Zhang; Yi Qu; Bohejin Tang (Chemical Engineering Journal, 2023)

SnO2/ATP catalyst enabling energy-efficient and green amine-based CO2 capture - Zhan Tan; Shangshang Zhang; Fangfang Zhao; Rui Zhang; Feiying Tang; Kuiyi You; He'an Luo; Xiaowen Zhang (Chemical Engineering Journal, 2023)

Long-lifespan benzoquinone-intercalated vanadium oxide with vacancies and disorders on the (00l) facets for efficient sodium-ion battery: A facile approach to Na+ capture and pre-sodiation - Rui Tang; Kai Li; Changlin Liu; Yang Liu; Yun Gong; Jianhua Lin (Chemical Engineering Journal, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Correction: Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Repurposing of spent lithium-ion battery separator as a green reductant for efficiently refining the cathode metals - Wei Hou; Xuanrui Huang; Rui Tang; Yulin Min; Qunjie Xu; Zhenhu Hu; Penghui Shi (Waste Management, 2023)

Naïve-like conversion of bovine induced pluripotent stem cells from Sertoli cells - Yu Jiang; Ning-Ning Cai; Xing-Lan An; Wen-Qian Zhu; Rui Yang; Bo Tang; Zi-Yi Li; Xue-Ming Zhang (Theriogenology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Secondary organic aerosol formation in China from urban-lifestyle sources: Vehicle exhaust and cooking emission - Zirui Zhang; Wenfei Zhu; Min Hu; Hui Wang; Lizi Tang; Shuya Hu; Ruizhe Shen; Ying Yu; Kai Song; Rui Tan; Zheng Chen; Shiyi Chen; et al. (Science of The Total Environment, 2023)

Ca(ClO)2 pretreatment enhancing suspended solids removal through flocculation from digested dairy wastewater and its mechanisms - Xinyue Ma; Ziyan Cheng; Wenjing Bai; Rui Tang; Guangxue Wu; Xinmin Zhan; Zhen-Hu Hu (Science of The Total Environment, 2023)

Experimental study on non-isothermal oxidative characteristics and kinetics of methane in accelerating rate calorimetry tests - Xiaodong Tang; Wanfen Pu; Dan Wang; Shanshan Qu; Yiming Rui; Xuepei Zhao; Renbao Liu (Fuel, 2023)

Comparative assessment of nutritional composition, polyphenol profile and antioxidative properties of wild edible ferns from northeastern China - Yun Guo; Sen Shi; Nan Yang; Mei-Xin Tang; Ze-Jia Duan; Xiao-Rui Guo; Zhong-Hua Tang (Food Research International, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Yeast cell wall polysaccharides in Tibetan kefir grains are key substances promoting the formation of bacterial biofilm - XiaoMeng Wang; XueLiang Zhang; YuKe Wang; NanYu Tang; LuYao Xiao; JuanJuan Tian; Xin Rui; Wei Li (Carbohydrate Polymers, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Precise orbit determination for BDS-3 GEO satellites enhanced by intersatellite links - Xiaojie Li; Xiaogong Hu; Rui Guo; Chengpan Tang; Shuai Liu; Jie Xin; Jinglei Guo; Yijun Tian; Yufei Yang; Jianhua Yang; Xinglong Zhao (GPS Solutions, 2023)

Effects of combined application of nitrogen, phosphorus, and potassium fertilizers on tea (Camellia sinensis) growth and fungal community - Sheng Tang; Jingjie Zhou; Wankun Pan; Tao Sun; Mengjiao Liu; Rui Tang; Zijing Li; Qingxu Ma; Lianghuan Wu (Applied Soil Ecology, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Assessing psychological factors on farmers' intention to apply organic manure: an application of extended theory of planned behavior - Jing Li; Rui Jiang; Xueyu Tang (Environment, Development and Sustainability, 2022)

Modification of TiO2 by Er3+ and rGO enhancing visible photocatalytic degradation of arsanilic acid - Xinghao Ren; Hang Yao; Rui Tang; Rong A; Shoujun Yuan; Wei Wang; Ibrahim Mohamed Ali; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

The integrated exposure assessment and potential risks of five organophosphorus pesticides in vegetables in Zhejiang, China (2018–2020) - Quan Zhang; Rui Cao; Tao Tang; Zeteng Ying; Shitao Hu; Yitian Xu (Environmental Science and Pollution Research, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Risk Assessment and Source Identification of Arsenic in Surface Sediments from Caohai Lake, China - Ying Tang; Xinmin Liu; Rui Tian; Rui Li; Hang Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Sensor Partitioning Placements via Random Walk and Water Quality and Leakage Detection Models within Water Distribution Systems - Tianwei Mu; Manhong Huang; Shi Tang; Rui Zhang; Gang Chen; Baiyi Jiang (Water Resources Management, 2022)

Nutrient combined hydrodynamic mixing facilitates Microcystis dominating phytoplankton communities: evidence from a microcosm experiment - Guijun Yang; Wenwen Pan; Zheng Rui; Chunni Zhong; Xiangming Tang; Ruipeng Yu; Xiquan Hu (Journal of Applied Phycology, 2022)

Integration of ABC curve, three dimensions of alpha diversity indices, and spatial patterns of fish assemblages into the health assessment of the Chishui River basin, China - Fandong Yu; Fei Liu; Zhijun Xia; Chunsen Xu; Jianwei Wang; Rui Tang; Zujun Ai; Youzhao Zhang; Miaomiao Hou; Xinhua Zou (Environmental Science and Pollution Research, 2022)

Protective Effect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2022)

Heavy metal pollution status and deposition history of mangrove sediments in Zhanjiang Bay, China - Daobin Tang; Songying Luo; Suyan Deng; Rui Huang; Bishan Chen; Ziyi Deng (Frontiers in Marine Science, 2022)
Mangroves have high ecological service value and play an important role in achieving carbon neutrality. However, the ecological services provided by mangroves are gradually declining due to the threat of various pollutants, especially heavy metal (HM) pollution. Researching the status and history of heavy metals (HMs) in mangrove sediments improves understanding of how mangroves can be protected. We studied the Zhanjiang Bay mangroves, which is an important part of the Zhanjiang Mangrove National Nature Reserve, and is greatly affected by human activities, as an example. We analyzed the pollution levels and deposition process of HMs and their influencing factors. In the mangrove surface sediments of Zhanjiang Bay, Pb, Cr, and Co were slightly to moderate enriched and Cu was moderate-heavy enriched. Zn and Hg showed moderate-heavy enrichment and heavy enrichment, respectively. Cu, Zn, Hg, and Co were 1.5, 1.88, 2.66, and 1.27 times the local background, respectively. Cu, Zn, and Hg mainly originated from anthropogenic sources, and Co may have derived from natural sources. The HM data of mangrove sedimentary cores in Zhanjiang Bay were obtained for the first time; high HM content appeared in the deep layer of the cores but not in the mangrove surface sediments. Both cores were well documented for the effects of natural and anthropogenic factors on the deposition process of HMs. Among them, the high enrichment of Hg in 1909–1921 may be closely related to human activities rather than natural formation. Before 1954, dense mangroves favored the accumulation and gradual increase of HMs. The intense human activity in 1945–1963 during the period of economic construction and reclamation of the Nansan Island Engineering led to significant increases in Cu, Zn, Pb, Cr, and Co, which reached their highest values in more than one hundred years. After 1963, anthropic factors such as deforestation and conversion to aquaculture sharply reduced mangrove area. Reclamation engineering enhanced tidal erosion. Natural factors such as precipitation, storm surge, sea-level rise, and high tides have accelerated the erosion and dilution of mangrove sediments in Zhanjiang Bay. These factors have led to the gradual reduction of HM content in sedimentary cores.

Wnt Signaling Pathways: A Role in Pain Processing - Yiting Tang; Yupeng Chen; Rui Liu; Weidong Li; Baojin Hua; Yanju Bao (NeuroMolecular Medicine, 2022)
The wingless-related integration site (Wnt) signaling pathway plays an essential role in embryonic development and nervous system regulation. It is critically involved in multiple types of neuropathic pain (NP), such as HIV-related NP, cancer pain, diabetic neuralgia, multiple sclerosis-related NP, endometriosis pain, and other painful diseases. Wnt signaling is also implicated in the pain induced by sciatic nerve compression injury and selective spinal nerve ligation. Thus, the Wnt signaling pathway may be a potential therapeutic target for NP.

Orbit determination, clock estimation and performance evaluation of BDS-3 PPP-B2b service - Chengpan Tang; Xiaogong Hu; Jinping Chen; Li Liu; Shanshi Zhou; Rui Guo; Xiaojie Li; Feng He; Jinhuo Liu; Jianhua Yang (Journal of Geodesy, 2022)

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Mesoscale eddies induce variability in the sea surface temperature gradient in the Kuroshio Extension - Rui Tang; Yi Yu; Jingyuan Xi; Wentao Ma; Yuntao Wang (Frontiers in Marine Science, 2022)
The Kuroshio Extension (KE) region is one of the most energetic regions in the global ocean where prominent mesoscale dynamics persistently occur. The spatial distribution and temporal evolution of the sea surface temperature (SST) gradient and mesoscale eddies in the KE are investigated. The SST gradient can be applied for identifying the fronts, and the SST gradient within two times the radii of the eddies is composited to quantify the impact of eddies on frontal activities. Depressed SST gradients are identified for eddies with both polarities, but prominent spatial variance in the SST gradient reveals that a large SST gradient is located to the north of anticyclones and along the south periphery for cyclones. The eddies are further separated into two groups depending on their location relative to the main path of the KE, as the background fields to the north and south of the KE are largely different. The spatial pattern, e.g., monopole and dipole features, and temporal variation in the SST gradient are fully studied over the lifespans of eddies. The results show that most eddies can significantly weaken the internal SST gradient and induce the horizontal redistribution of the SST gradient in surrounding regions. Cyclonic eddies north of the KE elevate the fronts along the periphery of eddies. The temporal variability in the SST gradient is prominent and largely varies for each group of eddies. This study offers quantitative analyses of the spatial and temporal relationships between eddies and fronts that are important for understanding the mesoscale dynamics in the world’s oceans.

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

The nexuses between carbon emissions, agriculture production efficiency, research and development, and government effectiveness: evidence from major agriculture-producing countries - Rizwana Yasmeen; Rui Tao; Wasi Ul Hassan Shah; Ihtsham Ul Haq Padda; Caihong Tang (Environmental Science and Pollution Research, 2022)

Thermal crosslinking synthesis of ethylene–vinyl acetate copolymer supported floating TiO2 photocatalyst: characterization and photocatalytic performance - Qiang Wu; Jizhong Meng; Hang Yao; Rui Tang; Shoujun Yuan; Yulan Wang; Wei Wang; Haiping Luo; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

Geographic information system and system dynamics combination technique for municipal solid waste treatment station site selection - Chen Wang; Fengqiu Zou; Jeffrey Boon Hui Yap; Rui Tang; Heng Li (Environmental Monitoring and Assessment, 2022)

Bone Marrow-Derived Alk1 Mutant Endothelial Cells and Clonally Expanded Somatic Alk1 Mutant Endothelial Cells Contribute to the Development of Brain Arteriovenous Malformations in Mice - Sonali S. Shaligram; Rui Zhang; Wan Zhu; Li Ma; Man Luo; Qiang Li; Miriam Weiss; Thomas Arnold; Nicolas Santander; Rich Liang; Leandro do Prado; Chaoliang Tang; et al. (Translational Stroke Research, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Combination Effects of Polyphenols Present in Sugarcane on Proliferation in MCF-7 Human Breast Cancer Cells - Yujiao Yang; Rui Zheng; Pingling Zhang; Jing Wen; Yue Luo; Zhengang Zhao; Lijun You; Chi-Tang Ho (Sugar Tech, 2022)

Impact of N application rate on tea (Camellia sinensis) growth and soil bacterial and fungi communities - Sheng Tang; Jingjie Zhou; Wankun Pan; Rui Tang; Qingxu Ma; Meng Xu; Tong Qi; Zhengbo Ma; Haoran Fu; Lianghuan Wu (Plant and Soil, 2022)

Synergistic Effect and Mechanism of Apoptosis Induction by Morphine and the HIV-1gp120V3 Loop in Hippocampal Neurons - Xueqin Yan; Zheng Gong; Rui Pan; Huili Wang; Haijie Tang; Hanyang He; Saixian Wen; Yongmei Fu; Jun Dong (Journal of Neuroimmune Pharmacology, 2022)

Plant contribution to the remediation of PAH-contaminated soil of Dagang Oilfield by Fire Phoenix - Xiaomei Wang; Jianping Sun; Rui Liu; Tingyu Zheng; Yingnan Tang (Environmental Science and Pollution Research, 2022)

Logging evaluation of shale oil “sweet spot” in Da’anzhai member, Longgang area, Sichuan Basin - Zonghui Lin; Jungang Lu; Rui Zhang; Shaoming Zhang; Longxiang Tang; Zhanghao Liu; Yaoting Li (Arabian Journal of Geosciences, 2022)

Chlorogenic acid, a natural product as potential inhibitor of COVID-19: virtual screening experiment based on network pharmacology and molecular docking - Wen-Xiang Wang; Ying-Rui Zhang; Shi-Ying Luo; Yun-Sen Zhang; Yi Zhang; Ce Tang (Natural Product Research, 2022)

Manganese Mitigates Heat Stress–Induced Apoptosis by Alleviating Endoplasmic Reticulum Stress and Activating the NRF2/SOD2 Pathway in Primary Chick Embryonic Myocardial Cells - Shizhen Qin; Rui Wang; Defu Tang; Shijiao Qin; Yanli Guo; Zhaoguo Shi (Biological Trace Element Research, 2022)

Acoustic Emission and Failure Characteristics of Shales with Different Brittleness Under AWJ Impingement - Hai Qu; Xiaoguang Wu; Pengpeng Huang; Shimao Tang; Rui Wang; Yushuang Hu (Rock Mechanics and Rock Engineering, 2022)

Interaction between organic matter and tetracycline in river sediments in cold regions - Changyong Wu; Rui Tang; Huiqi Li; Xiang Liu; Liya Fu; Yin Yu; Chunli Wan (Environmental Science and Pollution Research, 2022)

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

A longitudinal model for the Mayo Clinical Score and its sub-components in patients with ulcerative colitis - Sonoko Kawakatsu; Rui Zhu; Wenhui Zhang; Meina T. Tang; Tong Lu; Angelica L. Quartino; Matts Kågedal (Journal of Pharmacokinetics and Pharmacodynamics, 2022)
Clinical trials in patients with ulcerative colitis (UC) face the challenge of high and variable placebo response rates. The Mayo Clinical Score (MCS) is used widely as the primary endpoint in clinical trials to describe the clinical status of patients with UC. The MCS is comprised of four subscores, each scored 0, 1, 2 and 3: rectal bleeding (RB), stool frequency (SF), physician’s global assessment (PGA), and endoscopy (ENDO) subscore. Excluding the PGA subscore gives the modified MCS. Quantitative insight on the placebo response, and its impact on the components of the MCS over time, can better inform clinical trial design and interpretation. Longitudinal modeling of the MCS, and the modified MCS, can be challenging due to complex clinical trial design, population heterogeneity, and limited assessments for the ENDO subscore. The current study pooled patient-level placebo/standard of care (SoC) arm data from five clinical trials in the TransCelerate database to develop a longitudinal placebo response model that describes the MCS over time in patients with UC. MCS subscores were modeled using proportional odds models, and the removal of patients from the placebo/SoC arm, or “dropout”, was modeled using logistic regression models. The subscore and dropout models were linked to allow for the prediction of the MCS and the modified MCS. Stepwise covariate modeling identified prior exposure to TNF-α antagonists as a statistically significant predictor on the RB + SF subscore. Patients with prior exposure to TNF-α antagonists had higher post-baseline RB + SF subscores than naive patients.

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Continuous hydrodynamic mixing weakens the dominance of Microcystis: evidences from microcosm and lab experiments - Guijun Yang; Chunni Zhong; Wenwen Pan; Zheng Rui; Xiangming Tang; Ruipeng Yu; Weijian Qiu; Yun Guo (Environmental Science and Pollution Research, 2022)

Expression of Human Uncoupling Protein-1 in Escherichia coli Decreases its Survival Under Extremely Acidic Conditions - Rui Tang; Wei Sun; Ji-Chun Zhang; Liufeng Mao; Natalie Quanquin; Donghai Wu; Yirong Sun (Current Microbiology, 2022)

Evaluation of suitable qRT-PCR normalization genes for various citrus rootstocks - Wen He; Rui Xie; Huan Li; Yan Wang; Qing Chen; Yuanxiu Lin; Yunting Zhang; Ya Luo; Yong Zhang; Haoru Tang; Xiaorong Wang (Plant Biotechnology Reports, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Roots and microbiome jointly drive the distributions of 17 phytohormones in the plant soil continuum in a phytohormone‐specific manner - Yuqiu Lu; Enzhao Wang; Zhiyu Tang; Junpeng Rui; Yanling Li; Zhixi Tang; Weiling Dong; Xiongduo Liu; Timothy S. George; Alin Song; Fenliang Fan (Plant and Soil, 2022)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Insight into the Interaction Between Microplastics and Microorganisms Based on a Bibliometric and Visualized Analysis - Yanping Jiang; Wanjun Xia; Rui Zhao; Mengge Wang; Jinfeng Tang; Yongjun Wei (Bulletin of Environmental Contamination and Toxicology, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

An eco‐city design methodology for hilly areas of western China - Kai Lin; Zhengwei He; Zhujun Zhao; Jiaxin Chang; Keran Tang; Rui Qu; Li He (Earth Science Informatics, 2021)

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

Critical Review of Electro-kinetic Remediation of Contaminated Soils and Sediments: Mechanisms, Performances and Technologies - Ding Han; Xingyi Wu; Rui Li; Xianqiang Tang; Shangbin Xiao; Miklas Scholz (Water, Air, & Soil Pollution, 2021)
Remediation of contaminated soil and sediment is important for improving the eco-environmental quality. Electro-kinetic remediation (EKR) is an environmentally friendly technology to migrate and remove pollutants from the soil and sediment matrix. This paper analyses the mechanism and performance of EKR of heavy metals, organic pollutants, and compound pollutants. Moreover, the effect of optimizing individual EKR through soil and sediment pre-treatment (adding acid/oxidant/co-solvent/surfactant, stirring, heating, etc.), electrode optimization (exchange electrode, anode approximation, electrode matrix, etc.), and applying multi-technology combination (electro-kinetic permeable reaction barrier/Fenton/ion, exchange membrane/ultrasonic/electrolyte enhancement, etc.) was evaluated. Factors including incomplete separation of pollutants, variation in physico-chemical properties and microstructure of soil/sediment, and difficulties in in situ practice have restrained the field application of EKR. To solve the above technical challenge, an integrated EKR technology based on pollutant in situ separation, followed by separated contaminant treatment, and subsequent valuable elements recovery is proposed.

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Synthesis and biological evaluations of a series of calycanthaceous analogues as antifungal agents - Shaojun Zheng; Rui Zhu; Bing Tang; Lizhuang Chen; Hongjin Bai; Jiwen Zhang (Natural Product Research, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Selective cytotoxicity of epidithiodiketopiperazine DC1149B, produced by marine-derived Trichoderma lixii on the cancer cells adapted to glucose starvation - Rui Tang; Atsushi Kimishima; Ryosuke Ishida; Andi Setiawan; Masayoshi Arai (Journal of Natural Medicines, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s11418-021-01499-w

Experimental studies on the interaction mechanism of landslide stabilizing piles and sandwich-type bedrock - Zhen Zhong; Rui Yong; Huiming Tang; Changdong Li; Shigui Du (Landslides, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

BeiDou-3 broadcast clock estimation by integration of observations of regional tracking stations and inter-satellite links - Yufei Yang; Yuanxi Yang; Xiaogong Hu; Chengpan Tang; Rui Guo; Zhanshi Zhou; Junyi Xu; Junyang Pan; Mudan Su (GPS Solutions, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Fracture characterization in oil-based mud boreholes using image logs: example form tight sandstones of Lower Cretaceous Bashijiqike Formation of KS5 well area, Kuqa Depression, Tarim Basin, China - Rui Yuan; Denglin Han; Yangang Tang; Hongxing Wei; Tao Mo; Chenchen Wang (Arabian Journal of Geosciences, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

Seasonal variability and dynamics of coastal sea surface temperature fronts in the East China Sea - Lu Cao; Rui Tang; Wei Huang; Yuntao Wang (Ocean Dynamics, 2021)

CircRNA-23525 regulates osteogenic differentiation of adipose-derived mesenchymal stem cells via miR-30a-3p - Zeyou Guo; Luyang Zhao; Suhui Ji; Ting Long; Yanling Huang; Rui Ju; Wei Tang; Weidong Tian; Jie Long (Cell and Tissue Research, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

Duloxetine-Induced Neural Cell Death and Promoted Neurite Outgrowth in N2a Cells - Wanli Gao; Rui Chen; Nan Xie; Daolin Tang; Borong Zhou; Ding Wang (Neurotoxicity Research, 2020)
Duloxetine is a clinical drug that is primarily used for treatment of depression and pain, but it has side effects of addiction and tolerance. Cytochrome P450 (CYP) is its metabolic enzyme, and the drug’s biofunction results from its neuro-protective effect in animal and cell models. We aimed to investigate the duloxetine-induced neural cytotoxicity effect and its performance in an N2a cell neurite outgrowth model. Cell death was assessed as cell viability using a Cell Count Kit-8 and further evaluated using bright-field images, propidium iodide (PI) and annexin V staining, colony-formation analysis, TUNEL staining of the cells, and biochemical testing. N2a cells were committed to differentiation by serum withdrawal and RA induction, and the neurite outgrowth was evaluated as the number of differentiated cells, longest neurite length, and average neurite length. Cell cycle analysis, PI and annexin V staining, mRNA expression, and biochemical testing were used to evaluate the drug effects on differentiation. The induction of neural cell death by duloxetine was not affected by classic cell death inhibitors but was promoted by the CYP inducer rifampicin. N2a cell neurite outgrowth was promoted by duloxetine via reduction of the CYP2D6 and MDA levels and induction of Bdnf protein levels. Duloxetine induces neural cell death through effects on CYP and promotes N2a cell neurite outgrowth by regulating CYP, Bdnf protein, and the intracellular lipid peroxidation level.

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

A predicted protein functional network aids in novel gene mining for characteristic secondary metabolites in tea plant (Camellia sinensis) - Shihua Zhang; Yong Ma; Rui Zhang; Xiaolong He; Ying Chen; Jingke Du; Chi-tang Ho; Youhua Zhang; Guomin Han; Xiaoyi Hu (Journal of Biosciences, 2020)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

High expression of long non-coding RNA Linc-A associates with poor survival in patients with colorectal cancer - Chong Zhao; Can Gan; Yang Xiao; Rui Liu; Linhao Zhang; Tian Lan; Yanting Ye; Huan Tong; Zhiyin Huang; Chengwei Tang; Jinhang Gao (Molecular Biology Reports, 2020)

Surface fractal dimensions as a characterization parameter for methane adsorption–induced coal strains - Jie Zhu; Yang Zhang; Rui Zhang; Bo Zhang; Jun Tang; Fa He (Arabian Journal of Geosciences, 2020)

On the use of Markov chain models for drought class transition analysis while considering spatial effects - Wentao Yang; Min Deng; Jianbo Tang; Rui Jin (Natural Hazards, 2020)

The direct and indirect effects of democracy on carbon dioxide emissions in BRICS countries: evidence from panel quantile regression - Yinghua Ren; Lisi Liu; Huiming Zhu; Rui Tang (Environmental Science and Pollution Research, 2020)

Thallus sectioning as an efficient monospore release method in Pyropia yezoensis (Bangiales, Rhodophyta) - Nianci Chen; Lei Tang; Xiaowei Guan; Rui Chen; Min Cao; Yunxiang Mao; Dongmei Wang (Journal of Applied Phycology, 2020)
The red seaweed Pyropia yezoensis is a marine crop of important economic value and is widely cultivated in the coastal areas of northern China. The current seedling-raising system relies on the germination of conchospores, a process not fast enough to meet the increasing demand from farmers. In this study, we developed a monospore-dependent seedling method based on the asexual reproduction of the Pyropia thallus. The Pyropia thallus was physically sectioned into small pieces (microthalli) that were cultivated at 15 °C. The algal cells in the microthalli became morphologically condensed, underwent cell division, and then developed into monospores on the 5th day. The monospores were able to attach to the seeding rope in 24 h and germinated into healthy thalli. To optimize the efficiency of monospore release, we tested the effect of temperature and the size and original positions of the microthalli as well as the age of the mother thallus. Microthalli with a size of 30–50 cells from the middle and apex of 21-day-old thalli cultivated at 15 ° C yielded the optimum production of monospores. Theoretically, in this thallus-to-thallus seeding strategy, 0.1 g of thallus could produce at least 10 7 monospores, with the same number of offspring thallus seedlings. Taking all of these advantages together, including the high efficiency, short time, low cost and easy operation, this physical sectioning method could serve as a promising seed source especially for new cultivars with superior traits in Pyropia farming and rapid replenishment of seedlings when thalli undergo disastrous diseases.

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Evaluating landslide susceptibility based on cluster analysis, probabilistic methods, and artificial neural networks - Rui-Xuan Tang; Pinnaduwa H. S. W. Kulatilake; E-Chuan Yan; Jing-Sen Cai (Bulletin of Engineering Geology and the Environment, 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

Ambient temperature alters body size and gut microbiota of Xenopus tropicalis - Jiaying Li; Junpeng Rui; Yulong Li; Na Tang; Songping Zhan; Jianping Jiang; Xiangzhen Li (Science China Life Sciences, 2020)

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

Reduction of heavy metals leaching and pore volume in high-volume fly ash cement pastes by adding nano-SiO2 - Qian Huang; Shuai Tang; Ya You; Yibo Chen; Haisen Deng; Rui Tian (Environmental Science and Pollution Research, 2020)

Selective catalytic reduction of NOx by NH3 over CeVO4-CeO2 nanocomposite - Chao-peng Duan; Rui-tang Guo; Gui-lin Wu; Wei-guo Pan (Environmental Science and Pollution Research, 2020)

Impact of green finance on economic development and environmental quality: a study based on provincial panel data from China - Xiaoguang Zhou; Xinmeng Tang; Rui Zhang (Environmental Science and Pollution Research, 2020)

Impact of selenium, zinc and their interaction on key enzymes, grain yield, selenium, zinc concentrations, and seedling vigor of biofortified rice - Hla Hla Ei; Tengda Zheng; Muhammad Umer Farooq; Rui Zeng; Yang Su; Yujie Zhang; Yuanke Liang; Zhichen Tang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2020)

The enhancement of NH3-SCR performance for CeO2 catalyst by CO pretreatment - Ping Zhang; Rui-tang Guo; Li-jun Wu; Wei-guo Pan (Environmental Science and Pollution Research, 2020)

Secalonic acid D as a selective cytotoxic substance on the cancer cells adapted to nutrient starvation - Rui Tang; Atsushi Kimishima; Andi Setiawan; Masayoshi Arai (Journal of Natural Medicines, 2020)

Comparative study on adsorption and immobilization of Cd(II) by rape component biomass - Chao Hu; Hongqing Hu; Yafang Tang; Yujun Dai; Zefeng Wang; Rui Yan (Environmental Science and Pollution Research, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Selective cytotoxicity of epidithiodiketopiperazine DC1149B, produced by marine-derived Trichoderma lixii on the cancer cells adapted to glucose starvation - Rui Tang; Atsushi Kimishima; Ryosuke Ishida; Andi Setiawan; Masayoshi Arai (Journal of Natural Medicines, 2020)
The core of solid tumors is characterized by hypoxia and a nutrient-starved microenvironment and has gained much attention as targets of anti-cancer drugs. In the course of search for selective growth inhibitors against the cancer cells adapted to nutrient starvation, epidithiodiketopiperazine DC1149B ( 1 ) together with structurally related compounds, trichodermamide A ( 2 ) and aspergillazine A ( 3 ), were isolated from culture extract of marine-derived Trichoderma lixii . Compounds 1 exhibited potent selective cytotoxic activity against human pancreatic carcinoma PANC-1 cells cultured under glucose-starved conditions with IC 50 values of 0.02 µM. The selective index of the compound 1 was found to be 35,500-fold higher for cells cultured under glucose-starved conditions than those under the general culture conditions. The mechanistic analysis indicated that compound 1 inhibited the response of the ER stress signaling. In addition, these effects of compound 1 could be mediated by inhibiting complex II in the mitochondrial electron transport chain.

Selenium Mitigates Cadmium-Induced Adverse Effects on Trace Elements and Amino Acids Profiles in Chicken Pectoral Muscles - Kui-Chao Qu; Hui-Qin Li; Kou-Kou Tang; Zhen-Yong Wang; Rui-Feng Fan (Biological Trace Element Research, 2020)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

Three new Coccomyces species from Shennongjia National Nature Reserve in China - Tu Lv; Wan-Peng Tang; Shu-Rui Cai; Cheng-Lin Hou (Mycological Progress, 2019)

Synthesis and antitumor evaluation of novel fused heterocyclic 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazole derivatives - Xiao-Jia Liu; Hai-Ying Liu; Hai-Xin Wang; Yan-Ping Shi; Rui Tang; Shuai Zhang; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Changes in bacterial community structure and humic acid composition in response to enhanced extracellular electron transfer process in coastal sediment - Jiulong Zhao; Long Wang; Lili Tang; Rui Ren; Wuxin You; Robina Farooq; Zejie Wang; Yongyu Zhang (Archives of Microbiology, 2019)

Selenium alleviates cadmium-induced inflammation and meat quality degradation via antioxidant and anti-inflammation in chicken breast muscles - Kou-Kou Tang; Hui-Qin Li; Kui-Chao Qu; Rui-Feng Fan (Environmental Science and Pollution Research, 2019)

Alterations in transcriptome and antioxidant activity of naturally aged mice exposed to selenium-rich rice - Rui Zeng; Yuanke Liang; Muhammad Umer Farooq; Yujie Zhang; Hla Hla Ei; Zhichen Tang; Tengda Zheng; Yang Su; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2019)

Oxidation of high iron content electroplating sludge in supercritical water: stabilization of zinc and chromium - Bo Zhang; Yinghui Wang; Xingying Tang; Shaopeng Wang; Chaoshuai Wei; Rui Wang; Wei Zhang (Environmental Science and Pollution Research, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

RNA-Sequencing Analysis Reveals Critical Roles of Hormone Metabolism and Signaling Transduction in Seed Germination of Andrographis paniculata - Jiayun Tong; Rui He; Xiaoting Tang; Mingzhi Li; Tao Yi (Journal of Plant Growth Regulation, 2019)

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

Study on RSS/AOA hybrid localization in life detection in huge disaster situation - ShiYang Tang; XueMing Shu; Jun Hu; Rui Zhou; ShiFei Shen; SiYang Cao (Natural Hazards, 2019)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

A factor analysis of landscape metrics of particles deposited on leaf surface - Lin Lin; Guojian Chen; Jingli Yan; Rongli Tang; Xiu Yuan; Zhe Yin; Rui Zhang (Environmental Science and Pollution Research, 2018)

The distribution and partitioning of trace metals (Pb, Cd, Cu, and Zn) and metalloid (As) in the Beijiang River - Rui Li; Changyuan Tang; Yingjie Cao; Tao Jiang; Jianyao Chen (Environmental Monitoring and Assessment, 2018)

An adaptive sampling approach to reduce uncertainty in slope stability analysis - Jing-Sen Cai; Tian-Chyi Jim Yeh; E-Chuan Yan; Rui-Xuan Tang; Jet-Chau Wen; Shao-Yang Huang (Landslides, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

Proline dehydrogenase gene (PRODH) polymorphisms and schizophrenia susceptibility: a meta-analysis - Xingzhi Guo; Peng Tang; Caiping Yang; Rui Li (Metabolic Brain Disease, 2018)

Enhanced phosphorus removal using acid-treated magnesium slag particles - Xianqiang Tang; Rui Li; Min Wu; Lei Dong; Zhenhua Wang (Environmental Science and Pollution Research, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Analysis of miRNA-seq combined with gene expression profile reveals the complexity of salinity stress response in Oryza sativa - Qingwei Wang; Tianlong Geng; Shuhua Zhu; Rui Li; Yongao Tong; Shenghua Wang; Fang Chen; Lin Tang; Yang He (Acta Physiologiae Plantarum, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Prospect of recovering phosphorus in magnesium slag-packed wetland filter - Xianqiang Tang; Min Wu; Rui Li; Zhenhua Wang (Environmental Science and Pollution Research, 2017)

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

Stability analysis of stratified rock slopes with spatially variable strength parameters: the case of Qianjiangping landslide - Huiming Tang; Rui Yong; M. A. M. Ez Eldin (Bulletin of Engineering Geology and the Environment, 2017)

Site-directed mutagenesis under the direction of in silico protein docking modeling reveals the active site residues of 3-ketosteroid-Δ1-dehydrogenase from Mycobacterium neoaurum - Ning Qin; Yanbing Shen; Xu Yang; Liqiu Su; Rui Tang; Wei Li; Min Wang (World Journal of Microbiology and Biotechnology, 2017)

Multi-parametric study of temperature and thermal damage of tumor exposed to high-frequency nanosecond-pulsed electric fields based on finite element simulation - Yan Mi; Shaoqin Rui; Chengxiang Li; Chenguo Yao; Jin Xu; Changhao Bian; Xuefeng Tang (Medical & Biological Engineering & Computing, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Stability design charts for homogeneous slopes under typical conditions based on the double shear strength reduction technique - Gaopeng Tang; Lianheng Zhao; Li Liang; Shi Zuo; Rui Zhang (Arabian Journal of Geosciences, 2017)

Three new phenylpropanoids from Lavandula angustifolia and their bioactivities - Shiyun Tang; Jianlian Shi; Chunbo Liu; Rui Jiang; Wei Zhao; Xin Liu; Nengjun Xiang; Yongkuan Chen; Qinpeng Shen; Mingming Miao; Zhihua Liu; Guangyu Yang (Natural Product Research, 2017)

Comprehensive Analysis of R2R3-MYB Genes During Adventitious Root Formation in Cuttings of Morus alba - Xiao Long Du; Xu Cao; Chao Rui Yin; Zhuang Tang; Wei Du; Yue Yuan Ban; Jia Ling Cheng (Journal of Plant Growth Regulation, 2017)

Enantioselective synthesis and evaluation of 4-styryldihydropyrimidin-2-thiones as anti-proliferative agents - Han Yu; Guoyong Dai; Qiu-Rui He; Jiang-Jiang Tang (Medicinal Chemistry Research, 2017)

Model testing of the spatial–temporal evolution of a landslide failure - Junwei Ma; Huiming Tang; Xinli Hu; Antonio Bobet; Rui Yong; Mutasim A. M. Ez Eldin (Bulletin of Engineering Geology and the Environment, 2017)

Occurrence, fate, and risk assessment of selected endocrine disrupting chemicals in wastewater treatment plants and receiving river of Shanghai, China - Gang Xu; Sihan Ma; Liang Tang; Rui Sun; Jiajia Xiang; Bentuo Xu; Yangyang Bao; Minghong Wu (Environmental Science and Pollution Research, 2016)

Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2016)
Abnormal angiogenesis is critical for portal hypertension in cirrhosis. Except for etiological treatment, no efficient medication or regime has been explored to treat the early stage of cirrhosis when angiogenesis is initiated or overwhelming. In this study, we explored an anti-angiogenesis effort through non-cytotoxic drugs octreotide and celecoxib to treat early stage of cirrhotic portal hypertension in an animal model. Peritoneal injection of thioacetamide (TAA) was employed to induce liver cirrhosis in rats. A combination treatment of celecoxib and octreotide was found to relieve liver fibrosis, portal venous pressure, micro-hepatic arterioportal fistulas, intrahepatic and splanchnic angiogenesis. Celecoxib and octreotide exerted their anti-angiogenesis effect via an axis of cyclooxygenase-2/prostaglandin E2/EP-2/somatostatin receptor-2, which consequently down-regulated phosphorylation of extracellular signal-regulated kinase (p-ERK)–hypoxia-inducible factor-1α (HIF-1α)–vascular endothelial growth factor (VEGF) integrated signaling pathways. In conclusions, combination of celecoxib and octreotide synergistically ameliorated liver fibrosis and portal hypertension of the cirrhotic rats induced by TAA via the inhibition of intrahepatic and extrahepatic angiogenesis. The potential mechanisms behind the regimen may due to the inactivation of p-ERK–HIF-1α–VEGF signaling pathway.

Proof-of-Concept of Polymeric Sol-Gels in Multi-Drug Delivery and Intraoperative Image-Guided Surgery for Peritoneal Ovarian Cancer - Matthew McKenzie; David Betts; Amy Suh; Kathryn Bui; Rui Tang; Kexian Liang; Samuel Achilefu; Glen S. Kwon; Hyunah Cho (Pharmaceutical Research, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Curdlan blocks the immune suppression by myeloid-derived suppressor cells and reduces tumor burden - Ke Rui; Jie Tian; Xinyi Tang; Jie Ma; Ping Xu; Xinyu Tian; Yungang Wang; Huaxi Xu; Liwei Lu; Shengjun Wang (Immunologic Research, 2016)

Effects of climate change on potential habitats of the cold temperate coniferous forest in Yunnan province, southwestern China - Wang-jun Li; Ming-chun Peng; Motoki Higa; Nobuyuki Tanaka; Tetsuya Matsui; Cindy Q. Tang; Xiao-kun Ou; Rui-wu Zhou; Chong-yun Wang; Hai-zhong Yan (Journal of Mountain Science, 2016)

Characterization of a NaCl-tolerant β-N-acetylglucosaminidase from Sphingobacterium sp. HWLB1 - Junpei Zhou; Zhifeng Song; Rui Zhang; Limei Ding; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2016)

Slope spectrum variation in a simulated loess watershed - Fayuan Li; Guoan Tang; Chun Wang; Lingzhou Cui; Rui Zhu (Frontiers of Earth Science, 2016)

Current approaches to reduce or eliminate mitochondrial DNA mutations - Liang Yang; Tingfang Mei; Xiaobing Lin; Haite Tang; Yi Wu; Rui Wang; Jinglei Liu; Zahir Shah; Xingguo Liu (Science China Life Sciences, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Upregulation of long noncoding RNA TMEVPG1 enhances T helper type 1 cell response in patients with Sjögren syndrome - Juan Wang; Huiyong Peng; Jie Tian; Jie Ma; Xinyi Tang; Ke Rui; Xinyu Tian; Yungang Wang; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2016)

Over-expression of StLCYb increases β-carotene accumulation in potato tubers - Xiao-yan Song; Wen-jiao Zhu; Rui-min Tang; Jing-hui Cai; Min Chen; Qing Yang (Plant Biotechnology Reports, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Seismic Stability of Gravity Retaining Structures by Pseudo-Dynamic Method - Rui Huang; Tang-Dai Xia (Marine Georesources & Geotechnology, 2016)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Tempo-spatial analysis of water quality in tributary bays of the Three Gorges Reservoir region (China) - Jialiang Tang; Tao Wang; Bo Zhu; Pei Zhao; Yi Xiao; Rui Wang (Environmental Science and Pollution Research, 2015)

Mertk deficiency alters expression of micrornas in the retinal pigment epithelium cells - Yong Tang; Qingjun Lu; Yunrong Wei; Lixia Han; Rui Ji; Qiutang Li; Qingxian Lu (Metabolic Brain Disease, 2015)

Suppression of spring rain by surface greening over North China Plain - Xuezhen Zhang; Qiuhong Tang; Jingyun Zheng; Quansheng Ge; Rui Mao (International Journal of Climatology, 2015)
Surface greenness and rainfall in spring have changed from the 1980s to 1990s over the North China Plain (NCP). The greenness changes are characterized by large increase in north and little in south with an obvious greening zone from the centre of the NCP to the northeast. The rainfall change has a similar spatial pattern with reversed sign. The correlation between changes in greenness and rainfall is significant and the correlation ( r = −0.71, p

Effect of Processing on Phenolic Antioxidants of Fruits, Vegetables, and Grains—A Review - Balunkeswar Nayak; Rui Hai Liu; Juming Tang (Critical Reviews in Food Science and Nutrition, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

Gene transcript profiles of the TIA biosynthetic pathway in response to ethylene and copper reveal their interactive role in modulating TIA biosynthesis in Catharanthus roseus - Ya-Jie Pan; Jia Liu; Xiao-Rui Guo; Yuan-Gang Zu; Zhong-Hua Tang (Protoplasma, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

China’s provincial CO2 emissions embodied in trade with implications for regional climate policy - Zhangqi Zhong; Rui Huang; Qinneng Tang; Xiaonan Cong; Zheng Wang (Frontiers of Earth Science, 2015)

Characterization of Sphingomonas sp. JB13 exo-inulinase: a novel detergent-, salt-, and protease-tolerant exo-inulinase - Junpei Zhou; Mozhen Peng; Rui Zhang; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Yajie Gao; Junrong Ren; Zunxi Huang (Extremophiles, 2015)

Detection and Analysis of 12 Heavy Metals in Blood and Hair Sample from a General Population of Pearl River Delta Area - Jiqiang Li; Dongzhi Cen; Donglan Huang; Xufeng Li; Jiajun Xu; Shilin Fu; Rui Cai; Xiaocong Wu; Ming Tang; Yao Sun; Jiren Zhang; Jingfen Zheng (Cell Biochemistry and Biophysics, 2014)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

FEM application to loess slope excavation and support: case study of Dong Loutian coal bunker, Shuozhou, China - Zhi Qing Li; Ibrahim Adewuyi Oyediran; Chuan Tang; Rui Lin Hu; Ying Xin Zhou (Bulletin of Engineering Geology and the Environment, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

A thermo-halo-tolerant and proteinase-resistant endoxylanase from Bacillus sp. HJ14 - Junpei Zhou; Qian Wu; Rui Zhang; Minghe Mo; Xianghua Tang; Junjun Li; Bo Xu; Junmei Ding; Qian Lu; Zunxi Huang (Folia Microbiologica, 2014)

Dynamic stability analysis of wedge in rock slope based on kinetic vector method - Weida Ni; Huiming Tang; Xiao Liu; Rui Yong; Zongxing Zou (Journal of Earth Science, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

The sensitivity analysis of different induced polarization models used in magnetotelluric method - Rui Tang; Peng Yu; Yang Xiang; Xu Zhang (Acta Geodaetica et Geophysica, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

MicroRNA-128 regulates the differentiation of rat bone mesenchymal stem cells into neuron-like cells by Wnt signaling - Rui Wu; Yue Tang; Wenqiao Zang; Yuanyuan Wang; Min Li; Yuwen Du; Guoqiang Zhao; Yuming Xu (Molecular and Cellular Biochemistry, 2014)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Comprehensive identification of high-frequency and co-occurring Mafa-DPA1, Mafa-DQA1, Mafa-DRA, and Mafa-DOA alleles in Vietnamese cynomolgus macaques - Ruirui Xiang; Huiling Zhang; Qing Deng; Rui Yue; Haite Tang; Yanqi Zhang; Fei Ling; Min Zhuo; Hongli Du; Shiqian Xu; Qiang Xu; Xiaoning Wang (Immunogenetics, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Over-expression of l-galactono-γ-lactone dehydrogenase increases vitamin C, total phenolics and antioxidant activity in lettuce through bio-fortification - Xinbo Guo; Rui Hai Liu; Xueqing Fu; Xiaofen Sun; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Recombinant High Density Lipoprotein Nanoparticles for Target-Specific Delivery of siRNA - Mengjie Rui; Hailing Tang; Yan Li; Xiaohui Wei; Yuhong Xu (Pharmaceutical Research, 2013)

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Novel association of a PROC variant with ischemic stroke in a Chinese Han population - Xuan Lu; Liang Tang; Kang Xu; Jie Ma; Tao Guo; Heng Mei; Rui Yang; Jianming Yu; Qingyun Wang; Yan Yang; Xiaorong Jian; Yu Hu (Human Genetics, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Over-expression of integrin-linked kinase correlates with aberrant expression of Snail, E-cadherin and N-cadherin in oral squamous cell carcinoma: implications in tumor progression and metastasis - Dan Zhao; Xiu-Fa Tang; Kai Yang; Ji-Yuan Liu; Xiang-Rui Ma (Clinical & Experimental Metastasis, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Molybdenite Re–Os and muscovite 40Ar/39Ar dating of quartz vein-type W–Sn polymetallic deposits in Northern Guangdong, South China - Hua-Wen Qi; Rui-Zhong Hu; Xiao-Fei Wang; Wen-Jun Qu; Xian-Wu Bi; Jian-Tang Peng (Mineralium Deposita, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells - Hao-Liang Ke; Ying-Wen Zhang; Bi-Fa Zhou; Rui-Tang Zhen (Natural Product Research, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Physiological responses of Catharanthus roseus to different nitrogen forms - Xiao-Rui Guo; Yuan-Gang Zu; Zhong-Hua Tang (Acta Physiologiae Plantarum, 2012)

Blind detection of liquefaction by existing methods for New Zealand M L6.3 earthquake on Feb. 22, 2011 - Rui Sun; Fuhui Tang; Longwei Chen (Earthquake Engineering and Engineering Vibration, 2011)

The staphylococcal nuclease prevents biofilm formation in Staphylococcus aureus and other biofilm-forming bacteria - JunNi Tang; MingSong Kang; HuanChun Chen; XianMing Shi; Rui Zhou; Juan Chen; YiWu Du (Science China Life Sciences, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Cytotoxic Activity and DNA-binding Properties of Xanthone Derivatives - Rui Shen; Peng Wang; Ning Tang (Journal of Fluorescence, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

Characterization of an Alien Chromosome of Oryza officinalis Transferred the Genomic and Cytological Environment of Oryza sativa - Gang Li; Ming Tang; Wei Hu; Guangcun He; Hong Liu; Xuequn Liu; Rui Qin (Journal of Plant Biology, 2010)

Isolation, Functional Characterization, and Expression Pattern of a Vacuolar Na+/H+ Antiporter Gene TrNHX1 from Trifolium repens L. - Rui Tang; Cui Li; Kai Xu; Yanhua Du; Tao Xia (Plant Molecular Biology Reporter, 2010)

Genetic transformation of the bast fiber plant ramie (Boehmeria nivea Gaud.) via Agrobacterium tumefaciens - Xiongfeng Ma; Chunming Yu; Shouwei Tang; Sandui Guo; Rui Zhang; Yanzhou Wang; Aiguo Zhu; Siyuan Zhu; Heping Xiong (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Characterization of the Photosynthetic Apparatus and Proteome of Roseobacter denitrificans - Kai Tang; Rui Zong; Fan Zhang; Na Xiao; Nianzhi Jiao (Current Microbiology, 2010)

No significant association between Fc receptor-like 3 gene polymorphisms and human leukocyte antigen-B27 positive ankylosing spondylitis in Han Chinese population - Guo Xia; Faming Pan; Fangfang Liao; Xiaowu Tang; Rui Ge; Yang Mei; Heping Pan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2010)

Synthesis, Crystal Structure, DNA-binding Properties and Cytotoxic Activity of the Copper (II) Complex Involving Xanthone - Rui Shen; Peng Wang; Ning Tang (Journal of Fluorescence, 2009)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Interethnic differences of PEPT2 (SLC15A2) polymorphism distribution and associations with cephalexin pharmacokinetics in healthy Asian subjects - Rui Liu; Audrey May Yi Tang; Yen Ling Tan; Lie Michael George Limenta; Edmund Jon Deoon Lee (European Journal of Clinical Pharmacology, 2009)

Fingerprint analysis of Lingzhi (Ganoderma) strains by high-performance liquid chromatography coupled with chemometric methods - Xian-Min Shi; Jing-Song Zhang; Qing-Jiu Tang; Yan Yang; Rui-Xia Hao; Ying-Jie Pan (World Journal of Microbiology and Biotechnology, 2008)

High level expression of a functional human/mouse chimeric anti-CD20 monoclonal antibody in milk of transgenic mice - Bo Tang; Shanshan Yu; Min Zheng; Fangrong Ding; Rui Zhao; Jianmin Zhao; Yunping Dai; Ning Li (Transgenic Research, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Genetic dissection of plant height by molecular markers using a population of recombinant inbred lines in maize - Tang Ji-hua; Teng Wen-tao; Yan Jian-bing; Ma Xi-qing; Meng Yi-jiang; Dai Jin-rui; Li Jian-Sheng (Euphytica, 2007)

A Study of Conservation Genetics in Cupressus chengiana, an Endangered Endemic of China, Using ISSR Markers - Bingqing Hao; Wang Li; Mu Linchun; Yao Li; Zhang Rui; Tang Mingxia; Bao Weikai (Biochemical Genetics, 2006)

Inhibition of TRPC5 channels by Ca2+-binding protein 1 in Xenopus oocytes - Mariko Kinoshita-Kawada; Jisen Tang; Rui Xiao; Shuji Kaneko; J. Kevin Foskett; Michael X. Zhu (Pflügers Archiv - European Journal of Physiology, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Differential expression of KV and KCa channels in vascular smooth muscle cells during 1-day culture - Guanghua Tang; Rui Wang (Pflügers Archiv - European Journal of Physiology, 2001)

A New Height Growth Model for Dominant and Codominant Trees - Fan-Rui Meng; Chao Ho Meng; Shouzheng Tang; Paul A. Arp (Forest Science, 1997)
A model was developed to predict height growth for dominant and codominant trees, using asymptotic tree height, and tree height at the age of maximum height growth as principal characteristics to express the influence of site on tree height. The proposed model has many desirable attributes: it (1) produces polymorphic site-index curves, (2) contains an inflection point, (3) asymptotically approaches maximum tree height as age increases, (4) is mathematically defined at the point of origin, and (5) has a theoretical base (pipe model theory) for height growth. Model performance was evaluated with stem analysis data taken from naturally regenerated forest stands of mature to overmature balsam fir (Abies balsamea [L.] Mill.) and black spruce (Picea mariana Mill.) growing in two separate regions within New Brunswick, Canada. The model was also evaluated by analyzing its ability to reproduce existing site index curves for red pine (Pinus resinosa Ait.). The results indicate that the proposed model performs slightly better than an existing 5-parameter model based on the Richards' growth function. For. Sci. 43(3):348-354.